Light-emitting element, display device, electronic device, and lighting device

By using specific organic compounds in the luminescent layer, the problem of low luminescence efficiency of fluorescent luminescent elements is solved, and a high efficiency, low driving voltage and high reliability luminescent effect is achieved.

CN119894227APending Publication Date: 2025-04-25SEMICON ENERGY LAB CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510041921.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-11-02
Filing Date
2018-10-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The luminescence efficiency of the fluorescent light emitting element is low, making it difficult to achieve the efficiency of the phosphorescent light emitting element, and while improving the luminescence efficiency, it is difficult to maintain good reliability and reduce power consumption.

Method used

By using an organic compound with specific energy transfer characteristics in the luminescent layer, including a first organic compound capable of converting triple excitation energy into luminescent, a second organic compound with a π-energy-rich and π-electron-deficient skeleton, and a third organic compound capable of converting single excitation energy into luminescent, in order to improve the luminescent efficiency and reduce the driving voltage.

Benefits of technology

High-efficiency light emission is achieved, driving voltage is reduced, the reliability of the light-emitting element is improved, and the power consumption is reduced, while color purity is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894227A_ABST
    Figure CN119894227A_ABST
Patent Text Reader

Abstract

Provided are a light-emitting element having high luminous efficiency, a display device, an electronic device, and a lighting device. The light-emitting element includes first to third organic compounds. The first organic compound has a function of converting triplet excitation energy into luminescence. The second organic compound is preferably a TADF material. The third organic compound is a fluorescent compound. Light emitted by the light-emitting element is obtained from the third organic compound. Triple excitation energy in the light-emitting layer is transferred to the third organic compound through the first organic compound due to anti-intersystem crossing caused by the second organic compound.
Need to check novelty before this filing date? Find Prior Art

Description

This invention application is a divisional application of the invention patent application with international application number PCT / IB2018 / 058227, international application date October 23, 2018, application number 201880068480.1 entering the Chinese national phase, and name “Light-emitting element, display device, electronic device and lighting device”. Technical Field

[0001] One embodiment of the present invention relates to a light-emitting element, or a display device, an electronic device, and a lighting device each including the light-emitting element.

[0002] Note that one embodiment of the present invention is not limited to the above-mentioned technical field. The technical field of one embodiment of the invention disclosed in this specification and the like relates to an object, a method, or a manufacturing method. In addition, one embodiment of the present invention relates to a process, a machine, a product, or a composition of matter. Therefore, specifically, as examples of the technical field of one embodiment of the present invention disclosed in this specification, semiconductor devices, display devices, liquid crystal display devices, light-emitting devices, lighting devices, power storage devices, storage devices, and methods for driving or manufacturing these devices can be cited. Background Art

[0003] In recent years, research and development of light-emitting devices that utilize electroluminescence (EL) have become increasingly intense. The basic structure of these light-emitting devices is a layer containing a light-emitting substance (EL layer) sandwiched between a pair of electrodes. By applying a voltage between the electrodes of the device, light from the light-emitting substance is generated.

[0004] Because the light-emitting element is self-luminous, a display device using it has the following advantages: good visibility, no need for a backlight, and low power consumption. Furthermore, the display device can be made thin and lightweight, and has a fast response speed.

[0005] When a light-emitting element (e.g., an organic EL element) uses an organic compound as a light-emitting substance and an EL layer containing the light-emitting substance is provided between a pair of electrodes, voltage is applied between the pair of electrodes, and electrons and holes are injected from the cathode and anode, respectively, into the light-emitting EL layer, causing current to flow. The injected electrons and holes then recombine, causing the light-emitting organic compound to enter an excited state, resulting in light emission.

[0006] As the types of excited states formed by organic compounds, there are singlet excited states (S * ) and triplet excited state (T *), the light emission from the singlet excited state is called fluorescence, and the light emission from the triplet excited state is called phosphorescence. * :T * The statistical ratio of triplet excitation energy to phosphorescence is 1:3. Therefore, compared to light-emitting elements using compounds that emit fluorescence (fluorescent compounds), light-emitting elements using compounds that emit phosphorescence (phosphorescent compounds) have higher luminescence efficiency. Consequently, in recent years, research and development of light-emitting elements using phosphorescent compounds that can convert triplet excitation energy into luminescence has become increasingly intense.

[0007] Light-emitting elements using phosphorescent compounds, particularly those emitting blue light, have not yet been put into practical use due to the difficulty in developing stable compounds with high triplet excitation energy levels. Therefore, efforts are underway to develop light-emitting elements using more stable fluorescent compounds, and to improve the luminous efficiency of light-emitting elements using fluorescent compounds (fluorescent light-emitting elements).

[0008] As an example, a fluorescent light-emitting element using a thermally activated delayed fluorescence (TADF) material is known. In a TADF material, a singlet excited state is generated from a triplet excited state by anti-intersystem crossing, and the singlet excited state is converted into light emission.

[0009] Patent Document 1 discloses a method in which, in a light-emitting element including a thermally activated delayed fluorescent material and a fluorescent compound, singlet excitation energy of the thermally activated delayed fluorescent material is transferred to the fluorescent compound to obtain light emission from the fluorescent compound. [References] [Patent Document]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 2014-45179

[0011] [Non-patent literature] [Non-patent document 1] T. Sajoto et al., J. Am. Chem. Soc., 2009, 131, 9813 Summary of the Invention

[0012] Fluorescent materials cannot convert triplet excitation energy into luminescence. Therefore, the luminous efficiency of fluorescent light-emitting components is often lower than that of phosphorescent light-emitting components. To achieve high brightness, fluorescent light-emitting components require large amounts of current, which increases heat generation and current load. Consequently, achieving good reliability in fluorescent light-emitting components is difficult.

[0013] To improve the luminous efficiency of fluorescent light-emitting devices, it is desirable that triplet excitation energy in the light-emitting layer be efficiently converted to singlet excitation energy or efficiently transferred to the fluorescent material. To this end, it is necessary to develop methods and materials that efficiently generate singlet excitation energy from triplet excitation states to further improve the luminous efficiency of light-emitting devices. Furthermore, materials with good carrier transport properties are desirable for the light-emitting layer to reduce the driving voltage.

[0014] In view of the above, an object of one embodiment of the present invention is to provide a light-emitting element with high luminous efficiency. In addition, an object of one embodiment of the present invention is to provide a light-emitting element with low driving voltage. In addition, an object of one embodiment of the present invention is to provide a light-emitting element with high reliability. In addition, an object of one embodiment of the present invention is to provide a light-emitting element with reduced power consumption. In addition, an object of one embodiment of the present invention is to provide a light-emitting element with high color purity. In addition, an object of one embodiment of the present invention is to provide a novel light-emitting element. In addition, an object of one embodiment of the present invention is to provide a novel light-emitting device. In addition, an object of one embodiment of the present invention is to provide a novel electronic device.

[0015] Note that the description of the above-mentioned objectives does not preclude the existence of other objectives. One embodiment of the present invention does not necessarily need to achieve all of the above-mentioned objectives. In addition, objectives other than the above-mentioned objectives may be known and derived from the description of the specification, etc.

[0016] As described above, there is a need to develop a method for efficiently converting triplet excitation energy into luminescence in a fluorescent light-emitting element. To achieve this, it is necessary to improve the energy transfer efficiency between the materials used in the light-emitting layer.

[0017] In view of the above, one embodiment of the present invention is a light-emitting element comprising a light-emitting layer between a pair of electrodes. The light-emitting layer comprises a first organic compound, a second organic compound, and a third organic compound. The first organic compound has a function of converting triplet excitation energy into light emission. The difference between the singlet excitation energy of the second organic compound and the triplet excitation energy of the second organic compound is 0 eV to 0.2 eV. The third organic compound has a function of converting singlet excitation energy into light emission. Light emitted from the light-emitting layer includes light emitted from the third organic compound.

[0018] Another embodiment of the present invention is a light-emitting element comprising a light-emitting layer between a pair of electrodes. The light-emitting layer comprises a first organic compound, a second organic compound, and a third organic compound. The first organic compound converts triplet excitation energy into luminescence. The second organic compound has a π-electron-rich skeleton and a π-electron-deficient skeleton. The third organic compound converts singlet excitation energy into luminescence. Light emitted from the light-emitting layer includes light emitted from the third organic compound.

[0019] Another embodiment of the present invention is a light-emitting element comprising a light-emitting layer between a pair of electrodes. The light-emitting layer comprises a first organic compound, a second organic compound, and a third organic compound. The first organic compound and the second organic compound are capable of forming an exciplex. The first organic compound has the function of converting triplet excitation energy into light emission. The difference between the singlet excitation energy level of the second organic compound and the triplet excitation energy level of the second organic compound is 0 eV to 0.2 eV. The third organic compound has the function of converting singlet excitation energy into light emission. Light emitted from the light-emitting layer includes light emitted from the third organic compound.

[0020] Another embodiment of the present invention is a light-emitting element comprising a light-emitting layer between a pair of electrodes. The light-emitting layer comprises a first organic compound, a second organic compound, and a third organic compound. The first organic compound and the second organic compound are capable of forming an exciplex. The first organic compound has the function of converting triplet excitation energy into luminescence. The second organic compound has a π-electron-rich skeleton and a π-electron-deficient skeleton. The third organic compound has the function of converting singlet excitation energy into luminescence. Light emitted from the light-emitting layer includes light emitted from the third organic compound.

[0021] In any of the above-described embodiments, the first organic compound preferably has a function of supplying excitation energy to the third organic compound.

[0022] In any of the above-mentioned embodiments, the exciplex preferably has a function of supplying excitation energy to the third organic compound.

[0023] In any of the above embodiments, the π-electron-rich skeleton and the π-electron-deficient skeleton are preferably directly bonded.

[0024] In any of the above embodiments, the triplet excitation energy level of the first organic compound is preferably equal to or higher than the singlet excitation energy level of the third organic compound.

[0025] In any of the above embodiments, the first organic compound preferably comprises Ru, Rh, Pd, Os, Ir, or Pt.

[0026] In any of the above embodiments, the first organic compound preferably has a function of emitting phosphorescence.

[0027] In any of the above embodiments, the lowest triplet excitation energy level of the first organic compound is preferably lower than the lowest triplet excitation energy level of the second organic compound.

[0028] In any of the above-mentioned embodiments, the emission spectrum of the exciplex preferably has a region overlapping with the absorption band on the longest wavelength side of the absorption spectrum of the third organic compound.

[0029] In any of the above embodiments, the first organic compound preferably has a light emission quantum yield of 0% or more and 40% or less at room temperature.

[0030] In any of the above embodiments, the third organic compound preferably emits fluorescence.

[0031] In addition, another embodiment of the present invention is a display device including a light-emitting element of each of the above structures, and at least one of a color filter and a transistor. In addition, another embodiment of the present invention is an electronic device including the above display device, and at least one of a housing and a touch sensor. In addition, another embodiment of the present invention is a lighting device including a light-emitting element of each of the above structures, and at least one of a housing and a touch sensor. In addition, one embodiment of the present invention is that its scope includes not only a light-emitting device having a light-emitting element but also an electronic device having a light-emitting device. Therefore, the light-emitting device in this specification refers to an image display device or a light source (including a lighting device). In addition, the light-emitting device sometimes also includes the following modules: a display module in which a connector such as an FPC (Flexible Printed Circuit) or a TCP (Tape Carrier Package) is installed in the light-emitting element; a display module in which a printed circuit board is provided at the end of the TCP; or a display module in which an IC (integrated circuit) is directly mounted on the light-emitting element by a COG (Chip On Glass) method.

[0032] According to one embodiment of the present invention, a light-emitting element with high luminous efficiency can be provided. In addition, according to one embodiment of the present invention, a light-emitting element with low driving voltage can be provided. In addition, according to one embodiment of the present invention, a light-emitting element with high reliability can be provided. In addition, according to one embodiment of the present invention, a light-emitting element with reduced power consumption can be provided. In addition, according to one embodiment of the present invention, a light-emitting element with high color purity can be provided. In addition, according to one embodiment of the present invention, a novel light-emitting element can be provided. In addition, according to one embodiment of the present invention, a novel light-emitting device can be provided. In addition, according to one embodiment of the present invention, a novel electronic device can be provided.

[0033] Note that the description of these effects does not preclude the existence of other effects. Furthermore, an embodiment of the present invention does not necessarily need to have all of the above-mentioned effects. Furthermore, effects other than the above-mentioned effects can be known and derived from the description of the specification, drawings, claims, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In the attached figure: Figure 1A and Figure 1B is a schematic cross-sectional view of a light-emitting element according to one embodiment of the present invention, Figure 1C shows the energy level correlation of the light-emitting layer; Figure 2A and Figure 2B The following shows the energy level correlation of the light-emitting layer of the light-emitting element according to one embodiment of the present invention. Figure 3 The following shows the energy level correlation of the light-emitting layer of the light-emitting element according to one embodiment of the present invention. Figure 4A and Figure 4B The following shows the energy level correlation of the light-emitting layer of the light-emitting element according to one embodiment of the present invention. Figure 5 is a schematic cross-sectional view of a light-emitting element according to one embodiment of the present invention; Figure 6A and Figure 6B 1 is a plan view and a schematic cross-sectional view illustrating a display device according to an embodiment of the present invention; Figure 7A and Figure 7B is a schematic cross-sectional view illustrating a display device according to one embodiment of the present invention; Figure 8A and Figure 8B is a schematic cross-sectional view illustrating a display device according to one embodiment of the present invention; 9A to 9D An electronic device according to an embodiment of the present invention is shown; Figures 10A to 10CAn electronic device according to an embodiment of the present invention is shown; Figure 11A and Figure 11B An electronic device according to an embodiment of the present invention is shown; Figure 12 A lighting device according to an embodiment of the present invention is shown; Figure 13 The current efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 14 shows the current-voltage characteristics of the light-emitting element according to the embodiment; Figure 15 The external quantum efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 16 shows an emission spectrum of a light-emitting element according to an embodiment; Figure 17 shows the results of time-resolved luminescence measurement according to the embodiment; Figure 18 shows the relationship between the emission spectrum and the absorption spectrum according to the embodiment; Figure 19A and Figure 19B shows transition fluorescence characteristics according to an embodiment; Figure 20 shows the emission spectra of the compounds according to the examples; Figure 21 shows the emission spectra of the compounds according to the examples; Figure 22 shows the reliability test results of the light emitting element according to the embodiment; Figure 23 The current efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 24 shows the current-voltage characteristics of the light-emitting element according to the embodiment; Figure 25 The external quantum efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 26 shows an emission spectrum of a light-emitting element according to an embodiment; Figure 27 shows the results of time-resolved luminescence measurement according to the embodiment; Figure 28 shows the reliability test results of the light emitting element according to the embodiment; Figure 29 The current efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 30 shows the current-voltage characteristics of the light-emitting element according to the embodiment; Figure 31The external quantum efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 32 shows an emission spectrum of a light-emitting element according to an embodiment; Figure 33 shows the results of time-resolved luminescence measurement according to the embodiment; Figure 34 shows the results of time-resolved luminescence measurement according to the embodiment; Figure 35 shows emission spectra of compounds according to Examples; Figure 36 shows the reliability test results of the light emitting element according to the embodiment; Figure 37 The current efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 38 shows the current-voltage characteristics of the light-emitting element according to the embodiment; Figure 39 The external quantum efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 40 shows an emission spectrum of a light-emitting element according to an embodiment; Figure 41 shows the results of time-resolved luminescence measurement according to the embodiment; Figure 42 shows emission spectra of compounds according to Examples; Figure 43 shows the reliability test results of the light emitting element according to the embodiment; Figure 44 The current efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 45 shows the current-voltage characteristics of the light-emitting element according to the embodiment; Figure 46 The external quantum efficiency-luminance characteristics of the light-emitting element according to the embodiment are shown; Figure 47 shows an emission spectrum of a light-emitting element according to an embodiment; Figure 48 shows an emission spectrum of a light-emitting element according to an embodiment; Figure 49 shows the results of time-resolved luminescence measurement according to the embodiment; Figure 50 The relationship between the emission spectrum and the absorption spectrum according to the embodiment is shown. DETAILED DESCRIPTION

[0035] The following describes embodiments of the present invention in detail with reference to the accompanying drawings. Note that the present invention is not limited to the following description, and its embodiments and details may be modified in various forms without departing from the spirit and scope of the present invention. Therefore, the present invention should not be construed as being limited to the embodiments and examples described below.

[0036] Furthermore, for ease of understanding, the positions, sizes, and ranges of various components shown in the drawings and the like may not necessarily represent their actual positions, sizes, and ranges. Therefore, the disclosed invention is not necessarily limited to the positions, sizes, and ranges disclosed in the drawings and the like.

[0037] In addition, in this specification and other documents, ordinal numbers such as "first" and "second" are used to facilitate understanding. However, these numbers do not always indicate the order of steps or the order of stacking. Therefore, for example, "first" can be appropriately replaced with "second" or "third" for explanation. In addition, the ordinal numbers described in this specification and other documents may not be consistent with the ordinal numbers used to designate an embodiment of the present invention.

[0038] Note that in this specification and the like, when describing the configuration of the invention using drawings, reference numerals may be used in common to represent the same components in different drawings.

[0039] In this specification, "film" and "layer" may be interchanged. For example, "conductive layer" may be replaced with "conductive film." Also, "insulating film" may be replaced with "insulating layer."

[0040] In this specification, the singlet excited state (S * ) refers to a singlet state with excitation energy. In addition, the S1 energy level is the lowest energy level of the singlet excitation energy level, which refers to the excitation energy level of the lowest singlet excitation state (S1 state). In addition, the triplet excitation state (T * ) refers to a triplet state having excitation energy. In addition, the T1 energy level is the lowest energy level of the triplet excited energy level, and it refers to the excitation energy level of the lowest triplet excited state (T1 state). In addition, in this specification, etc., although sometimes simply described as "singlet excited state" and "singlet excited energy level", sometimes they refer to the S1 state and S1 energy level, respectively. In addition, even when described as "triplet excited state" and "triplet excited energy level", sometimes they refer to the T1 state and T1 energy level, respectively.

[0041] In this specification, a fluorescent compound refers to a compound that emits light in the visible light region when returning from a singlet excited state to a ground state. A phosphorescent compound refers to a compound that emits light in the visible light region at room temperature when returning from a triplet excited state to a ground state. In other words, a phosphorescent compound is a compound that can convert triplet excitation energy into visible light.

[0042] Note that in this specification and the like, room temperature refers to a temperature within a range of 0° C. to 40° C. both inclusive.

[0043] In this specification, etc., the blue wavelength region refers to the wavelength region of 400 nm to less than 490 nm, and blue luminescence has at least one emission spectrum peak in this wavelength region. Furthermore, the green wavelength region refers to the wavelength region of 490 nm to less than 580 nm, and green luminescence has at least one emission spectrum peak in this wavelength region. Furthermore, the red wavelength region refers to the wavelength region of 580 nm to less than 680 nm, and red luminescence has at least one emission spectrum peak in this wavelength region.

[0044] (Implementation 1) In this embodiment, referring to Figures 1A to 1C 、 Figure 2A and Figure 2B 、 Figure 3 as well as Figure 4A and Figure 4B A light-emitting element according to one embodiment of the present invention will be described.

[0045] <Structural Example 1 of Light Emitting Element First, we will refer to Figures 1A to 1C The structure of a light-emitting element according to one embodiment of the present invention will be described.

[0046] Figure 1A 1 is a schematic cross-sectional view of a light-emitting element 150 according to one embodiment of the present invention.

[0047] The light-emitting element 150 includes a pair of electrodes (electrode 101 and electrode 102 ) and an EL layer 100 provided between the pair of electrodes. The EL layer 100 includes at least a light-emitting layer 130 .

[0048] in addition, Figure 1A The EL layer 100 shown includes functional layers such as a hole injection layer 111 , a hole transport layer 112 , an electron transport layer 118 , and an electron injection layer 119 in addition to the light-emitting layer 130 .

[0049] Note that although this embodiment describes a pair of electrodes in which electrode 101 serves as an anode and electrode 102 serves as a cathode, the structure of light-emitting element 150 is not limited to this. In other words, electrode 101 may serve as a cathode and electrode 102 as an anode, with the order of layers stacked between the electrodes reversed. In other words, the hole injection layer 111, hole transport layer 112, light-emitting layer 130, electron transport layer 118, and electron injection layer 119 may be stacked in this order from the anode side.

[0050] Note that the structure of the EL layer 100 is not limited to Figure 1AThe structure shown may include at least one selected from the group consisting of the hole injection layer 111, the hole transport layer 112, the electron transport layer 118, and the electron injection layer 119. Alternatively, the EL layer 100 may include a functional layer having the following functions: a functional layer capable of reducing the injection barrier for holes or electrons; a functional layer capable of improving the transportability of holes or electrons; a functional layer capable of inhibiting the transportability of holes or electrons; or a functional layer capable of suppressing quenching caused by electrodes. The functional layer may be a single layer or a stack of layers.

[0051] Next, the light emitting layer 130 will be described.

[0052] In one embodiment of the present invention, the light-emitting element 150 is a fluorescent light-emitting element containing a fluorescent compound in the light-emitting layer 130. Fluorescent light-emitting elements have high reliability and emit light with high color purity because their emission spectrum is sharper than that of phosphorescent light-emitting elements. The statistical probability of the generation ratio of singlet excitons to triplet excitons (hereinafter also referred to as the exciton generation probability) of an organic EL element is 1:3. This means that in a conventional fluorescent light-emitting element that emits light using singlet excitons, only 25% of the generated excitons contribute to luminescence. Therefore, in order to achieve high efficiency of fluorescent light-emitting elements, it is important to make triplet excitons contribute to luminescence.

[0053] In light of the above, the present inventors have discovered that triplet excitons can efficiently contribute to fluorescence. Specifically, by using an organic compound capable of converting triplet excitation energy into luminescence, an organic compound having a difference between singlet and triplet excitation energies of 0 eV to 0.2 eV, and an organic compound that exhibits fluorescence in the light-emitting layer, a highly efficient fluorescent element can be obtained. Furthermore, the organic compound having a difference between singlet and triplet excitation energies of 0 eV to 0.2 eV can also contain both a π-electron-rich skeleton and a π-electron-deficient skeleton within a single molecule.

[0054] As an organic compound having a difference of more than 0eV and less than 0.2eV between singlet excitation energy and triplet excitation energy, a thermally activated delayed fluorescence (TADF) material can be cited. Thermally activated delayed fluorescence material refers to a material in which the difference between S1 energy level and T1 energy level is small and has the function of converting triplet excitation energy into singlet excitation energy by anti-intersystem crossing. Therefore, triplet excitation energy can be up-converted (up-converted) into singlet excitation energy (anti-intersystem crossing) by tiny thermal energy and can efficiently produce a singlet excited state. The exciplex formed by two substances in an excited state has the function of converting triplet excitation energy into a thermally activated delayed fluorescence material of singlet excitation energy because the difference between S1 energy level and T1 energy level is extremely small.

[0055] Since organic compounds containing a π-electron-rich skeleton and a π-electron-deficient skeleton in one molecule have bipolarity and good carrier (electron and hole) transport properties, the use of this organic compound in a light-emitting element can improve the carrier balance and reduce the driving voltage. In addition, the organic compound sometimes has TADF properties. In this case, the π-electron-rich skeleton and the π-electron-deficient skeleton are preferably directly bonded. By adopting this structure, anti-intersystem crossing can be improved, so a TADF material with good luminous efficiency can be obtained.

[0056] TADF materials contain organic compounds with a π-electron-rich and π-electron-deficient backbone within a single molecule. As mentioned above, TADF materials have excellent carrier transport properties. Using TADF materials in light-emitting devices can improve carrier balance and reduce the driving voltage of light-emitting devices.

[0057] As the above-mentioned organic compound having the function of converting triplet excitation energy into luminescence, a compound capable of emitting phosphorescence (hereinafter referred to as a phosphorescent compound) can be cited. In this specification, etc., a phosphorescent compound refers to a compound that emits phosphorescence but does not emit fluorescence at a temperature range of a low temperature (for example, 77K) or above and below room temperature (that is, 77K or above and 313K or below). In order for the phosphorescent compound to efficiently convert triplet excitation energy into luminescence, it is preferred to contain heavy atoms. In addition, when the phosphorescent compound contains heavy atoms, due to the spin-orbit interaction (the interaction between the spin angular momentum of electrons and the orbital angular momentum), the transition between the singlet ground state and the triplet excited state is allowed. Thereby, the transition probability between the singlet ground state and the triplet excited state of the phosphorescent compound can be increased, thereby improving the luminescence efficiency and absorption probability associated with the transition. In addition, the transition from the triplet excitation energy level of the phosphorescent compound to the singlet excitation energy level of the fluorescent compound is based on the Forster equation. The energy transfer of the mechanism is allowed. In order to promote energy transfer, it is preferred that the phosphorescent compound include a metal element with a large spin-orbit interaction, specifically, a transition metal element. It is particularly preferred to include a platinum group element (ruthenium (Ru), rhodium (Rh), palladium (Pd), osmium (Os), iridium (Ir) or platinum (Pt)), and particularly preferably to include iridium, so that the probability of direct transition between the singlet ground state and the triplet excited state can be increased. In addition, as a material having the function of converting triplet excitation energy into luminescence, the above-mentioned TADF material can be cited.

[0058] Figure 1B It shows Figure 1A FIG. 1 is a schematic cross-sectional view of an example of the light-emitting layer 130 shown. Figure 1BThe light-emitting layer 130 shown includes compound 131, compound 132, and compound 133. In one embodiment of the present invention, compound 131 has the function of converting triplet excitation energy into luminescence. In addition, compound 132 is preferably a TADF material. Compound 133 is a guest material that emits fluorescence.

[0059] <Structural Example 1 of Light-Emitting Layer> Figure 1C An example of energy level correlation in a light-emitting layer of a light-emitting element according to one embodiment of the present invention is shown. In this structural example, Compound 131 is a phosphorescent compound.

[0060] in addition, Figure 1C The energy level correlation of Compound 131, Compound 132, and Compound 133 in the light-emitting layer 130 is shown. Figure 1C The marks and symbols in are as follows. Comp(131): Compound 131 Comp(132): Compound 132 ·Guest (133): Compound 133 ·T C1 : T1 energy level of compound 131 ·S C2 :S1 energy level of compound 132 ·T C2 :T1 energy level of compound 132 ·S G :S1 energy level of compound 133 ·T G :T1 energy level of compound 133

[0061] exist Figure 1C In the case where compound 131 or compound 132 receives holes and electrons, an excited state is formed. Since compound 131 is a phosphorescent compound, intersystem crossing between singlet and triplet states is allowed. Therefore, both the singlet excitation energy and the triplet excitation energy of compound 132 can be quickly transferred to compound 131 ( Figure 1C Here, S is preferred. C2 ≥T C1 And T C2 ≥T C1. In addition, the light-emitting layer 130 is formed by mixing compound 131, compound 132 and compound 133. Preferably, the proportion of compound 132 in the mixture is greater than the proportion of compound 131. Specifically, the weight ratio of compound 131 to compound 132 is preferably in the range of 1:9 to 3:7. By adopting this composition, compound 131 can be efficiently excited. In addition, since compound 131 is a phosphorescent compound, the triplet excitation energy of compound 131 can be efficiently converted into the singlet excitation energy of compound 133 ( Figure 1C Path A2 in ). Here, as Figure 1C As shown, when S C2 ≥T C1 ≥S G When T C2 ≥T C1 ≥S G At this time, triplet excitation energy is efficiently converted into singlet excitation energy and transferred to compound 133 which is a guest material, which is preferable.

[0062] In addition, from T C1 To T G The transferred triplet excitation energy is deactivated ( Figure 1C Pathway A3 in the reaction). Therefore, the amount of energy transferred via Pathway A3 is preferably small. In order to suppress energy transfer via Pathway A3, the weight ratio of Compound 133 relative to the total amount of Compound 131 and Compound 132 is preferably low. Specifically, the weight ratio of Compound 133 relative to Compound 131 and Compound 132 is preferably 0.001 to 0.05, more preferably 0.001 to 0.01.

[0063] Note that when the direct recombination process of carriers in compound 133 is dominant, multiple triplet excitons are generated in compound 133, and thermal deactivation leads to a decrease in luminous efficiency. Therefore, it is preferred that the proportion of the energy transfer process via path A2 is higher than the proportion of the direct recombination process of carriers in compound 133, at which time the probability of generating the triplet excited state of compound 133 can be reduced and thermal deactivation can be suppressed. For this reason, the weight ratio of compound 133 relative to the total amount of compound 131 and compound 132 is preferably low. Specifically, the weight ratio of compound 133 relative to compound 131 and compound 132 is preferably 0.001 or more and 0.05 or less, and more preferably 0.001 or more and 0.01 or less.

[0064] In the light-emitting element of one embodiment of the present invention, compound 132 has a function of exhibiting thermally activated delayed fluorescence (TADF property). In other words, compound 132 has a function of converting triplet excitation energy into singlet excitation energy by upconversion ( Figure 1C The singlet excitation energy of compound 132 can be rapidly transferred to compound 133 ( Figure 1C Path A5). At this time, it is preferably S C2 ≥S G .

[0065] Note that path A1 occurs even if the anti-intersystem crossing represented by path A4 does not occur. In other words, the energy transfer represented by path A1 occurs regardless of whether the anti-intersystem crossing represented by path A4 occurs.

[0066] As described above, in the light-emitting element of one embodiment of the present invention, there is a triplet excitation energy Figure 1C The paths A1 and A2 in the above diagram move to the path of compound 133 as the guest material and the triplet excitation energy passes through Figure 1C Path A4 and Path A5 in the example are transferred to the path of compound 133. The transfer of triplet excitation energy to the path of the fluorescent compound can improve the luminescence efficiency of the fluorescent light-emitting element. In addition, the transfer of triplet excitation energy to multiple paths of the fluorescent compound can further improve the luminescence efficiency.

[0067] By configuring the light-emitting layer 130 to have the above structure, light emission from the fluorescent compound in the light-emitting layer 130 can be efficiently obtained.

[0068] In addition, T G It is preferably 2.0 eV or less. By adopting this structure, a light-emitting element with high reliability can be obtained.

[0069] Since the phosphorescent compound in the above structure does not require a material with a high luminescence quantum yield, material design is easy and the range of material selection is wide. Specifically, the luminescence quantum yield of the compound at room temperature or normal temperature can be from 0% to 50%, from 0% to 40%, from 0% to 25%, from 0% to 10%, or from 0% to 1%. In addition, the compound preferably contains a heavy atom. Examples of such heavy atoms include Ru, Rh, Pd, Os, Ir, and Pt.

[0070] <Structural Example 2 of Light-Emitting Layer> Figure 2B An example of energy level correlation in the light-emitting layer 130 of the light-emitting element 150 according to one embodiment of the present invention is shown. In this structural example, the compound 131 is a phosphorescent compound, and the compound 131 and the compound 132 form an exciplex.

[0071] As a combination of compound 131 and compound 132, any combination that can form an exciplex is sufficient, preferably one of which is a compound having hole transport properties and the other is a compound having electron transport properties. In this case, a donor-acceptor type exciplex is easily formed, and an exciplex can be formed efficiently. In addition, when the combination of compound 131 and compound 132 is a combination of a compound having hole transport properties and a compound having electron transport properties, the balance of carriers can be easily controlled by adjusting their mixing ratio. Specifically, the weight ratio of the compound having hole transport properties to the compound having electron transport properties is preferably in the range of 1:9 to 9:1. In addition, due to the above composition, the balance of carriers can be easily controlled, thereby also easily controlling the carrier recombination region.

[0072] The formation of an exciplex can be confirmed, for example, by comparing the emission spectra of Compound 131, the emission spectra of Compound 132, and the emission spectra of a mixed film of Compound 131 and Compound 132, and observing that the emission spectrum of the mixed film shifts toward the longer wavelength side compared to the emission spectra of Compound 131 and Compound 132 (or has a new peak on the longer wavelength side); or by comparing the transient photoluminescence (PL) of Compound 131, the transient PL of Compound 132, and the transient PL of a mixed film of Compound 131 and Compound 132, and observing a difference in transient response (such as a phenomenon in which the transient PL lifetime of the mixed film has a greater long-life component or a greater ratio of delayed components than the transient PL lifetimes of Compound 131 and Compound 132). Alternatively, transition electroluminescence (EL) can be used instead of the above-mentioned transition PL. In other words, by comparing the transition EL of Compound 131, the transition EL of Compound 132, and the transition EL of a mixed film of Compound 131 and Compound 132, and observing the difference in the transient response, the formation of an exciplex can be confirmed.

[0073] In addition, as a combination of materials that efficiently form an exciplex, it is preferred that the HOMO (Highest Occupied Molecular Orbital, also known as the highest occupied molecular orbital) energy level of one of compound 131 and compound 132 is higher than the HOMO energy level of the other, and the LUMO (Lowest Unoccupied Molecular Orbital, also known as the lowest unoccupied molecular orbital) energy level of one of them is higher than the LUMO energy level of the other. Specifically, the energy difference between the HOMO energy level of compound 131 and the HOMO energy level of compound 132 is preferably 0.1eV or more, more preferably 0.2eV or more, and further preferably 0.3eV or more. In addition, the energy difference between the LUMO energy level of compound 131 and the LUMO energy level of compound 132 is preferably 0.1eV or more, more preferably 0.2eV or more, and further preferably 0.3eV or more. Through this energy level correlation, holes and electrons as carriers injected from a pair of electrodes (electrode 101 and electrode 102) are easily injected into compound 131 and compound 132, respectively, so it is preferred. In addition, the HOMO energy level of compound 131 may be equal to the HOMO energy level of compound 132, or the LUMO energy level of compound 131 may be equal to the LUMO energy level of compound 132.

[0074] Note that the LUMO energy level and the HOMO energy level of a compound can be determined from the electrochemical properties (reduction potential and oxidation potential) of the compound measured by cyclic voltammetry (CV).

[0075] For example, when compound 131 has hole transport properties and compound 132 has electron transport properties, as Figure 2A As shown in the energy band diagram, it is preferred that the HOMO energy level of compound 131 is higher than the HOMO energy level of compound 132, and the LUMO energy level of compound 131 is higher than the LUMO energy level of compound 132. This energy level correlation facilitates the injection of holes and electrons as carriers from a pair of electrodes (electrode 101 and electrode 102) into compound 131 and compound 132, respectively, which is preferred.

[0076] In addition, Figure 2A In the equation, Comp(131) represents compound 131, Comp(132) represents compound 132, and ΔE C1 represents the energy difference between the LUMO and HOMO levels of compound 131, ΔE C2 represents the energy difference between the LUMO and HOMO levels of compound 132, and ΔE E represents the energy difference between the LUMO level of compound 132 and the HOMO level of compound 131.

[0077] In addition, the exciplex formed by Compound 131 and Compound 132 has a HOMO in Compound 131 and a LUMO in Compound 132. In addition, the excitation energy of the exciplex is approximately equivalent to the energy difference (ΔE) between the LUMO energy level of Compound 132 and the HOMO energy level of Compound 131. E ), and is smaller than the energy difference between the LUMO and HOMO levels of compound 131 (ΔE C1 ) and the energy difference between the LUMO and HOMO levels of compound 132 (ΔE C2 ). Therefore, by forming an exciplex from Compound 131 and Compound 132, an excited state can be formed at a lower excitation energy. In addition, the exciplex can form a stable excited state due to its low excitation energy.

[0078] Figure 2B The energy level correlation of compound 131, compound 132 and compound 133 in the light-emitting layer 130 is shown as follows. Figure 2B The marks and symbols in Figure 1C The marks and symbols shown are the same. ·S C1 : S1 energy level of compound 131 ·S E : S1 energy level of the exciplex ·T E : T1 energy level of the exciplex

[0079] In the light-emitting element of one embodiment of the present invention of this structural example, the compound 131 and the compound 132 contained in the light-emitting layer 130 form an exciplex. The S1 energy level (S E ) and the T1 energy level of the exciplex (T E ) are adjacent to each other (refer to Figure 2B Path A6 in ).

[0080] When the exciplex formed through the above process loses its excitation energy and returns to the ground state by emitting light or supplying the excitation energy to other materials, the two substances forming the exciplex exist again as the original two substances.

[0081] The excited energy level of the exciplex (S E and T E ) than the S1 energy level (S C1 and S C2 ) is low, so an excited state can be formed with a lower excitation energy. As a result, the driving voltage of the light-emitting element 150 can be reduced.

[0082] Since the S1 energy level (S E ) and T1 energy level (T E ) are adjacent to each other, so the exciplex has the function of exhibiting thermally activated delayed fluorescence. That is, the exciplex has the function of converting triplet excitation energy into singlet excitation energy by up-conversion. Therefore, part of the triplet excitation energy generated in the light-emitting layer 130 is converted into singlet excitation energy by the exciplex. In order to cause up-conversion, the S1 energy level (S E ) and T1 energy level (T E ) is preferably greater than 0 eV and less than 0.2 eV, more preferably greater than 0 eV and less than 0.1 eV. Note that in order to efficiently cause antisystem crossing, the T1 level (T E ) is preferably lower than the T1 energy level (T C1 and T C2 ). As a result, quenching of the triplet excitation energy of the exciplex formed by Compound 131 and Compound 132 is less likely to occur, and antisystem crossing from the triplet excitation energy to the singlet excitation energy of the exciplex occurs efficiently.

[0083] In addition, the singlet excited energy level (S E ) is preferably higher than the singlet excitation energy level (S) of compound 133 as a light-emitting material. G Through this energy level correlation, the singlet excitation energy of the formed exciplex can be converted from the singlet excitation energy level (S E ) transfers to the singlet excited level (S G ).

[0084] Here, the energy level correlation between compound 131 and compound 132 is not limited to Figure 2B That is, the singlet excitation level (S C1 ) can be higher than the singlet excitation level (S C2 ) can also be lower than the singlet excitation level (S C2 In addition, the triplet excitation level (T C1 ) can be higher than the triplet excitation level (T C2 ) can also be lower than the triplet excitation level (T C2 ).

[0085] In addition, in one embodiment of the present invention, since a phosphorescent compound is used as one compound forming an exciplex, intersystem crossing between a singlet state and a triplet state is allowed. Thus, an exciplex capable of transitioning from a triplet excited state to a singlet ground state can be formed. In this case, the triplet excited energy level (T E ) is preferably higher than the singlet excitation energy level (S) of compound 133 as a light-emitting material. G Through this energy level correlation, the triplet excitation energy of the formed exciplex can be increased from the triplet excitation energy level (T E ) to the singlet excited level (S G ) transfer. Note that the S1 energy level (S E ) and T1 level (T E ) are adjacent to each other, making it difficult to clearly distinguish between fluorescence and phosphorescence in the emission spectrum. In this case, fluorescence and phosphorescence can sometimes be distinguished based on the emission lifetime.

[0086] After the above energy transfer process, compound 133 changes to a singlet excited state, thereby being able to emit light (refer to Figure 2B Path A7 in the diagram).

[0087] In addition, from T E To T G The transferred triplet excitation energy is deactivated ( Figure 2B Pathway A8 in the reaction). Therefore, the amount of energy transferred via Pathway A8 is preferably small. In order to suppress energy transfer via Pathway A8, the weight ratio of Compound 133 relative to the total amount of Compound 131 and Compound 132 is preferably low. Specifically, the weight ratio of Compound 133 relative to Compound 131 and Compound 132 is preferably 0.001 to 0.05, more preferably 0.001 to 0.01.

[0088] Note that when the direct recombination process of carriers in compound 133 is dominant, multiple triplet excitons are generated in compound 133, and thermal deactivation leads to a decrease in luminescence efficiency. Therefore, it is preferred that the energy transfer process ( Figure 2B The ratio of path A7 in the reaction mixture is higher than the ratio of the direct recombination process of carriers in compound 133. In this case, the probability of generating a triplet excited state of compound 133 can be reduced and thermal deactivation can be suppressed. To this end, as described above, the weight ratio of compound 133 relative to the total amount of compound 131 and compound 132 is preferably low. Specifically, the weight ratio of compound 133 relative to compound 131 and compound 132 is preferably 0.001 to 0.05, and more preferably 0.001 to 0.01.

[0089] In addition, T G It is preferably 2.0 eV or less. By adopting this structure, a light-emitting element with high reliability can be obtained.

[0090] Alternatively, a structure may be employed in which compound 131 has an electron-transporting property and compound 132 has a hole-transporting property. In this case, the HOMO level of compound 132 is preferably higher than that of compound 131, and the LUMO level of compound 132 is preferably higher than that of compound 131.

[0091] In addition, the weight ratio of Compound 131 relative to Compound 132 is preferably low. Specifically, the weight ratio of Compound 131 relative to Compound 132 is preferably 0.01 to 0.5, and more preferably 0.05 to 0.3.

[0092] As described above, when energy transfer via both paths A6 and A7 occurs efficiently, both singlet excitation energy and triplet excitation energy generated in the light-emitting layer 130 are efficiently converted into singlet excitation energy of the compound 133. Therefore, the light-emitting element 150 can emit light with high luminous efficiency.

[0093] In the light-emitting element of one embodiment of the present invention, Compound 132 preferably has a π-electron-deficient skeleton. Due to the above composition, the LUMO level of Compound 132 becomes low, which is suitable for the formation of an exciplex.

[0094] In the light-emitting element of one embodiment of the present invention, Compound 132 preferably has a π-electron-rich skeleton. Due to the above composition, the HOMO level of Compound 132 is increased, which is suitable for the formation of an exciplex.

[0095] In the light-emitting element of one embodiment of the present invention, compound 132 has a function of exhibiting thermally activated delayed fluorescence (TADF property). Therefore, in compound 132 without forming an exciplex, as shown in the structural example of the above-mentioned light-emitting layer, it has a function of converting triplet excitation energy into singlet excitation energy by upconversion ( Figure 2B The singlet excitation energy of compound 132 can be rapidly transferred to compound 133 ( Figure 2B Path A 10 ). In this case, preferably S C2 ≥S G .

[0096] As described above, in the light-emitting element of one embodiment of the present invention, there is a triplet excitation energy Figure 2B The paths A6 and A7 in the above diagram move to the path of compound 133 as the guest material and the triplet excitation energy passes through Figure 2B Path A9 and Path A in10 The pathway for triplet excitation energy to transfer to compound 133. As with the aforementioned structural example of the light-emitting layer, the pathway for triplet excitation energy to transfer to the fluorescent compound can improve the luminous efficiency of the fluorescent light-emitting element. Furthermore, the multiple pathways for triplet excitation energy to transfer to the fluorescent compound can further improve the luminous efficiency.

[0097] In this specification, the processes of Path A6 and Path A7 are sometimes referred to as ExSET (Exciplex-Singlet Energy Transfer) or ExEF (Exciplex-Enhanced Fluorescence). In other words, in the light-emitting layer 130, excitation energy is supplied from the exciplex to the fluorescent compound.

[0098] By making the light-emitting layer 130 have the above-described structure, light emission from the fluorescent compound can be obtained efficiently.

[0099] <Structural Example 3 of Light-Emitting Layer> Figure 3 An example of energy level correlation in the light-emitting layer of a light-emitting element according to one embodiment of the present invention is shown. In this structural example, compound 131 is a TADF material. C1 represents the S1 energy level of compound 131, Figure 3 The marks and symbols in Figure 1C The marks and symbols shown are the same.

[0100] exist Figure 3 In the case where compound 131 or compound 132 receives holes and electrons, an excited state is formed. In addition, the excitation energy of compound 132 can be quickly transferred to compound 131 ( Figure 3 Path A in 11 ). Here, S is preferred C2 ≥S C1 And T C2 ≥T C1 Here, compound 131 is a thermally activated delayed fluorescent material, so the triplet excitation energy of compound 131 is up-converted into singlet excitation energy at a temperature around room temperature ( Figure 3 Path A in 12 In addition, since the singlet excitation level (S C1 ) to the singlet excited level (S G ) for energy transfer ( Figure 3 Path A in 13 ), through path A 11 To Path A 13 The triplet excitation energy of compound 131 can be transferred to the singlet excitation energy level (SG ). Here, Figure 3 As shown, when T C2 ≥T C1 ≥S G When , both the singlet excitation energy and the triplet excitation energy are efficiently transferred from Compound 131 and Compound 132 to Compound 133 which is a guest material, so it is preferred.

[0101] In order to carry out the above up-conversion efficiently, the S1 energy level (S C2 ) and T1 energy level (T C2 ) is preferably greater than 0 eV and less than 0.2 eV, more preferably greater than 0 eV and less than 0.1 eV.

[0102] In addition, from T C1 To T G The transferred triplet excitation energy is deactivated ( Figure 3 Path A in 14 ). Therefore, it is preferred to go through route A 14 The amount of energy transferred is small. In order to suppress the 14 Energy transfer, preferably T C1 With T G Therefore, it is preferred that T G By adopting this structure, a light-emitting element with high luminous efficiency and high reliability can be obtained.

[0103] As shown in the above structural example of the light-emitting layer, since compound 132 is a TADF material, it has the function of converting triplet excitation energy into singlet excitation energy by upconversion ( Figure 3 Path A 15 The singlet excitation energy of compound 132 can be rapidly transferred to compound 133 ( Figure 3 Path A 16 ). In this case, preferably S C2 ≥S G .

[0104] As in the above-mentioned example of the structure of the light-emitting layer, in a light-emitting element according to one embodiment of the present invention, there is a triplet excitation energy passing through Figure 3 Path A in 11 To Path A 13 The path of the compound 133 that moves to the guest material and the triplet excitation energy through Figure 3 Path A in 15 and path A 16 The triplet excitation energy can be transferred to the fluorescent compound through a pathway that can improve the luminescence efficiency of the fluorescent light-emitting element. The triplet excitation energy can be transferred to multiple pathways of the fluorescent compound through a pathway that can further improve the luminescence efficiency.

[0105] Note that path A 11 Even if path A is not generated 15 In other words, the anti-intersystem crossing represented by path A 11 The energy movement represented by path A 15 The indicated reverse intersystem crossing will occur whether it occurs or not.

[0106] <Structural Example 4 of Light-Emitting Layer> Figure 4A The case where four materials are used for the light emitting layer 130 is shown. Figure 4A The light-emitting layer 130 in the embodiment includes compound 131, compound 132, compound 133, and compound 134. In one embodiment of the present invention, compound 131 has the function of converting triplet excitation energy into luminescence. In addition, compound 132 is preferably a TADF material. Compound 133 is a guest material that emits fluorescence. In addition, compound 134 is an organic compound that forms an exciplex with compound 132.

[0107] in addition, Figure 4B The energy level correlation of compound 131, compound 132, compound 133 and compound 134 in the light-emitting layer 130 is shown as follows. Figure 4B The marks and symbols in Figure 2B The marks and symbols shown are the same. ·S C3 :S1 energy level of compound 134 ·T C3 :T1 energy level of compound 134

[0108] In the light-emitting element of one embodiment of the present invention of this structural example, the compound 132 and the compound 134 contained in the light-emitting layer 130 form an exciplex. The S1 energy level (S E ) and the T1 energy level of the exciplex (T E ) are adjacent to each other (refer to Figure 4B Path A in 17 ).

[0109] As described above, when the exciplex formed through the above process loses its excitation energy, the two substances forming the exciplex exist again as the original two substances.

[0110] The excited energy level of the exciplex (S E and T E ) than the S1 energy level (S C2 and S C3) is low, so an excited state can be formed with a lower excitation energy. As a result, the driving voltage of the light-emitting element 150 can be reduced.

[0111] Here, since compound 131 is a phosphorescent compound, it allows intersystem crossing between singlet and triplet states. Therefore, both the singlet excitation energy and triplet excitation energy of the exciplex can be quickly transferred to compound 131 (path A). 18 ). Here, T is preferably E ≥T C1 In addition, since the triplet excitation energy of compound 131 can be efficiently converted into the singlet excitation energy of compound 133 (path A 19 ). Here, Figure 4B As shown, when T E ≥T C1 ≥S G When , the excitation energy of compound 131 is efficiently transferred as singlet excitation energy to compound 133 which is a guest material, so it is preferred.

[0112] At this time, as a combination of compound 132 and compound 134, any combination that can form an exciplex is sufficient, preferably one of which is a compound having hole transport properties and the other is a compound having electron transport properties. In this case, a donor-acceptor type exciplex is easily formed, and an exciplex can be formed efficiently. In addition, when the combination of compound 132 and compound 134 is a combination of a compound having hole transport properties and a compound having electron transport properties, the balance of carriers can be easily controlled by adjusting their mixing ratio. Specifically, the weight ratio of the compound having hole transport properties: the compound having electron transport properties is preferably in the range of 1:9 to 9:1. In addition, due to the above composition, the balance of carriers can be easily controlled, thereby also easily controlling the carrier recombination region.

[0113] In addition, as a combination of materials that efficiently form an exciplex, it is preferred that the HOMO energy level of one of compound 132 and compound 134 is higher than the HOMO energy level of the other, and the LUMO energy level of one is higher than the LUMO energy level of the other. Specifically, the energy difference between the HOMO energy level of compound 132 and the HOMO energy level of compound 134 is preferably 0.1 eV or more, more preferably 0.2 eV or more, and further preferably 0.3 eV or more. In addition, the energy difference between the LUMO energy level of compound 132 and the LUMO energy level of compound 134 is preferably 0.1 eV or more, more preferably 0.2 eV or more, and further preferably 0.3 eV or more. Through this energy level correlation, holes and electrons injected as carriers from a pair of electrodes (electrode 101 and electrode 102) are easily injected into compound 132 and compound 134, respectively, so it is preferred. In addition, the HOMO energy level of compound 132 may be equal to the HOMO energy level of compound 134, or the LUMO energy level of compound 132 may be equal to the LUMO energy level of compound 134.

[0114] In addition, the energy level correlation between compound 132 and compound 134 is not limited to Figure 4B That is, the singlet excitation level (S C2 ) can be higher than the singlet excitation level (S C3 ) can also be lower than the singlet excitation level (S C3 In addition, the triplet excitation level (T C2 ) can be higher than the triplet excitation level (T C3 ) can also be lower than the triplet excitation level (T C3 ).

[0115] In the light-emitting element of one embodiment of the present invention, Compound 132 preferably has a π-electron-deficient skeleton. Due to the above composition, the LUMO level of Compound 132 becomes low, which is suitable for the formation of an exciplex.

[0116] In the light-emitting element of one embodiment of the present invention, Compound 132 preferably has a π-electron-rich skeleton. Due to the above composition, the HOMO level of Compound 132 is increased, which is suitable for the formation of an exciplex.

[0117] As shown in the above-mentioned structural example of the light-emitting layer, since compound 132 is a TADF material, compound 132 which does not form an exciplex has the function of converting triplet excitation energy into singlet excitation energy by upconversion ( Figure 4B Path A 21 The singlet excitation energy of compound 132 can be rapidly transferred to compound 133 ( Figure 4B Path A 22 ). In this case, preferably S C2 ≥S G .

[0118] As in the above-mentioned example of the structure of the light-emitting layer, in a light-emitting element according to one embodiment of the present invention, there is a triplet excitation energy passing through Figure 4B Path A in 17 To Path A 19 The path of the compound 133 that moves to the guest material and the triplet excitation energy through Figure 4B Path A in 21 and path A 22 The triplet excitation energy can be transferred to the fluorescent compound through a pathway that can improve the luminescence efficiency of the fluorescent light-emitting element. The triplet excitation energy can be transferred to multiple pathways of the fluorescent compound through a pathway that can further improve the luminescence efficiency.

[0119] In addition, from T C1 To T G The transferred triplet excitation energy is deactivated ( Figure 4B Path A in 20 ). Therefore, it is preferred to go through route A 20 The amount of energy transferred is small. In order to suppress the 20 energy transfer, preferably, the weight ratio of compound 133 relative to the total amount of compound 131, compound 132 and compound 134 is low. Specifically, the weight ratio of compound 133 relative to the total amount of compound 131, compound 132 and compound 134 is preferably greater than 0.001 and less than 0.05, and more preferably greater than 0.001 and less than 0.01.

[0120] In addition, T G It is preferably 2.0 eV or less. By adopting this structure, a light-emitting element with high reliability can be obtained.

[0121] <Energy transfer mechanism> The factors controlling the intermolecular energy transfer process are described below. Two proposed mechanisms for intermolecular energy transfer are the Förster mechanism (dipole-dipole interaction) and the Dexter mechanism (electron exchange interaction). Note that while this description focuses on the intermolecular energy transfer process between a first material and a second material, involving the transfer of excitation energy from the first material in an excited state to the second material in a ground state, the same principle applies when one of the materials is an exciplex.

[0122] Foster Mechanism In the Förster mechanism, energy transfer does not require direct contact between molecules. Instead, energy transfer occurs through the resonance phenomenon of dipole oscillations between the first and second materials. Through the resonance phenomenon of dipole oscillations, the first material supplies energy to the second material, and the excited state of the first material becomes the ground state, and the ground state of the second material becomes the excited state. In addition, the rate constant k of the Förster mechanism is expressed by equation (1): h*→g .

[0123] [Formula 1]

[0124] In formula (1), ν represents the oscillation number, f' h (ν) represents the normalized emission spectrum of the first material (fluorescence spectrum when discussing energy transfer from a singlet excited state, phosphorescence spectrum when discussing energy transfer from a triplet excited state), ε g (ν) represents the molar absorptivity of the second material, N represents Avogadro's number, n represents the refractive index of the medium, R represents the molecular distance between the first material and the second material, τ represents the lifetime of the excited state being measured (fluorescence lifetime or phosphorescence lifetime), c represents the speed of light, φ represents the luminescence quantum yield (fluorescence quantum yield when discussing energy transfer from a singlet excited state, phosphorescence quantum yield when discussing energy transfer from a triplet excited state), K 2 A coefficient (0 to 4) representing the orientation of the transition dipole moment of the first material and the second material. In addition, in random orientation, K 2 =2 / 3.

[0125] Dexter Mechanism In the Dexter mechanism, the first material and the second material are close to the contact effective distance that causes orbital overlap, and energy transfer occurs by exchanging electrons in the first material in an excited state with electrons in the second material in a ground state. In addition, the rate constant k of the Dexter mechanism is shown in formula (2): h*→g .

[0126] [Formula 2]

[0127] In formula (2), h represents Planck's constant, K represents a constant with energy dimension, ν represents the oscillation number, and f' h (ν) represents the normalized emission spectrum of the first material (fluorescence spectrum when discussing energy transfer from a singlet excited state, phosphorescence spectrum when discussing energy transfer from a triplet excited state), ε' g (ν) represents the normalized absorption spectrum of the second material, L represents the effective molecular radius, and R represents the molecular distance between the first material and the second material.

[0128] Here, the energy transfer efficiency from the first material to the second material (energy transfer efficiency φ ET ) is expressed as formula (3). In the formula, k r k represents the rate constant of the light emission process of the first material (fluorescence when discussing energy transfer from a singlet excited state, phosphorescence when discussing energy transfer from a triplet excited state) n represents the rate constant of the non-luminescent process (thermal deactivation or intersystem crossing) of the second material, and τ represents the measured lifetime of the excited state of the first material.

[0129] [Formula 3]

[0130] From equation (3), we can see that by increasing the rate constant k of energy transfer h*→g , which can improve the energy transfer efficiency φ ET , thus making the other competition rate constant k r +k n (=1 / τ) becomes relatively small.

[0131] Concepts used to facilitate energy transfer First, consider the energy transfer based on the Förster mechanism. By substituting equation (1) into equation (3), τ can be eliminated. Therefore, in the Förster mechanism, the energy transfer efficiency φ ET It does not depend on the lifetime τ of the excited state of the first material. In addition, when the luminescence quantum yield φ (fluorescence quantum yield when discussing energy transfer from a singlet excited state, phosphorescence quantum yield when discussing energy transfer from a triplet excited state) is high, it can be said that the energy transfer efficiency φ ET Higher.

[0132] In addition, the overlap between the emission spectrum of the first material (the fluorescence spectrum when discussing energy transfer from the singlet excited state, and the phosphorescence spectrum when discussing energy transfer from the triplet excited state) and the absorption spectrum of the second material (equivalent to the absorption of the transition from the singlet ground state to the singlet excited state) is preferably large. Furthermore, the molar absorptivity of the second material is preferably high. This means that the emission spectrum of the first material overlaps with the absorption band on the longest wavelength side of the second material. Note that since the direct transition from the singlet ground state to the triplet excited state in the second material is prohibited, the molar absorptivity in the triplet excited state in the second material can be ignored. Thus, the energy transfer process from the excited state of the first material to the triplet excited state of the second material based on the Förster mechanism can be ignored, and only the energy transfer process to the singlet excited state of the second material needs to be considered.

[0133] Next, consider the energy transfer based on the Dexter mechanism. From equation (2), we can see that in order to increase the rate constant k h*→gThe overlap between the emission spectrum of the first material (the fluorescence spectrum when discussing energy transfer from a singlet excited state, and the phosphorescence spectrum when discussing energy transfer from a triplet excited state) and the absorption spectrum of the second material (equivalent to the absorption corresponding to the transition from the singlet ground state to the singlet excited state) is preferably large. Therefore, by aligning the emission spectrum of the first material with the longest-wavelength absorption band of the second material, energy transfer efficiency can be optimized.

[0134] In addition, when equation (2) is substituted into equation (3), it can be seen that the energy transfer efficiency φ in the Dexter mechanism is ET Since the Dexter mechanism is an energy transfer process based on electron exchange, energy transfer from the triplet excited state of the first material to the triplet excited state of the second material also occurs, similarly to energy transfer from the singlet excited state of the first material to the singlet excited state of the second material.

[0135] Similar to the energy transfer from the first material to the second material, the energy transfer from the exciplex to the fluorescent compound may also occur based on both the Förster mechanism and the Dexter mechanism.

[0136] In the light-emitting element according to one embodiment of the present invention, the second material is a fluorescent compound, so the energy transfer efficiency to the triplet excited state of the second material is preferably low. In other words, the energy transfer efficiency from the first material to the second material based on the Dexter mechanism is preferably low, while the energy transfer efficiency from the first material to the second material based on the Förster mechanism is preferably high.

[0137] As described above, the energy transfer efficiency based on the Förster mechanism does not depend on the lifetime τ of the excited state of the first material. On the other hand, the energy transfer efficiency based on the Dexter mechanism depends on the excitation lifetime τ of the first material. To reduce the energy transfer efficiency based on the Dexter mechanism, the excitation lifetime τ of the first material is preferably short.

[0138] Thus, in one embodiment of the present invention, an exciplex or a TADF material is used as the first material, and a compound forming the exciplex has the function of converting triplet excitation energy into luminescence. Through the structure of one embodiment of the present invention, the antisystem crossing from the triplet excited state to the singlet excited state of the exciplex (first material) can be promoted, and the excitation lifetime τ of the triplet excited state of the exciplex (first material) can be shortened. In addition, the transition from the triplet excited state to the singlet ground state of the exciplex (first material) can be promoted, and the excitation lifetime τ of the triplet excited state of the exciplex (first material) can be shortened. As a result, the energy transfer efficiency based on the Dexter mechanism from the triplet excited state of the exciplex (first material) to the triplet excited state of the fluorescent compound (second material) can be reduced, and therefore one embodiment of the present invention can provide a light-emitting element with high luminous efficiency.

[0139] Furthermore, in the light emitted by the exciplex, the fluorescence lifetime of the thermally activated delayed fluorescence component is preferably short, specifically preferably 10 ns to 50 μs, more preferably 10 ns to 20 μs, and even more preferably 10 ns to 10 μs.

[0140] In addition, the rate constant of the Förster mechanism is inversely proportional to the sixth power of the distance between the first material and the second material, and the rate constant of the Dexter mechanism is inversely proportional to the exponential function of the distance between the first material and the second material. Therefore, when the distance between the two molecules is approximately 1 nm or less, the Dexter mechanism prevails, and when the distance between the two molecules is approximately 1 nm or more, the Förster mechanism prevails. Therefore, in order to reduce the efficiency of energy transfer based on the Dexter mechanism, it is preferred to increase the distance between the first material and the second material. Specifically, the distance is preferably 0.7 nm or more, more preferably 0.9 nm or more, and even more preferably 1 nm or more. In addition, in order to efficiently transfer energy using the Förster mechanism, the distance between the first material and the second material is preferably 5 nm or less.

[0141] Therefore, in one embodiment of the present invention, compound 133 as a fluorescent compound preferably includes at least two alkyl groups having 2 or more carbon atoms. Alternatively, compound 133 preferably includes at least two branched alkyl groups having 3 or more and 10 or less carbon atoms. Alternatively, compound 133 preferably includes at least two cyclic hydrocarbon groups having 3 or more and 10 or less carbon atoms or at least two bridged cyclic hydrocarbon groups having 3 or more and 10 or less carbon atoms. In addition, compound 133 preferably includes a fused aromatic hydrocarbon having 3 or more and 12 or less carbon atoms.

[0142] <Materials> Next, components of a light-emitting element according to one embodiment of the present invention will be described.

[0143] Luminous Layer Next, materials that can be used for the light-emitting layer 130 will be described.

[0144] Examples of the compound 132 include TADF materials. Preferably, the energy difference between the S1 level and the T1 level of the compound 132 is small, specifically, greater than 0 eV and not more than 0.2 eV.

[0145] Compound 132 preferably includes a skeleton having hole transport properties and a skeleton having electron transport properties. Alternatively, compound 132 preferably has a π-rich electron skeleton or an aromatic amine skeleton and has a π-deficient electron skeleton. It is thus easy to form a donor-acceptor type excited state in the molecule. Furthermore, it is preferred that a structure in which a skeleton having electron transport properties is directly bonded to a skeleton having hole transport properties is included in a manner that simultaneously enhances the donor and acceptor properties in the molecule of compound 132. Alternatively, it is preferred that a structure in which a π-rich electron skeleton or an aromatic amine skeleton is directly bonded to a π-deficient electron skeleton is included. By simultaneously enhancing the donor and acceptor properties in the molecule, the region where the molecular orbital distribution of HOMO overlaps with the region where the molecular orbital distribution of LUMO overlaps can be reduced in compound 132, and the energy difference between the singlet excitation energy level and the triplet excitation energy level of compound 132 can be reduced. In addition, the triplet excitation energy level of compound 132 can be kept high.

[0146] When the thermally activated delayed fluorescent material is composed of one material, for example, the following materials can be used.

[0147] First, there are fullerenes or their derivatives, acridine derivatives such as proflavine, eosin, etc. In addition, there are metal-containing porphyrins containing magnesium (Mg), zinc (Zn), cadmium (Cd), tin (Sn), platinum (Pt), indium (In), or palladium (Pd). Examples of the metal-containing porphyrin include protoporphyrin-tin fluoride complex (SnF2(Proto IX)), mesoporphyrin-tin fluoride complex (SnF2(Meso IX)), hematoporphyrin-tin fluoride complex (SnF2(Hemato IX)), coproporphyrin tetramethyl ester-tin fluoride complex (SnF2(Copro III-4Me)), octaethylporphyrin-tin fluoride complex (SnF2(OEP)), protoporphyrin-tin fluoride complex (SnF2(Etio I)), octaethylporphyrin-platinum chloride complex (PtCl2OEP), and the like.

[0148]

[0149] In addition, as a thermally activated delayed fluorescent material composed of a single material, heterocyclic compounds having a π-electron-rich skeleton and a π-electron-deficient skeleton can also be used. Specifically, 2-(biphenyl-4-yl)-4,6-bis(12-phenylindolo[2,3-a]carbazole-11-yl)-1,3,5-triazine (abbreviated as: PIC-TRZ), 2-{4-[3-(N-phenyl-9H-carbazole-3-yl)-9H-carbazole-9-yl]phenyl}-4,6-diphenyl-1,3,5-triazine (abbreviated as: PCCzPTzn), 2 -[4-(10H-phenoxazin-10-yl)phenyl]-4,6-diphenyl-1,3,5-triazine (abbreviated as PXZ-TRZ), 3-[4-(5-phenyl-5,10-dihydrophenazin-10-yl)phenyl]-4,5-diphenyl-1,2,4-triazole (abbreviated as PPZ-3TPT), 3-(9,9-dimethyl-9H-acridin-10-yl)-9H-xanthene-9 -ketone (abbreviated as ACRXTN), bis[4-(9,9-dimethyl-9,10-dihydroacridine)phenyl]sulfone (abbreviated as DMAC-DPS), 10-phenyl-10H,10'H-spiro[acridine-9,9'-anthracenes]-10'-one (abbreviated as ACRSA), 4-(9'-phenyl-3,3'-bi-9H-carbazol-9-yl)benzofurano[3,2-d]pyrimidine (abbreviated as :4PCCzBfpm), 4-[4-(9'-phenyl-3,3'-bi-9H-carbazole-9-yl)phenyl]benzofurano[3,2-d]pyrimidine (abbreviated as: 4PCCzPBfpm), 9-[3-(4,6-diphenyl-1,3,5-triazine-2-yl)phenyl]-9'-phenyl-2,3'-bi-9H-carbazole (abbreviated as: mPCCzPTzn-02), etc. This heterocyclic compound has a π-electron-rich skeleton and a π-electron-deficient skeleton, so the electron transport property and the hole transport property are high, so it is preferred. In particular, among those with a π-electron-deficient skeleton, the pyridine skeleton, the diazine skeleton (pyrimidine skeleton, pyrazine skeleton, pyridazine skeleton) and the triazine skeleton are stable and have good reliability, so they are preferred. In particular, the benzofuranopyrimidine skeleton, the benzothienopyrimidine skeleton, the benzofuranopyrazine skeleton, and the benzothienopyrazine skeleton have high acceptor properties and good reliability, so they are preferred. In addition, among the π-electron-rich skeletons, the acridine skeleton, the phenoxazine skeleton, the phenothiazine skeleton, the furan skeleton, the thiophene skeleton, and the pyrrole skeleton are stable and have good reliability, so it is preferred to have at least one of the above skeletons. In addition, as the furan skeleton, a dibenzofuran skeleton is preferably used, and as the thiophene skeleton, a dibenzothiophene skeleton is preferably used. As the pyrrole skeleton, an indole skeleton, a carbazole skeleton, a bicarbazole skeleton, and a 3-(9-phenyl-9H-carbazole-3-yl)-9H-carbazole skeleton are particularly preferably used.Furthermore, materials in which a π-electron-rich skeleton and a π-electron-deficient skeleton are directly bonded are particularly preferred because both the donor properties of the π-electron-rich skeleton and the acceptor properties of the π-electron-deficient skeleton are strong, minimizing the energy difference between the singlet excited state and the triplet excited state. Alternatively, an aromatic ring bonded with an electron-withdrawing group such as a cyano group can be used as the π-electron-deficient skeleton.

[0150]

[0151] Next, as described above, compound 131 preferably has a function of converting triplet excitation energy into luminescence. Examples of organic compounds having this function include phosphorescent materials and thermally activated delayed fluorescent materials.

[0152] Examples of the phosphorescent compound include iridium, rhodium, and platinum-type organometallic complexes or metal complexes. Furthermore, platinum complexes or organic iridium complexes with porphyrin ligands may be used. In particular, organic iridium complexes such as ortho-metal complexes of the iridium type are preferably used. Examples of ortho-metallated ligands include 4H-triazole ligands, 1H-triazole ligands, imidazole ligands, pyridine ligands, pyrimidine ligands, pyrazine ligands, and isoquinoline ligands. Compound 131 (phosphorescent compound) exhibits a triple MLCT (metal to ligand charge transfer) absorption band.

[0153] Examples of substances having a light emission peak in the blue or green wavelength region include tris{2-[5-(2-methylphenyl)-4-(2,6-dimethylphenyl)-4H-1,2,4-triazol-3-yl-κN 2]phenyl-κC}iridium(III) (abbreviated as: Ir(mpptz-dmp)3), tris(5-methyl-3,4-diphenyl-4H-1,2,4-triazole)iridium(III) (abbreviated as: Ir(Mptz)3), tris[4-(3-biphenyl)-5-isopropyl-3-phenyl-4H-1,2,4-triazole]iridium(III) (abbreviated as: Ir(iPrptz-3b)3), tris[3-(5-biphenyl)-5-isopropyl-4-phenyl-4H-1,2,4-triazole]iridium(III) (abbreviated as: Ir(iPr5btz)3); tris[3-methyl-1-(2-methylphenyl)-5-phenyl-1H-1,2,4-triazole]iridium(III) (abbreviated as: Organometallic iridium complexes with a 1H-triazole skeleton, such as Ir(Mptz1-mp)3), tris(1-methyl-5-phenyl-3-propyl-1H-1,2,4-triazole)iridium(III) (abbreviated as Ir(Prptz1-Me)3); organometallic iridium complexes with an imidazole skeleton, such as fac-tris[1-(2,6-diisopropylphenyl)-2-phenyl-1H-imidazole]iridium(III) (abbreviated as Ir(iPrpmi)3), tris[3-(2,6-dimethylphenyl)-7-methylimidazo[1,2-f]phenanthridinato]iridium(III) (abbreviated as Ir(dmpimpt-Me)3); and bis[2-(4',6'-difluorophenyl)pyridinium-N,C 2 '] iridium (III) tetrakis (1-pyrazolyl) borate (abbreviated as: FIr6), bis [2- (4', 6'-difluorophenyl) pyridinium-N, C 2 '] iridium (III) picolinate (abbreviated as: FIrpic), bis{2-[3',5'-bis(trifluoromethyl)phenyl]pyridinium-N,C 2 '}Iridium(III) picolinate (abbreviated as: Ir(CF3ppy)2(pic)), bis[2-(4',6'-difluorophenyl)pyridinium-N,C 2 Organometallic iridium complexes with phenylpyridine derivatives having electron-withdrawing groups as ligands, such as iridium (III) acetylacetonate (FIr(acac)). Among these materials, organometallic iridium complexes with nitrogen-containing five-membered heterocyclic skeletons, such as 4H-triazole, 1H-triazole, and imidazole, are particularly preferred due to their high triplet excitation energy, high reliability, and high luminous efficiency.

[0154] Examples of substances having a light emission peak in the green or yellow wavelength region include tris(4-methyl-6-phenylpyrimidinyl)iridium(III) (abbreviated as Ir(mppm)3), tris(4-tert-butyl-6-phenylpyrimidinyl)iridium(III) (abbreviated as Ir(tBuppm)3), (acetylacetonate)bis(6-methyl-4-phenylpyrimidinyl)iridium(III) (abbreviated as Ir(mppm)2(acac)), (acetylacetonate)bis(6-tert-butyl-4-phenylpyrimidinyl)iridium(III) (abbreviated as Ir(mppm)2(acac)), and tris(4-tert-butyl-6-phenylpyrimidinyl)iridium(III) (abbreviated as Ir(tBuppm)3). Abbreviations: Ir(tBuppm)2(acac)), (acetylacetonate)bis[4-(2-norbornyl)-6-phenylpyrimidinyl]iridium(III) (Abbreviation: Ir(nbppm)2(acac)), (acetylacetonate)bis[5-methyl-6-(2-methylphenyl)-4-phenylpyrimidinyl]iridium(III) (Abbreviation: Ir(mpmppm)2(acac)), (acetylacetonate)bis{4,6-dimethyl-2-[6-(2,6-dimethylphenyl)-4-pyrimidinyl-κN 3 ]phenyl-κC}iridium(III) (abbreviated as: Ir(dmppm-dmp)2(acac)), (acetylacetonate)bis(4,6-diphenylpyrimidine)iridium(III) (abbreviated as: Ir(dppm)2(acac)), etc., which have a pyrimidine skeleton; (acetylacetonate)bis(3,5-dimethyl-2-phenylpyrazine)iridium(III) (abbreviated as: Ir(mppr-Me)2(acac)), (acetylacetonate)bis(5-isopropyl-3-methyl-2-phenylpyrazine)iridium(III) (abbreviated as: Ir(mppr-iPr)2(acac)), etc., which have a pyrazine skeleton; tris(2-phenylpyridinium-N,C 2 ') Iridium (III) (abbreviated as: Ir(ppy)3), bis(2-phenylpyridinium-N,C 2 ') Iridium(III) acetylacetonate (abbreviated as Ir(ppy)2(acac)), bis(benzo[h]quinolinolato)iridium(III) acetylacetonate (abbreviated as Ir(bzq)2(acac)), tris(benzo[h]quinolinolato)iridium(III) (abbreviated as Ir(bzq)3), tris(2-phenylquinolinolato-N,C 2′ )iridium(III) (abbreviated as: Ir(pq)3), bis(2-phenylquinoline-N,C 2 ') Iridium (III) acetylacetonate (abbreviated as: Ir (pq) 2 (acac)) and other organometallic iridium complexes with a pyridine skeleton; bis (2, 4-diphenyl-1, 3-oxazole-N, C 2 ') iridium (III) acetylacetonate (abbreviated as: Ir(dpo)2(acac)), bis{2-[4'-(perfluorophenyl)phenyl]pyridine-N, C 2'}Iridium (III) acetylacetonate (abbreviated as: Ir(p-PF-ph)2(acac)), bis(2-phenylbenzothiazole-N, C 2 Organometallic iridium complexes such as iridium(III) acetylacetonate (abbreviated as Ir(bt)2(acac)); and rare earth metal complexes such as terbium(III) tris(acetylacetonate)(monophenanthroline) (abbreviated as Tb(acac)3(Phen)). Among these materials, organometallic iridium complexes with a pyrimidine skeleton are particularly preferred due to their exceptionally high reliability and luminous efficiency.

[0155] In addition, examples of substances having a light emission peak in the yellow or red wavelength region include (diisobutyrylmethane)bis[4,6-bis(3-methylphenyl)pyrimidinyl]iridium(III) (abbreviation: Ir(5mdppm)2(dibm)), bis[4,6-bis(3-methylphenyl)pyrimidinyl](dipivaloylmethane)iridium(III) (abbreviation: Ir(5mdppm)2(dpm)), bis[4,6-di(naphthalene-1-yl)pyrimidinyl](dipivaloylmethane)iridium(III) (abbreviation: Ir(d1npm)2(dpm) ) and other organometallic iridium complexes with a pyrimidine skeleton; (acetylacetonato)bis(2,3,5-triphenylpyrazinato)iridium(III) (abbreviated as: Ir(tppr)2(acac)), bis(2,3,5-triphenylpyrazinato)(dipivaloylmethane)iridium(III) (abbreviated as: Ir(tppr)2(dpm)), (acetylacetonato)bis[2,3-bis(4-fluorophenyl)quinoxaline]iridium(III) (abbreviated as: Ir(Fdpq)2(acac)) and other organometallic iridium complexes with a pyrazine skeleton; tris(1-phenylisoquinoline-N,C 2’ ) iridium (III) (abbreviated as: Ir(piq)3), bis(1-phenylisoquinoline-N, C 2’ ) iridium(III) acetylacetonate (abbreviated as Ir(piq)2(acac)) and other organometallic iridium complexes with a pyridine skeleton; platinum complexes such as 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphyrin platinum(II) (abbreviated as PtOEP); and rare earth metal complexes such as tris(1,3-diphenyl-1,3-propanedione)(monophenanthroline)europium(III) (abbreviated as Eu(DBM)3(Phen)) and tris[1-(2-thenoyl)-3,3,3-trifluoroacetone](monophenanthroline)europium(III) (abbreviated as Eu(TTA)3(Phen)). Of the above, organometallic iridium complexes with a pyrimidine skeleton are particularly preferred because they also have very high reliability and luminous efficiency. In addition, organometallic iridium complexes with a pyrazine skeleton can produce red luminescence with good chromaticity.

[0156] In addition, as materials that can be used for compound 131, the thermally activated delayed fluorescent materials mentioned above can be cited.

[0157] In addition, a fluorescent compound is preferably used as the compound 133 in the light-emitting layer 130. The fluorescent compound is not particularly limited, but anthracene derivatives, tetracene derivatives, chrysene derivatives, phenanthrene derivatives, pyrene derivatives, perylene derivatives, stilbene derivatives, acridone derivatives, coumarin derivatives, phenoxazine derivatives, phenothiazine derivatives, and the like.

[0158] Specifically, examples of the material include 5,6-bis[4-(10-phenyl-9-anthracenyl)phenyl]-2,2'-bipyridine (abbreviated as PAP2BPy), 5,6-bis[4'-(10-phenyl-9-anthracenyl)biphenyl-4-yl]-2,2'-bipyridine (abbreviated as PAPP2BPy), N,N'-diphenyl-N,N'-bis[4-(9-phenyl-9H-fluoren-9-yl)phenyl]pyrene-1,6-diamine (abbreviated as 1,6FLPAPrn), N,N'-bis(3-methylphenyl)-N,N'-bis[3-(9-phenyl-9H-fluoren-9-yl)phenyl]pyrene- 1,6-diamine (abbreviated as: 1,6mMemFLPAPrn), N,N'-bis[4-(9-phenyl-9H-fluoren-9-yl)phenyl]-N,N'-bis(4-tert-butylphenyl)pyrene-1,6-diamine (abbreviated as: 1,6tBu-FLPAPrn), N,N'-diphenyl-N,N'-bis[4-(9-phenyl-9H-fluoren-9-yl)phenyl]-3,8-dicyclohexylpyrene-1,6-diamine (abbreviated as: ch-1,6FLPAPrn), N,N'-bis[4-(9H-carbazol-9-yl)phenyl]-N,N'-diphenylstilbene-4,4'-diamine (abbreviated as: YGA2S), 4-(9H-carbazol-9-yl)-4'-(10-phenyl-9-anthracenyl)triphenylamine (abbreviated as: YGAPA), 4-(9H-carbazol-9-yl)-4'-(9,10-diphenyl-2-anthracenyl)triphenylamine (abbreviated as: 2YGAPPA), N,9-diphenyl-N-[4-(10-phenyl-9-anthracenyl)phenyl]-9H-carbazol-3-amine (abbreviated as: PCAPA), perylene, 2,5,8,11-tetra(tert-butyl)perylene (abbreviated as: TBP), 4-(10-phenyl-9-anthracenyl)-4'-(9-phenyl-9H-carbazol-3-yl)triphenylamine (abbreviated as: P CBAPA), N,N"-(2-tert-butylanthracene-9,10-diyldi-4,1-phenylene)bis[N,N',N'-triphenyl-1,4-phenylenediamine] (abbreviated as DPABPA), N,9-diphenyl-N-[4-(9,10-diphenyl-2-anthryl)phenyl]-9H-carbazole-3-amine (abbreviated as 2PCAPPA), N-[4-(9,10-diphenyl-2-anthryl)phenyl]-N,N',N'-triphenyl-1,4-phenylenediamine (abbreviated as 2DPAPPA), N,N,N',N',N",N",N"',N"'-octaphenyldibenzo[g,p] (chrysene)-2,7,10,15-tetramine (abbreviated as DBC1), coumarin 30, N-(9,10-diphenyl-2-anthracenyl)-N,9-diphenyl-9H-carbazole-3-amine (abbreviated as 2PCAPA), N-[9,10-bis(1,1'-biphenyl-2-yl)-2-anthracenyl]-N,9-diphenyl-9H-carbazole-3-amine (abbreviated as 2PCABPhA), N-(9,10-diphenyl-2-anthracenyl)-N,N',N'-triphenyl-1,4-phenylenediamine (abbreviated as 2DPAPA), N-[9,10-bis(1,1'-biphenyl-2-yl)-2-anthracenyl]-N,N',N'-triphenyl-1,4-phenylenediamine (abbreviated as 2DPAPA), N-[9,10-bis(1,1'-biphenyl-2-yl)-2-anthracenyl]-N,N',N'-triphenyl-1,4-phenylenediamine Abbreviation: 2DPABPhA), 9,10-bis(1,1'-biphenyl-2-yl)-N-[4-(9H-carbazol-9-yl)phenyl]-N-phenylanthracen-2-amine (Abbreviation: 2YGABPhA), N,N,9-triphenylanthracen-9-amine (Abbreviation: DPhAPhA), Coumarin 6, Coumarin 545T, N,N'-diphenylquinacridone (Abbreviation: DPQd), rubrene, 2,8-di-tert-butyl-5,11-bis(4-tert-butylphenyl)-6,12-diphenyltetracene (Abbreviation: TBRb), Nile Red, 5,12-bis(1,1'-biphenyl-4-yl)-6,11-diphenyltetracene (Abbreviation: BPT), 2-(2-{2-[4-(dimethylamino)phenyl]-1,2-diphenyltetracene] [amino)phenyl]vinyl]-6-methyl-4H-pyran-4-ylidene)malononitrile (abbreviated as DCM1), 2-{2-methyl-6-[2-(2,3,6,7-tetrahydro-1H,5H-benzo[ij]quinolizin-9-yl)vinyl]-4H-pyran-4-ylidene}malononitrile (abbreviated as DCM2), N,N,N',N'-tetrakis(4-methylphenyl)tetracene-5,11-diamine (abbreviated as p-mPhTD), 7,14-diphenyl-N,N,N',N'-tetrakis(4-methylphenyl)acenaphtho[1,2-a]fluoranthene-3,10-diamine (abbreviated as p-mPhAFD), 2-{2-isopropyl-6-[2-(1,1,7,7-tetramethyl- 2-{2-tert-butyl-6-[2-(1,1,7,7-tetramethyl-2,3,6,7-tetrahydro-1H,5H-benzo[ij]quinolizin-9-yl)vinyl]-4H-pyran-4-ylidene}malononitrile (abbreviation: DCJTI), 2-{2-tert-butyl-6-[2-(1,1,7,7-tetramethyl-2,3,6,7-tetrahydro-1H,5H-benzo[ij]quinolizin-9-yl)vinyl]-4H-pyran-4-ylidene}malononitrile (abbreviation: DCJTB), 2-(2,6-bis{2-[4-(dimethylamino)phenyl]vinyl}-4H-pyran-4-ylidene)malononitrile (abbreviation: BisDCM), 2-{2,6-bis[2-(8-methoxy-1,1,7,7-tetramethyl-2,3,6,7-tetrahydro-1H,5H-benzo[ij]quinolizin-9-yl)vinyl]-4H-pyran-4-ylidene}malononitrile (abbreviated as: BisDCJTM), 5,10,15,20-tetraphenylbisbenzo[5,6]indeno[1,2,3-cd:1',2',3'-lm]perylene, etc.

[0159] In addition, when Compound 131 and Compound 132 form an exciplex, Compound 131, Compound 132, and Compound 133 are preferably selected so that the emission peak of the formed exciplex overlaps with the absorption band on the longest wavelength side (low energy side) of Compound 133 as a luminescent material.

[0160] The light-emitting layer 130 may also be formed of two or more layers. For example, when the light-emitting layer 130 is formed by stacking a first light-emitting layer and a second light-emitting layer in sequence from the hole transport layer side, the first light-emitting layer may be formed of a substance having a hole transport property as a host material, and the second light-emitting layer may be formed of a substance having an electron transport property as a host material.

[0161] In addition, if Figure 4A and Figure 4B As shown, the light-emitting layer 130 may also contain a material other than compound 131, compound 132, and compound 133 (compound 134). In this case, it is preferred that compound 132 and compound 134 form an exciplex. For this reason, it is preferred that the HOMO energy level of one of compound 132 and compound 134 is the highest among the materials of the light-emitting layer 130, and the LUMO energy level of the other of compound 132 and compound 134 is the lowest among the materials of the light-emitting layer 130. That is, the HOMO energy level of one of compound 132 and compound 134 is preferably higher than the HOMO energy level of the other of compound 132 and compound 134 and the HOMO energy level of compound 131, and the LUMO energy level of the other of compound 132 and compound 134 is preferably lower than the LUMO energy level of one of compound 132 and compound 134 and the LUMO energy level of compound 131. By adopting this structure, the reaction of compound 132 and compound 131 to form an exciplex can be suppressed.

[0162] As the compound 134, for example, the following hole-transporting materials and electron-transporting materials can be used.

[0163] As the hole transport material, a material having a hole transport property higher than an electron transport property can be used, and preferably a material having a 1×10 -6 cm 2The hole transport material may be a material with a hole mobility of 1 / Vs or higher. Specifically, aromatic amines, carbazole derivatives, etc. may be used. The hole transport material may also be a polymer compound.

[0164] As materials with high hole-transport properties, for example, aromatic amine compounds include N,N'-di(p-tolyl)-N,N'-diphenyl-p-phenylenediamine (abbreviation: DTDPPA), 4,4'-bis[N-(4-diphenylaminophenyl)-N-phenylamino]biphenyl (abbreviation: DPAB), N,N'-bis{4-[bis(3-methylphenyl)amino]phenyl}-N,N'-diphenyl-(1,1'-biphenyl)-4,4'-diamine (abbreviation: DNTPD), and 1,3,5-tris[N-(4-diphenylaminophenyl)-N-phenylamino]benzene (abbreviation: DPA3B).

[0165] In addition, specific examples of carbazole derivatives include 3-[N-(4-diphenylaminophenyl)-N-phenylamino]-9-phenylcarbazole (abbreviated as PCzDPA1), 3,6-bis[N-(4-diphenylaminophenyl)-N-phenylamino]-9-phenylcarbazole (abbreviated as PCzDPA2), 3,6-bis[N-(4-diphenylaminophenyl)-N-(1-naphthyl)amino]-9-phenylcarbazole (abbreviated as PCzDPA2), and 1-naphthylamino]-3-phenylcarbazole. CzTPN2), 3-[N-(9-phenylcarbazole-3-yl)-N-phenylamino]-9-phenylcarbazole (abbreviated as: PCzPCA1), 3,6-bis[N-(9-phenylcarbazole-3-yl)-N-phenylamino]-9-phenylcarbazole (abbreviated as: PCzPCA2), 3-[N-(1-naphthyl)-N-(9-phenylcarbazole-3-yl)amino]-9-phenylcarbazole (abbreviated as: PCzPCN1), etc.

[0166] Examples of carbazole derivatives include 4,4′-bis(N-carbazolyl)biphenyl (abbreviation: CBP), 1,3,5-tris[4-(N-carbazolyl)phenyl]benzene (abbreviation: TCPB), and 1,4-bis[4-(N-carbazolyl)phenyl]-2,3,5,6-tetraphenylbenzene.

[0167] In addition, as a material with a high hole-transporting property, for example, 4,4'-bis[N-(1-naphthyl)-N-phenylamino]biphenyl (abbreviated as NPB or α-NPD), N,N'-bis(3-methylphenyl)-N,N'-diphenyl-[1,1'-biphenyl]-4,4'-diamine (abbreviated as TPD), 4,4',4"-tris(carbazol-9-yl)triphenylamine (abbreviated as TCTA), 4,4',4"-tris[N-(1-naphthyl)-N-phenylamino]triphenylamine (abbreviated as 1'-TNATA), 4,4',4"-tris(N,N-diphenylamino)triphenylamine (abbreviated as TDATA), 4,4',4"-tris[N-(3-methylphenyl)-N-phenylamino]triphenylamine amine (abbreviated as m-MTDATA), 4,4'-bis[N-(spiro-9,9'-difluoren-2-yl)-N-phenylamino]biphenyl (abbreviated as BSPB), 4-phenyl-4'-(9-phenylfluoren-9-yl)triphenylamine (abbreviated as BPAFLP), 4-phenyl-3'-(9-phenylfluoren-9-yl)triphenylamine (abbreviated as mBPAFLP), N-(9,9-dimethyl-9H-fluoren-2-yl)-N-{9,9-dimethyl-2-[N'-phenyl-N'-(9,9-dimethyl-9H-fluoren-2-yl)amino]-9H-fluoren-7-yl}phenylamine (abbreviated as DFLADFL), N-(9,9-dimethyl-2-diphenylamino-9H-fluoren-7-yl)biphenylamine triphenylamine (abbreviation: PCBAB), 4-(1-naphthyl)-4'-(9-phenyl-9H-carbazole-3-yl)tri ... carbazol-3-yl)amine (abbreviation: PCA1BP), N,N'-bis(9-phenylcarbazol-3-yl)-N,N'-diphenylbenzene-1,3-diamine (abbreviation: PCA2B), N,N',N"-triphenyl-N,N',N"-tri(9-phenylcarbazol-3-yl)benzene-1,3,5-triamine (abbreviation: PCA3B), N-(4-biphenyl)-N-(9,9-dimethyl-9H-fluoren-2-yl)-9-phenyl-9H-carbazol-3-amine (abbreviation: PCBiF), N-(1,1'-biphenyl-4-yl)-N-[4-(9-phenyl-9H-carbazol-3-yl)phenyl]-9,9-dimethyl-9H-fluoren-2-amine (abbreviation: PCBBiF), 9,9-dimethyl-N-phenyl-N-[4-(9-phenyl-9H-carbazol-3-yl)phenyl]fluoren-2-amine (abbreviated as: PCBAF), N-phenyl-N-[4-(9-phenyl-9H-carbazol-3-yl)phenyl]spiro-9,9'-difluoren-2-amine (abbreviated as: PCBASF), 2-[N-(9-phenylcarbazol-3-yl)-N-phenylamino]spiro-9,9'-difluorene (abbreviated as: PCASF), 2,7 -Aromatic amine compounds such as bis[N-(4-diphenylaminophenyl)-N-phenylamino]spiro-9,9'-difluorene (abbreviation: DPA2SF), N-[4-(9H-carbazol-9-yl)phenyl]-N-(4-phenyl)phenylaniline (abbreviation: YGA1BP), N,N'-bis[4-(carbazol-9-yl)phenyl]-N,N'-diphenyl-9,9-dimethylfluorene-2,7-diamine (abbreviation: YGA2F), etc. In addition, 3-[4-(1-naphthyl)-phenyl]-9-phenyl-9H-carbazole (abbreviation: PCPN), 3-[4-(9-phenanthrenyl)-phenyl]-9-phenyl-9H-carbazole (abbreviation: PCPPn), 3,3'-bis(9-phenyl-9H-carbazole) (abbreviation: PCCP), 1,3-bis(N-carbazolyl)benzene (abbreviation: mCP), 3,6-bis(3,5-diphenylphenyl)-9-phenylcarbazole (abbreviation: CzTP), 4-{3-[3-(9-phenyl-9H-fluoren-9-yl)phenyl]phenyl}dibenzofuran (abbreviation: mmDBFFLBi-II), 4,4',4"-(benzene-1,3,5-triyl)tris(dibenzofuran) (abbreviation: Amine compounds, carbazole compounds, thiophene compounds, furan compounds, fluorene compounds, triphenylene compounds, phenanthrene compounds, etc. are also included. The substances described here mainly have a hole mobility of 1×10, -6 cm 2 However, any substance other than the above substances may be used as long as the substance has a higher hole-transporting property than an electron-transporting property.

[0168] As the electron transport material, a material having a higher electron transport property than a hole transport property can be used, and preferably a material having a 1×10 -6 cm 2 / Vs or more electron mobility. As a compound that easily receives electrons (a material with electron transport properties), a π-electron-deficient heteroaromatic compound or a metal complex of a nitrogen-containing heteroaromatic compound or the like can be used. As a specific example, a metal complex including a quinoline ligand, a benzoquinoline ligand, an oxazole ligand or a thiazole ligand can be cited. In addition, oxadiazole derivatives, triazole derivatives, phenanthroline derivatives, pyridine derivatives, bipyridine derivatives, pyrimidine derivatives, benzofuran pyrimidine derivatives or benzothieno pyrimidine derivatives can be cited. In addition, as long as the electron transport property is higher than the hole transport property, a substance other than the above substances can be used as the electron transport layer.

[0169] Specific examples of electron transport materials include tris(8-hydroxyquinolinolato)aluminum(III) (abbreviated as Alq), tris(4-methyl-8-hydroxyquinolinolato)aluminum(III) (abbreviated as Almq3), bis(10-hydroxybenzo[h]quinolinolato)beryllium(II) (abbreviated as BeBq2), bis(2-methyl-8-hydroxyquinolinolato)(4-phenylphenol)aluminum(III) (abbreviated as BAlq), and bis(8-hydroxyquinolinolato)zinc(II) (abbreviated as Znq). Furthermore, metal complexes having oxazolyl or thiazole ligands, such as bis[2-(2-benzoxazolyl)phenol]zinc(II) (abbreviated as ZnPBO) and bis[2-(2-benzothiazolyl)phenol]zinc(II) (abbreviated as ZnBTZ), can also be used.Furthermore, in addition to the metal complex, 2-(4-biphenyl)-5-(4-tert-butylphenyl)-1,3,4-oxadiazole (abbreviation: PBD), 1,3-bis[5-(p-tert-butylphenyl)-1,3,4-oxadiazol-2-yl]benzene (abbreviation: OXD-7), 9-[4-(5-phenyl-1,3,4-oxadiazol-2-yl)phenyl]-9H-carbazole (abbreviation: CO11), 3-(4-biphenyl)-4-phenyl-5-(4-tert-butylphenyl)-1,2,4-triazole (abbreviation: TAZ), 2,2',2"-(1,3,5-phenyltriyl)tris(1-phenyl-1H-benzimidazole) (abbreviation: TPBI), 2-[ Heterocyclic compounds such as 3-(dibenzothiophen-4-yl)phenyl]-1-phenyl-1H-benzimidazole (abbreviated as mDBTBIm-II), bathophenanthroline (abbreviated as BPhen), bathocuproin (abbreviated as BCP), 2,9-bis(naphthalene-2-yl)-4,7-diphenyl-1,10-phenanthroline (abbreviated as NBPhen); 2-[3-(dibenzothiophen-4-yl)phenyl]dibenzo[f,h]quinoxaline (abbreviated as 2mDBTPDBq-II), 2-[3'-(dibenzothiophen-4-yl)biphenyl-3-yl]dibenzo[f,h]quinoxaline (abbreviated as 2mDBTBPDBq-II), 2-[3'-(9H-carbazole- 9-yl)biphenyl-3-yl]dibenzo[f,h]quinoxaline (abbreviation: 2mCzBPDBq), 2-[4-(3,6-diphenyl-9H-carbazol-9-yl)phenyl]dibenzo[f,h]quinoxaline (abbreviation: 2CzPDBq-III), 7-[3-(dibenzothiophen-4-yl)phenyl]dibenzo[f,h]quinoxaline (abbreviation: 7mDBTPDBq-II), 6-[3-(dibenzothiophen-4-yl)phenyl]dibenzo[f,h]quinoxaline (abbreviation: 6mDBTPDBq-II), 4,6-bis[3-(phenanthren-9-yl)phenyl]pyrimidine (abbreviation: 4,6mPnP2Pm), 4,6-bis[3-(4 -dibenzothiophenyl)phenyl]pyrimidine (abbreviation: 4,6mDBTP2Pm-II), 4,6-bis[3-(9H-carbazol-9-yl)phenyl]pyrimidine (abbreviation: 4,6mCzP2Pm), and other heterocyclic compounds having a diazine skeleton; PCCzPTzn, and other heterocyclic compounds having a triazine skeleton; 3,5-bis[3-(9H-carbazol-9-yl)phenyl]pyridine (abbreviation: 35DCzPPy), 1,3,5-tris[3-(3-pyridyl)phenyl]benzene (abbreviation: TmPyPB), and other heterocyclic compounds having a pyridine skeleton; 4,4'-bis(5-methylbenzoxazolyl-2-yl)stilbene (abbreviation: BzOs), and other heteroaromatic compounds.Alternatively, polymer compounds such as poly(2,5-pyridinediyl) (abbreviated as PPy), poly[(9,9-dihexylfluorene-2,7-diyl)-co-(pyridine-3,5-diyl)] (abbreviated as PF-Py), and poly[(9,9-dioctylfluorene-2,7-diyl)-co-(2,2'-bipyridine-6,6'-diyl)] (abbreviated as PF-BPy) can be used. The substances described here primarily have an electron mobility of 1×10. -6 cm 2 Note that any substance other than the above substances may be used as long as it has a higher electron-transporting property than a hole-transporting property.

[0170] When Compound 134 forms an exciplex with Compound 132, Compound 131, Compound 132, and Compound 134 are preferably selected so that the emission peak of the formed exciplex overlaps with the absorption band of Compound 131 on the longest wavelength side (low energy side).

[0171] A Pair of Electrodes Electrodes 101 and 102 have the function of injecting holes and electrons into the light-emitting layer 130. Electrodes 101 and 102 can be formed using metals, alloys, conductive compounds, mixtures thereof, or laminates thereof. A typical example of a metal is aluminum (Al). In addition, transition metals such as silver (Ag), tungsten, chromium, molybdenum, copper, and titanium; alkali metals such as lithium (Li) or cesium; and Group 2 metals such as calcium or magnesium (Mg) can be used. Rare earth metals such as ytterbium (Yb) can also be used as transition metals. Alloys containing any of the above metals can be used, for example, MgAg, AlLi, etc. Conductive compounds include, for example, metal oxides such as indium tin oxide (ITO), indium tin oxide containing silicon or silicon oxide (ITSO), indium zinc oxide, and indium oxide containing tungsten and zinc. Inorganic carbon materials such as graphene can also be used as conductive compounds. As described above, electrodes 101 and / or electrodes 102 can be formed by stacking a plurality of these materials.

[0172] In addition, the light emitted from the light-emitting layer 130 is extracted through the electrode 101 and / or the electrode 102. Therefore, at least one of the electrode 101 and the electrode 102 transmits visible light. Examples of light-transmitting conductive materials include those having a visible light transmittance of 40% or more and 100% or less, preferably 60% or more and 100% or less, and a resistivity of 1×10 -2Ω·cm or less. In addition, the electrode on the light extraction side may also be formed of a conductive material having a light-transmitting function and a light-reflecting function. Examples of such conductive materials include those having a visible light reflectivity of 20% or more and 80% or less, preferably 40% or more and 70% or less, and a resistivity of 1×10 -2 When a material with low light transmittance, such as a metal or alloy, is used for the light extraction electrode, one or both of the electrodes 101 and 102 need only be formed to a thickness sufficient to transmit visible light (e.g., 1 nm to 10 nm).

[0173] Note that in this specification, as the electrode having a light-transmitting function, a material that transmits visible light and has conductivity may be used, such as the oxide conductor layer represented by ITO (Indium Tin Oxide), an oxide semiconductor layer, or an organic conductor layer containing an organic substance. Examples of the organic conductor layer containing an organic substance include a layer containing a composite material formed by mixing an organic compound and an electron donor (donor), a layer containing a composite material formed by mixing an organic compound and an electron acceptor (acceptor), and the like. In addition, the resistivity of the transparent conductive layer is preferably 1×10 5 Ω·cm or less, more preferably 1×10 4 Ω·cm or less.

[0174] As a method for forming the electrodes 101 and 102 , sputtering, vapor deposition, printing, coating, MBE (Molecular Beam Epitaxy), CVD, pulsed laser deposition, ALD (Atomic Layer Deposition), or the like can be appropriately used.

[0175] Hole injection layer The hole injection layer 111 has the function of lowering the injection barrier of holes from one of the pair of electrodes (electrode 101 or electrode 102) to promote hole injection, and is formed using, for example, a transition metal oxide, a phthalocyanine derivative, or an aromatic amine. Examples of transition metal oxides include molybdenum oxide, vanadium oxide, ruthenium oxide, tungsten oxide, and manganese oxide. Examples of phthalocyanine derivatives include phthalocyanine or metal phthalocyanine. Examples of aromatic amines include benzidine derivatives or phenylenediamine derivatives. Polymer compounds such as polythiophene or polyaniline can also be used, typically poly(ethylenedioxythiophene) / poly(styrenesulfonic acid) as a self-doped polythiophene.

[0176] As the hole injection layer 111, a layer having a composite material composed of a hole transport material and a material having the property of receiving electrons from the hole transport material can be used. Alternatively, a stack of a layer containing a material having the property of receiving electrons and a layer containing a hole transport material can be used. In a steady state or in the presence of an electric field, charge transfer can be carried out between these materials. As materials having the property of receiving electrons, organic acceptors such as quinone dimethane derivatives, tetrachlorobenzoquinone derivatives, and hexaazatriphenylene derivatives can be cited. Specific examples include compounds having electron-withdrawing groups (particularly halogen groups such as fluorine groups and cyano groups), such as 7,7,8,8-tetracyano-2,3,5,6-tetrafluoroquinodimethane (abbreviated as F4-TCNQ), chloranil, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (abbreviated as HAT-CN), and 1,3,4,5,7,8-hexafluorotetracyano-naphthoquinodimethane (abbreviated as F6-TCNNQ). Compounds such as HAT-CN, in which the electron-withdrawing group is bonded to a fused aromatic ring having multiple heteroatoms, are particularly preferred because they are thermally stable. In addition, [3]radialene derivatives containing electron-withdrawing groups (especially halogen groups such as fluorine groups and cyano groups) are particularly preferred because of their very high electron-accepting properties. Specifically, they include: α,α',α"-1,2,3-cycloalkyltriylidene tris[4-cyano-2,3,5,6-tetrafluorophenylacetonitrile], α,α',α"-1,2,3-cyclopropanetriylidene tris[2,6-dichloro-3,5-difluoro-4 -(trifluoromethyl)phenylacetonitrile], α,α',α"-1,2,3-cycloalkanetriylidenetris[2,3,4,5,6-pentafluorophenylacetonitrile]. Transition metal oxides, such as oxides of Group 4 to Group 8 metals, can also be used. Specifically, vanadium oxide, niobium oxide, tantalum oxide, chromium oxide, molybdenum oxide, tungsten oxide, manganese oxide, rhenium oxide, etc. can be used. Molybdenum oxide is particularly preferably used because it is stable even in the atmosphere, has low hygroscopicity, and is easy to handle.

[0177] As the hole transport material, a material having a hole transport property higher than an electron transport property can be used, and preferably a material having a 1×10 -6 cm 2 / Vs or higher. Specifically, aromatic amines and carbazole derivatives, which are examples of hole-transporting materials that can be used in the light-emitting layer 130, can be used. In addition, aromatic hydrocarbons and stilbene derivatives can also be used. The hole-transporting materials can also be polymer compounds.

[0178] Examples of aromatic hydrocarbons include 2-tert-butyl-9,10-di(2-naphthyl)anthracene (abbreviation: t-BuDNA), 2-tert-butyl-9,10-di(1-naphthyl)anthracene, 9,10-bis(3,5-diphenylphenyl)anthracene (abbreviation: DPPA), 2-tert-butyl-9,10-bis(4-phenylphenyl)anthracene (abbreviation: t-BuDBA), 9,10-di(2-naphthyl)anthracene (abbreviation: DNA), 9,10-diphenylanthracene (abbreviation: DPAnth), 2-tert-butylanthracene (abbreviation: t-BuAnth), 9,10-bis(4-methyl-1-naphthyl)anthracene (abbreviation: DMNA), 2-tert-butyl-9,10-bis[2-(1-naphthyl)phenyl]anthracene, 9,10-bis[2-(1-naphthyl)phenyl]anthracene, 2,3,6,7-tetramethyl-9,10-di(1-naphthyl)anthracene, 2,3,6,7-tetramethyl-9,10-di(2-naphthyl)anthracene, 9,9'-bianthracene, 10,10'-diphenyl-9,9'-bianthracene, 10,10'-bis(2-phenylphenyl)-9,9'-bianthracene, 10,10'-bis[(2,3,4,5,6-pentaphenyl)phenyl]-9,9'-bianthracene, anthracene, tetracene, rubrene, perylene, 2,5,8,11-tetra(tert-butyl)perylene, etc. In addition to these, pentacene, coronene, etc. can also be used. Thus, it is more preferable to use a 1×10 -6 cm 2 An aromatic hydrocarbon having a hole mobility of 1 / Vs or higher and 14 to 42 carbon atoms.

[0179] Note that the aromatic hydrocarbon may also have a vinyl skeleton. Examples of aromatic hydrocarbons having a vinyl group include 4,4'-bis(2,2-diphenylvinyl)biphenyl (abbreviated as DPVBi) and 9,10-bis[4-(2,2-diphenylvinyl)phenyl]anthracene (abbreviated as DPVPA).

[0180] In addition, high molecular weight compounds such as poly(N-vinylcarbazole) (abbreviation: PVK), poly(4-vinyltriphenylamine) (abbreviation: PVTPA), poly[N-(4-{N'-[4-(4-diphenylamino)phenyl]phenyl-N'-phenylamino}phenyl)methacrylamide] (abbreviation: PTPDMA), and poly[N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine] (abbreviation: Poly-TPD) can also be used.

[0181] Hole Transport Layer The hole transport layer 112 is a layer containing a hole-transporting material, and the materials exemplified as the materials for the hole injection layer 111 can be used. In order for the hole transport layer 112 to transport holes injected into the hole injection layer 111 to the light-emitting layer 130, the HOMO level of the hole transport layer 112 is preferably the same as or close to the HOMO level of the hole injection layer 111.

[0182] As the hole-transporting material, the materials listed as examples of the materials for the hole-injection layer 111 and the compound 134 can be used. In addition, it is preferable to use a material having a 1×10 -6 cm 2 / Vs or more. However, as long as the hole transport property is higher than the electron transport property, a substance other than the above substances can be used. In addition, the layer including the substance with high hole transport property is not limited to a single layer, and two or more layers including the above substances can be stacked.

[0183] Electron Transport Layer The electron transport layer 118 has the function of transporting electrons injected from the other of the pair of electrodes (electrode 101 or electrode 102) through the electron injection layer 119 to the light-emitting layer 130. As the electron transport material, a material with a higher electron transport property than a hole transport property can be used, and preferably a material with a 1×10 -6 cm 2 However, any material other than the above may be used as long as it has a higher electron transport property than a hole transport property.

[0184] As the electron transporting material, the materials exemplified as the material of compound 134 can be used. In addition, it is preferable to use a material having a 1×10 -6 cm 2 The electron transport layer 118 is not limited to a single layer, and two or more layers containing the above-mentioned substances may be stacked.

[0185] Furthermore, a layer for controlling the movement of electron carriers can be provided between the electron transport layer 118 and the light-emitting layer 130. This layer is formed by adding a small amount of a substance with high electron-trapping properties to the aforementioned material with high electron transport properties. By suppressing the movement of electron carriers, the carrier balance can be adjusted. This structure is very effective in suppressing problems caused by electrons passing through the light-emitting layer (such as a reduction in device life).

[0186] Electron injection layer The electron injection layer 119 has the function of lowering the injection barrier of electrons from the electrode 102 to promote electron injection. For example, Group 1 metals, Group 2 metals or their oxides, halides, carbonates, etc. can be used. A composite material of the above-mentioned electron transport material and a material having the property of supplying electrons to the electron transport material can also be used. As materials having electron-donating properties, Group 1 metals, Group 2 metals or their oxides can be cited. Specifically, lithium fluoride (LiF), sodium fluoride (NaF), cesium fluoride (CsF), calcium fluoride (CaF2) and lithium oxide (LiO x ) or other alkali metals, alkaline earth metals, or compounds of these metals. In addition, rare earth metal compounds such as erbium fluoride (ErF3) can be used. In addition, an electron salt can also be used for the electron injection layer 119. As the electron salt, for example, a substance that adds electrons to a mixed oxide of calcium and aluminum at a high concentration can be cited. In addition, a substance that can be used for the electron transport layer 118 can also be used for the electron injection layer 119.

[0187] In addition, a composite material formed by mixing an organic compound with an electron donor (donor) can also be used for the electron injection layer 119. This composite material has excellent electron injection and electron transport properties because electrons are generated in the organic compound by the electron donor. In this case, the organic compound is preferably a material with excellent performance in transporting the generated electrons. Specifically, for example, the substances constituting the electron transport layer 118 as described above (metal complexes, heteroaromatic compounds, etc.) can be used. As an electron donor, any substance that exhibits electron-donating properties for organic compounds can be used. Specifically, alkali metals, alkaline earth metals and rare earth metals are preferably used, and lithium, cesium, magnesium, calcium, erbium, ytterbium, etc. can be mentioned. In addition, alkali metal oxides or alkaline earth metal oxides are preferably used, and lithium oxide, calcium oxide, barium oxide, etc. can be mentioned. In addition, Lewis bases such as magnesium oxide can also be used. In addition, organic compounds such as tetrathiafulvalene (abbreviated as: TTF) can also be used.

[0188] In addition, the above-mentioned light-emitting layer, hole injection layer, hole transport layer, electron transport layer and electron injection layer can be formed by evaporation (including vacuum evaporation), inkjet method, coating method, nozzle printing method, gravure printing and the like. In addition, as the above-mentioned light-emitting layer, hole injection layer, hole transport layer, electron transport layer and electron injection layer, in addition to the above-mentioned materials, inorganic compounds such as quantum dots or high molecular compounds (oligomers, dendrimers, polymers, etc.) can also be used.

[0189] As quantum dots, colloidal quantum dots, alloy quantum dots, core-shell quantum dots, core-type quantum dots, etc. can be used. In addition, quantum dots containing elements from Group 2 and Group 16, Group 13 and Group 15, Group 13 and Group 17, Group 11 and Group 17, or Group 14 and Group 15 can also be used. Alternatively, quantum dots containing elements such as cadmium (Cd), selenium (Se), zinc (Zn), sulfur (S), phosphorus (P), indium (In), tellurium (Te), lead (Pb), gallium (Ga), arsenic (As), and aluminum (Al) can be used.

[0190] As the liquid medium used for the wet method, for example, ketones such as methyl ethyl ketone and cyclohexanone; glycerol fatty acid esters such as ethyl acetate; halogenated aromatic hydrocarbons such as dichlorobenzene; aromatic hydrocarbons such as toluene, xylene, mesitylene, cyclohexylbenzene; aliphatic hydrocarbons such as cyclohexane, decahydronaphthalene, dodecane; organic solvents such as dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0191] Examples of polymer compounds that can be used for the light-emitting layer include polyphenylene vinylene (PPV) derivatives such as poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (abbreviated as MEH-PPV) and poly(2,5-dioctyl-1,4-phenylene vinylene); polyfluorene derivatives such as poly(9,9-di-n-octylfluorenyl-2,7-diyl) (abbreviated as PF8), poly[(9,9-di-n-octylfluorenyl-2,7-diyl)-alt-(benzo[2,1,3]thiadiazole-4,8-diyl)] (abbreviated as F8BT), poly[(9 Examples of the present invention include poly(9,9-dioctylfluorenyl-2,7-diyl)-alt-(2,2'-bithiophene-5,5'-diyl)] (abbreviated as F8T2), poly[(9,9-dioctyl-2,7-divinylenefluorenyl)-alt-(9,10-anthracene)], poly[(9,9-dihexylfluorenyl-2,7-diyl)-alt-(2,5-dimethyl-1,4-phenylene)], polyalkylthiophene (PAT) derivatives such as poly(3-hexylthiophene-2,5-diyl) (abbreviated as P3HT), and polyphenylene derivatives. Furthermore, polymer compounds such as the above-mentioned polymer compounds, PVK, poly(2-vinylnaphthalene), and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (abbreviated as PTAA) can be doped with a light-emitting compound and used in the light-emitting layer. As the light-emitting compound, the light-emitting compounds exemplified above can be used.

[0192] Although one embodiment of the present invention employs a mixture of an organic compound containing a benzofuranopyrimidine skeleton or a benzothienopyrimidine skeleton, an organic compound capable of converting triplet excitation energy into luminescence, and an organic compound exhibiting fluorescence for use in the light-emitting layer 130, a polymer compound having the aforementioned skeletons or functions may also be used. For example, a polymer compound containing a benzofuranopyrimidine skeleton or a benzothienopyrimidine skeleton, a substituent capable of converting triplet excitation energy into luminescence, and a substituent exhibiting fluorescence may also be used in the light-emitting layer 130. Furthermore, a polymer compound containing a benzofuranopyrimidine skeleton or a benzothienopyrimidine skeleton and a substituent capable of converting triplet excitation energy into luminescence may also be mixed with a low-molecular-weight substance exhibiting fluorescence to manufacture the light-emitting layer 130. Using this polymer compound improves material utilization efficiency, thereby reducing manufacturing costs.

[0193] Substrate The light-emitting element of one embodiment of the present invention can be manufactured over a substrate made of glass, plastic, etc. The order of stacking layers on the substrate may be either sequentially stacked from the electrode 101 side or sequentially stacked from the electrode 102 side.

[0194] In addition, as a substrate capable of forming a light-emitting element according to one embodiment of the present invention, for example, glass, quartz, or plastic can be used. Alternatively, a flexible substrate can also be used. A flexible substrate is a bendable substrate, such as a plastic substrate made of polycarbonate or polyarylate. In addition, a thin film or an inorganic thin film formed by vapor deposition can be used. Note that other materials can be used as long as they serve as a support during the manufacturing process of the light-emitting element. Alternatively, any material can be used as long as it has the function of protecting the light-emitting element.

[0195] For example, in this specification, etc., various substrates can be used to form light-emitting elements. There is no particular limitation on the type of substrate. As examples of the substrate, for example, a semiconductor substrate (for example, a single crystal substrate or a silicon substrate), an SOI substrate, a glass substrate, a quartz substrate, a plastic substrate, a metal substrate, a stainless steel substrate, a substrate with a stainless steel foil, a tungsten substrate, a substrate with a tungsten foil, a flexible substrate, a bonding film, a cellulose nanofiber (CNF) containing a fibrous material, paper or a substrate film, etc. can be used. As examples of glass substrates, there are barium borosilicate glass, aluminoborosilicate glass, soda-lime glass, etc. As flexible substrates, bonding films, substrate films, etc., the following examples can be given. For example, plastics represented by polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyethersulfone (PES), and polytetrafluoroethylene (PTFE) can be given. Alternatively, as an example, resins such as acrylic resins can be given. Alternatively, as an example, polypropylene, polyester, polyvinyl fluoride, or polyvinyl chloride can be given. Alternatively, as an example, polyamide, polyimide, aramid, epoxy resin, inorganic vapor-deposited film, paper, etc. can be cited.

[0196] Alternatively, a flexible substrate can be used as the substrate, and the light-emitting element can be formed directly on the flexible substrate. Alternatively, a release layer can be provided between the substrate and the light-emitting element. The release layer can be used when part or all of the light-emitting element is manufactured on the release layer, and then separated from the substrate and transferred to another substrate. In this case, the light-emitting element can also be transferred to a substrate with low heat resistance or a flexible substrate. For example, the release layer can be a laminated structure of an inorganic film such as a tungsten film and a silicon oxide film, or a structure in which a resin film such as a polyimide is formed on a substrate.

[0197] That is, a light-emitting element can be formed using one substrate and then transferred to another substrate. Examples of substrates to which the light-emitting element is transferred include, in addition to the aforementioned substrates, cellophane substrates, stone substrates, wood substrates, cloth substrates (including natural fibers (silk, cotton, linen), synthetic fibers (nylon, polyurethane, polyester), or regenerated fibers (acetate, cuprammonium, rayon, regenerated polyester), etc.), leather substrates, and rubber substrates. By using these substrates, it is possible to manufacture light-emitting elements that are not easily damaged, have high heat resistance, achieve lightweight properties, or achieve thinness.

[0198] Alternatively, a field effect transistor (FET) may be formed over the substrate, and the light emitting element 150 may be fabricated on an electrode electrically connected to the FET. Thus, an active matrix display device in which the light emitting element 150 is driven by the FET can be fabricated.

[0199] The structure described in this embodiment can be used in combination with the structures described in other embodiment modes as appropriate.

[0200] (Implementation Method 2) In this embodiment, referring to Figure 5 A light-emitting element having a structure different from that of the light-emitting element described in Embodiment 1 will be described. Figure 5 In the Figure 1A The parts with the same functions as the reference numerals shown in the figure are shaded with the same shading, and the reference numerals are sometimes omitted. Figure 1A Components with the same functions are denoted by the same reference numerals, and detailed description thereof may be omitted.

[0201] <Structural Example 2 of Light-Emitting Element> Figure 5 is a schematic cross-sectional view of the light emitting element 250 .

[0202] Figure 5 The light emitting element 250 shown has a plurality of light emitting units (light emitting unit 106 and light emitting unit 108) between a pair of electrodes (electrode 101 and electrode 102). One of the plurality of light emitting units preferably has a Figure 1A The EL layer 100 has the same structure as shown. Figure 1A The light emitting element 150 shown preferably has one light emitting unit, while the light emitting element 250 preferably has multiple light emitting units. In the light emitting element 250, although the electrode 101 is an anode and the electrode 102 is a cathode, the structure of the light emitting element 250 may also be the opposite.

[0203] exist Figure 5 In the illustrated light-emitting element 250, the light-emitting unit 106 and the light-emitting unit 108 are stacked, and the charge generation layer 115 is provided between the light-emitting unit 106 and the light-emitting unit 108. The light-emitting unit 106 and the light-emitting unit 108 may have the same structure or different structures. For example, the light-emitting unit 108 preferably has the same structure as the EL layer 100.

[0204] Light-emitting element 250 includes light-emitting layer 120 and light-emitting layer 170. Light-emitting unit 106 includes, in addition to light-emitting layer 120, hole injection layer 111, hole transport layer 112, electron transport layer 113, and electron injection layer 114. Light-emitting unit 108 includes, in addition to light-emitting layer 170, hole injection layer 116, hole transport layer 117, electron transport layer 118, and electron injection layer 119.

[0205] In the light-emitting element 250, either the light-emitting unit 106 or the light-emitting unit 108 may contain the organic compound according to one embodiment of the present invention. The layer containing the organic compound is preferably the electron-transport layer 113 or the electron-transport layer 118, and more preferably the light-emitting layer 120 or the light-emitting layer 170.

[0206] The charge generation layer 115 may have a structure in which an acceptor substance serving as an electron acceptor is added to a hole transport material, or a structure in which a donor substance serving as an electron donor is added to an electron transport material, or both structures may be stacked.

[0207] When the charge generation layer 115 includes a composite material composed of an organic compound and an acceptor substance, the composite material that can be used for the hole injection layer 111 described in Embodiment 1 can be used as the composite material. As the organic compound, various compounds such as aromatic amine compounds, carbazole compounds, aromatic hydrocarbons, and high molecular weight compounds (oligomers, dendrimers, polymers, etc.) can be used. In addition, as the organic compound, it is preferable to use an organic compound having a hole mobility of 1×10 -6 cm 2 / Vs or above. However, as long as the hole transport property is higher than the electron transport property, substances other than these can be used. Because the composite material composed of organic compounds and acceptor substances has good carrier injection and carrier transport properties, low voltage drive and low current drive can be achieved. Note that when the surface on the anode side of the light-emitting unit contacts the charge generation layer 115, the charge generation layer 115 can also have the function of the hole injection layer or hole transport layer of the light-emitting unit, so the hole injection layer or hole transport layer may not be provided in the light-emitting unit. When the surface on the cathode side of the light-emitting unit contacts the charge generation layer 115, the charge generation layer 115 can also have the function of the electron injection layer or electron transport layer of the light-emitting unit, so the electron injection layer or electron transport layer may not be provided in the light-emitting unit.

[0208] Note that the charge generation layer 115 may have a stacked-layer structure comprising a layer comprising a composite material of an organic compound and an acceptor substance, and a layer comprising another material. For example, a structure may be formed by combining a layer comprising a composite material of an organic compound and an acceptor substance, and a layer comprising one compound selected from electron-donating substances and a compound having a high electron-transporting property. Alternatively, a structure may be formed by combining a layer comprising a composite material of an organic compound and an acceptor substance, and a layer comprising a transparent conductive film.

[0209] The charge generation layer 115 sandwiched between the light emitting unit 106 and the light emitting unit 108 may have a structure that injects electrons into one light emitting unit and injects holes into the other light emitting unit when a voltage is applied between the electrode 101 and the electrode 102. Figure 5 In the embodiment, when a voltage is applied so that the potential of the electrode 101 is higher than the potential of the electrode 102 , the charge generation layer 115 injects electrons into the light-emitting unit 106 and injects holes into the light-emitting unit 108 .

[0210] From the viewpoint of light extraction efficiency, the charge generation layer 115 preferably has visible light transmittance (specifically, a visible light transmittance of 40% or more). Furthermore, the charge generation layer 115 functions even if its conductivity is lower than that of the pair of electrodes (electrode 101 and electrode 102 ).

[0211] By forming the charge generation layer 115 using the above-mentioned material, an increase in driving voltage when a light-emitting layer is stacked can be suppressed.

[0212] Although Figure 5 While a light-emitting element having two light-emitting units is described above, the same structure can be applied to a light-emitting element having three or more light-emitting units stacked together. As shown in light-emitting element 250, by arranging multiple light-emitting units between a pair of electrodes, separated by a charge generation layer, a light-emitting element can be realized that can achieve high brightness while maintaining a low current density and a longer life. Furthermore, a light-emitting element with low power consumption can be realized.

[0213] In each of the above structures, the guest materials used in the light-emitting units 106 and 108 can emit light of the same or different colors. When the light-emitting units 106 and 108 include guest materials that emit light of the same color, the light-emitting element 250 preferably exhibits high luminance at a low current value. Furthermore, when the light-emitting units 106 and 108 include guest materials that emit light of different colors, the light-emitting element 250 preferably emits light of multiple colors. In this case, when multiple light-emitting materials having different emission wavelengths are used in one or both of the light-emitting layers 120 and 170, light having different emission peaks is synthesized, and the emission spectrum of the light-emitting element 250 has at least two maxima.

[0214] The above structure is suitable for obtaining white light. White light can be obtained by making the light emitted by light-emitting layer 120 and light-emitting layer 170 complementary colors. It is particularly preferable to select a guest material that produces white light with high color rendering properties or emits light with at least red, green, and blue.

[0215] The structure of the light-emitting layer 130 described in Embodiment 1 is preferably used in one or both of the light-emitting layer 120 and the light-emitting layer 170. This structure allows for a light-emitting element with excellent luminous efficiency and reliability. The guest material included in the light-emitting layer 130 is a fluorescent material. Therefore, by using the structure of the light-emitting layer 130 described in Embodiment 1 in one or both of the light-emitting layer 120 and the light-emitting layer 170, a light-emitting element with a sharp emission spectrum and high color purity can be obtained.

[0216] In addition, in a light-emitting element in which three or more light-emitting units are stacked, the luminescent colors of the guest materials used for each light-emitting unit may be the same or different. In the case where the light-emitting element includes a plurality of light-emitting units that emit light of the same color, these light-emitting units can obtain a light-emitting color with high luminescence brightness at a lower current value than other colors. This structure is suitable for adjusting the luminescent color. It is particularly preferred for use in the case of using guest materials with different luminous efficiencies and exhibiting different luminescent colors. For example, in the case of providing three light-emitting units, by providing two light-emitting units containing a fluorescent material that exhibits the same luminescent color and one light-emitting unit containing a phosphorescent material that exhibits a luminescent color different from the fluorescent material, the luminescent intensity of the fluorescent and phosphorescent light can be adjusted. In other words, the luminescent intensity of each color can be adjusted according to the number of light-emitting units.

[0217] In the case of using the above-mentioned light-emitting element including two fluorescent light-emitting units and one phosphorescent light-emitting unit, in order to efficiently obtain white light emission, it is preferably adopted the following structure: a structure in which the light-emitting unit includes two light-emitting units including blue fluorescent material and one light-emitting unit including yellow phosphorescent material; a structure in which the light-emitting unit includes two light-emitting units including blue fluorescent material and one light-emitting unit including red phosphorescent material and green phosphorescent material; a structure in which the light-emitting unit includes two light-emitting units including blue fluorescent material and one light-emitting unit including red phosphorescent material, yellow phosphorescent material and green phosphorescent material.

[0218] Alternatively, at least one of the light-emitting layer 120 and the light-emitting layer 170 may be further divided into layers, each containing a different light-emitting material. That is, at least one of the light-emitting layer 120 and the light-emitting layer 170 may be formed from two or more layers. For example, when a first light-emitting layer and a second light-emitting layer are stacked sequentially from the hole-transporting layer to form the light-emitting layer, a material with hole-transporting properties may be used as the host material for the first light-emitting layer, and a material with electron-transporting properties may be used as the host material for the second light-emitting layer. In this case, the light-emitting materials contained in the first and second light-emitting layers may be the same or different. Furthermore, the light-emitting materials contained in the first and second light-emitting layers may be materials capable of emitting light of the same color or materials capable of emitting light of different colors. By employing a structure in which multiple light-emitting materials capable of emitting light of different colors are used, white light with high color rendering properties, composed of three primary colors or four or more colors, can be obtained.

[0219] This embodiment mode can be appropriately combined with any other embodiment mode.

[0220] (Implementation 3) In this embodiment, reference is made to Figure 6A and Figure 6B A light-emitting device using the light-emitting element described in Embodiments 1 and 2 will be described.

[0221] Figure 6A is a top view of the light emitting device, Figure 6B It is along Figure 6A AB and CD cross-sectional views in FIG. The light-emitting device includes a driver circuit portion (source-side driver circuit) 601 for controlling the light emission of the light-emitting element, a pixel portion 602, and a driver circuit portion (gate-side driver circuit) 603, indicated by dashed lines. Reference numeral 604 denotes a sealing substrate, reference numeral 625 denotes a desiccant, and reference numeral 605 denotes a sealant. The space within the space surrounded by sealant 605 is space 607.

[0222] Note that the lead wiring 608 is used to transmit signals input to the source-side driver circuit 601 and the gate-side driver circuit 603, and receives video signals, clock signals, start signals, reset signals, etc. from the flexible printed circuit (FPC) 609, which serves as an external input terminal. Although only the FPC is shown here, the FPC can also be mounted on a printed wiring board (PWB). The light-emitting device in this specification includes not only the light-emitting device itself, but also a light-emitting device mounted with an FPC or PWB.

[0223] Next, refer to Figure 6BThe cross-sectional structure of the light emitting device is described below. A driver circuit portion and a pixel portion are formed on an element substrate 610. Here, a source-side driver circuit 601 serving as the driver circuit portion and one pixel in the pixel portion 602 are shown.

[0224] In the source-side driver circuit 601, a CMOS circuit is formed by combining an n-channel TFT 623 and a p-channel TFT 624. The driver circuit can also be formed using various CMOS circuits, PMOS circuits, or NMOS circuits. Although this embodiment shows a driver-integrated type in which the driver circuit is formed on the substrate, the driver circuit does not necessarily need to be formed on the substrate and can also be formed outside the substrate.

[0225] The pixel portion 602 includes a plurality of pixels including a switching TFT 611, a current control TFT 612, and a first electrode 613 electrically connected to the drain of the current control TFT 612. Note that an insulator 614 is formed to cover the end of the first electrode 613. The insulator 614 can be formed using a positive photosensitive resin film.

[0226] To improve the coverage of the film formed on insulator 614, the upper or lower end of insulator 614 is formed into a curved surface. For example, when photosensitive acrylic resin is used as the material for insulator 614, it is preferable to form a curved surface only on the upper end of insulator 614. The radius of curvature of this curved surface is preferably not less than 0.2 μm and not more than 0.3 μm. Insulator 614 can be made of either a negative-type photosensitive material or a positive-type photosensitive material.

[0227] An EL layer 616 and a second electrode 617 are formed on the first electrode 613. A material having a high work function is preferably used as the material for the first electrode 613, which serves as an anode. For example, in addition to single-layer films such as an ITO film, an indium tin oxide film containing silicon, an indium oxide film containing 2% to 20% zinc oxide by weight, a titanium nitride film, a chromium film, a tungsten film, a Zn film, and a Pt film, a stacked film comprising a titanium nitride film and a film primarily composed of aluminum, and a three-layer structure comprising a titanium nitride film, a film primarily composed of aluminum, and a titanium nitride film can also be used. When a stacked-layer structure is used, wiring resistance is also low, good ohmic contact can be achieved, and this can be used as an anode.

[0228] The EL layer 616 is formed by any of various methods, such as vapor deposition using a vapor deposition mask, inkjet, and spin coating. As a material contained in the EL layer 616, a low molecular weight compound or a high molecular weight compound (including an oligomer or a dendrimer) can be used.

[0229] The material of the second electrode 617, which is formed on the EL layer 616 and serves as a cathode, is preferably a material having a low work function (e.g., Al, Mg, Li, Ca, or alloys or compounds thereof, MgAg, MgIn, AlLi, etc.). To allow light generated in the EL layer 616 to pass through the second electrode 617, the second electrode 617 is preferably a stacked layer consisting of a relatively thin metal film and a transparent conductive film (e.g., ITO, indium oxide containing 2 wt% to 20 wt% zinc oxide, indium tin oxide containing silicon, zinc oxide (ZnO), etc.).

[0230] Note that the light-emitting element 618 is formed of the first electrode 613, the EL layer 616, and the second electrode 617. The light-emitting element 618 preferably has the structure described in Embodiment 1 or 2. In the light-emitting device of this embodiment, a pixel portion including a plurality of light-emitting elements may include both light-emitting elements having the structures described in Embodiment 1 or 2 and light-emitting elements having different structures.

[0231] The sealing substrate 604 and the element substrate 610 are bonded together using the sealant 605, and a light-emitting element 618 is provided in a space 607 surrounded by the element substrate 610, the sealing substrate 604, and the sealant 605. The space 607 is filled with a filler. The filler may be an inert gas (nitrogen, argon, etc.), a resin, and / or a desiccant.

[0232] Epoxy resin or glass powder is preferably used as the sealant 605. These materials are preferably materials that do not allow moisture or oxygen to pass through as much as possible. As the sealing substrate 604, a glass substrate, a quartz substrate, or a plastic substrate formed of fiber reinforced plastic (FRP), polyvinyl fluoride (PVF), polyester, or acrylic resin can be used.

[0233] By the above method, a light-emitting device including the light-emitting element described in Embodiment Mode 1 and Embodiment Mode 2 can be obtained.

[0234] <Structural Example 1 of Light Emitting Device> Figure 7A and Figure 7B Each example shows a light-emitting device including a light-emitting element that emits white light and a colored layer (color filter).

[0235] Figure 7AShown are a substrate 1001, a base insulating film 1002, a gate insulating film 1003, gate electrodes 1006, 1007, 1008, a first interlayer insulating film 1020, a second interlayer insulating film 1021, a peripheral portion 1042, a pixel portion 1040, a driving circuit portion 1041, first electrodes 1024W, 1024R, 1024G, 1024B of the light-emitting element, a partition wall 1026, an EL layer 1028, a second electrode 1029 of the light-emitting element, a sealing substrate 1031, a sealant 1032, a red pixel 1044R, a green pixel 1044G, a blue pixel 1044B, a white pixel 1044W, etc.

[0236] exist Figure 7A In the embodiment, the colored layers (red colored layer 1034R, green colored layer 1034G, blue colored layer 1034B) are provided on the transparent substrate 1033. In addition, a black layer (black matrix) 1035 may be provided. The transparent substrate 1033 provided with the colored layers and the black layer is aligned and fixed to the substrate 1001. Note that the colored layers and the black layer are covered by the covering layer 1036. Figure 7A In this case, light emitted from some light-emitting layers does not pass through the colored layers, while light emitted from other light-emitting layers does. Since light that does not pass through the colored layers is white, and light that passes through any of the colored layers is red, blue, or green, an image can be displayed using pixels of four colors.

[0237] Figure 7B 1034R, the green colored layer 1034G, and the blue colored layer 1034B are formed between the gate insulating film 1003 and the first interlayer insulating film 1020. Figure 7B As shown, a coloring layer may be provided between the substrate 1001 and the sealing substrate 1031.

[0238] Although the light-emitting device described above has a structure in which light is extracted from the substrate 1001 side where the TFT is formed (bottom emission type), it may also have a structure in which light is extracted from the sealing substrate 1031 side (top emission type).

[0239] <Structural Example 2 of Light Emitting Device Figure 8A and Figure 8B These are all cross-sectional views of light-emitting devices with a top-emission structure. In this case, a substrate that does not transmit light can be used as substrate 1001. The processes up to the point of forming the connection electrode connecting the TFT to the anode of the light-emitting element are carried out in the same manner as for a light-emitting device with a bottom-emission structure. Next, a third interlayer insulating film 1037 is formed to cover the electrode 1022. This insulating film may also have a planarizing function. The third interlayer insulating film 1037 can be formed using the same material as the second interlayer insulating film 1021 or various other materials.

[0240] Although the lower electrodes 1025W, 1025R, 1025G, and 1025B of the light emitting element are all anodes here, they can also be cathodes. Figure 8A and Figure 8B In the light-emitting device with a top-emission structure shown, the lower electrodes 1025W, 1025R, 1025G, and 1025B are preferably reflective electrodes. Note that the second electrode 1029 preferably has the functions of both emitting and transmitting light. A microcavity structure is preferably used between the second electrode 1029 and the lower electrodes 1025W, 1025R, 1025G, and 1025B to amplify light of a specific wavelength. The EL layer 1028 is formed to have the same structure as described in Embodiments 1 and 2, and is selected to produce white light emission.

[0241] exist Figure 7A 、 Figure 7B as well as Figure 8A and Figure 8B In the embodiment of the present invention, a structure of an EL layer capable of obtaining white light emission can be realized by using multiple light-emitting layers or multiple light-emitting units. Note that the structure for obtaining white light emission is not limited to this.

[0242] In adopting Figure 8A and Figure 8B In the case of the top emission structure shown, sealing can be performed using a sealing substrate 1031 provided with colored layers (red colored layer 1034R, green colored layer 1034G, blue colored layer 1034B). The sealing substrate 1031 may also be provided with a black layer (black matrix) 1035 located between pixels. The colored layers (red colored layer 1034R, green colored layer 1034G, blue colored layer 1034B) and the black layer (black matrix) may also be covered with a capping layer. Note that a light-transmitting substrate is used as the sealing substrate 1031.

[0243] In addition, although Figure 8A The structure of full-color display with three colors of red, green and blue is shown in FIG. Figure 8B As shown, full-color display can also be performed using four colors: red, green, blue, and white. In addition, the structure for performing full-color display is not limited to these structures. For example, full-color display can also be performed using four colors: red, green, blue, and yellow.

[0244] A light-emitting element according to one embodiment of the present invention uses a fluorescent material as a guest material. Because fluorescent materials have a sharper spectrum than phosphorescent materials, they can produce light with high color purity. Therefore, by using this light-emitting element in the light-emitting device described in this embodiment, a light-emitting device with high color reproducibility can be obtained.

[0245] By the above method, a light-emitting device including the light-emitting element described in Embodiment Mode 1 and Embodiment Mode 2 can be obtained.

[0246] This embodiment mode can be combined with any other embodiment mode as appropriate.

[0247] (Implementation 4) In this embodiment, an electronic device and a display device according to one embodiment of the present invention are described.

[0248] According to one embodiment of the present invention, electronic devices and displays having a flat surface, high luminous efficiency, and high reliability can be manufactured. According to one embodiment of the present invention, electronic devices and displays having a curved surface, high luminous efficiency, and high reliability can be manufactured. The light-emitting element according to one embodiment of the present invention can emit light with high color purity. Therefore, by using this light-emitting element in the light-emitting device described in this embodiment, electronic devices and displays with high color reproducibility can be obtained.

[0249] Examples of electronic devices include televisions; desktop or notebook personal computers; displays for computers, etc.; digital cameras; digital video cameras; digital photo frames; mobile phones; portable game consoles; portable information terminals; audio reproducing devices; and large-scale game machines such as pinball machines.

[0250] Figure 9A and Figure 9B The illustrated portable information terminal 900 includes a housing 901 , a housing 902 , a display portion 903 , a hinge portion 905 , and the like.

[0251] The housing 901 and the housing 902 are connected together by a hinge portion 905. The portable information terminal 900 can be opened from a folded state ( Figure 9A ) is converted into Figure 9B As a result, the portability is good when carrying, and the visibility is high when using due to the large display area.

[0252] The portable information terminal 900 is provided with a flexible display portion 903 spanning a housing 901 and a housing 902 connected by a hinge portion 905 .

[0253] The light-emitting device manufactured using one embodiment of the present invention can be used for the display portion 903. Thus, the portable information terminal can be manufactured with high yield.

[0254] The display portion 903 can display at least one of document information, still images, and moving images, etc. When the document information is displayed on the display portion, the portable information terminal 900 can be used as an electronic book reader.

[0255] When the portable information terminal 900 is unfolded, the display portion 903 curves gently. For example, the display portion 903 can be held so as to include a portion curved with a radius of curvature of 1 mm to 50 mm, preferably 5 mm to 30 mm. Pixels are continuously arranged on a portion of the display portion 903, extending across the housing 901 and the housing 902, thereby enabling a curved display.

[0256] The display portion 903 is used as a touch panel and can be operated with a finger, a stylus pen, or the like.

[0257] The display unit 903 is preferably formed of a flexible display. Thus, a continuous display can be provided across the housing 901 and the housing 902. Alternatively, the housing 901 and the housing 902 may each be provided with a display.

[0258] To prevent the angle formed by the housing 901 and the housing 902 from exceeding a predetermined angle when the portable information terminal 900 is unfolded, the hinge portion 905 preferably has a locking mechanism. For example, the locking angle (at which further opening is impossible) is preferably greater than 90° and less than 180°, and typically can be 90°, 120°, 135°, 150°, or 175°. This improves the convenience, safety, and reliability of the portable information terminal 900.

[0259] When the hinge portion 905 has the above-described locking mechanism, it is possible to suppress application of excessive force to the display portion 903, thereby preventing damage to the display portion 903. Thus, a highly reliable portable information terminal can be realized.

[0260] Housing 901 and housing 902 may also include a power button, operation buttons, an external connection port, a speaker, a microphone, and the like.

[0261] One of the housing 901 and the housing 902 may be provided with a wireless communication module, and data can be sent and received via a computer network such as the Internet, a local area network (LAN), or Wireless Fidelity (Wi-Fi: a registered trademark).

[0262] Figure 9C The illustrated portable information terminal 910 includes a housing 911 , a display portion 912 , operation buttons 913 , an external connection port 914 , a speaker 915 , a microphone 916 , a camera 917 , and the like.

[0263] The light-emitting device manufactured using one embodiment of the present invention can be used for the display portion 912. Thus, the portable information terminal can be manufactured with high yield.

[0264] The portable information terminal 910 includes a touch sensor in the display portion 912. By touching the display portion 912 with a finger or a stylus pen, various operations such as making a call and inputting text can be performed.

[0265] Furthermore, by operating the operation button 913, it is possible to turn the power on and off or switch the type of image displayed on the display portion 912. For example, the e-mail composition screen can be switched to the main menu screen.

[0266] Furthermore, by providing a detection device such as a gyro sensor or an accelerometer within the portable information terminal 910, the orientation (portrait or landscape) of the portable information terminal 910 can be determined, and the screen display orientation of the display unit 912 can be automatically switched. Alternatively, the screen display orientation can be switched by touching the display unit 912, operating the operation button 913, or inputting a voice message using the microphone 916.

[0267] Portable information terminal 910, for example, has one or more functions selected from the group consisting of a telephone, a notebook, and an information reader. Specifically, portable information terminal 910 can be used as a smartphone. Portable information terminal 910 can execute various applications, such as mobile phone use, email, article reading and editing, music playback, video playback, network communication, and computer games.

[0268] Figure 9D The illustrated camera 920 includes a housing 921 , a display portion 922 , operation buttons 923 , a shutter button 924 , etc. In addition, the camera 920 is equipped with a detachable lens 926 .

[0269] The light-emitting device manufactured using one embodiment of the present invention can be used for the display portion 922. Thus, a highly reliable camera can be manufactured.

[0270] Here, although the camera 920 shown here has a structure in which the lens 926 can be detached from the housing 921 and replaced, the lens 926 and the housing 921 may be formed integrally.

[0271] The camera 920 can capture a still image or a moving image by pressing the shutter button 924. Alternatively, the display portion 922 may have a touch panel function so that the user can capture images by touching the display portion 922.

[0272] In addition, the camera 920 may further include a flash device and a viewfinder that are separately installed. In addition, these components may also be incorporated into the housing 921.

[0273] Figure 10A Schematic diagram showing an example of a sweeping robot.

[0274] The robot vacuum cleaner 5100 includes a display 5101 on the top surface, multiple cameras 5102 on the side, a brush 5103, and operation buttons 5104. Although not shown, the bottom surface of the robot vacuum cleaner 5100 is provided with tires and a suction port. Furthermore, the robot vacuum cleaner 5100 includes various sensors, including infrared sensors, ultrasonic sensors, acceleration sensors, piezoelectric sensors, optical sensors, and gyroscope sensors. Furthermore, the robot vacuum cleaner 5100 includes a wireless communication unit.

[0275] The sweeping robot 5100 can walk automatically, detect garbage 5120, and suck the garbage from the suction port on the bottom.

[0276] In addition, the cleaning robot 5100 can analyze the images captured by the camera 5102 to determine the presence of obstacles such as walls, furniture, or steps. In addition, if the image analysis detects objects such as wiring that may be entangled with the brush 5103, the rotation of the brush 5103 can be stopped.

[0277] The remaining battery power and the amount of garbage sucked in can be displayed on the display 5101. In addition, the walking path of the cleaning robot 5100 can also be displayed on the display 5101. In addition, the display 5101 can be a touch panel, and the operation button 5104 can be displayed on the display 5101.

[0278] The robot vacuum cleaner 5100 can communicate with a portable electronic device 5140, such as a smartphone. Images captured by the camera 5102 can be displayed on the portable electronic device 5140. Therefore, the owner of the robot vacuum cleaner 5100 can also know the status of the room when leaving the house. Furthermore, the owner can use the portable electronic device 5140, such as a smartphone, to confirm the display content of the display 5101.

[0279] The light-emitting device according to one embodiment of the present invention can be used for the display 5101 .

[0280] Figure 10B The robot 2100 shown includes a computing device 2110 , an illumination sensor 2101 , a microphone 2102 , an upper camera 2103 , a speaker 2104 , a display 2105 , a lower camera 2106 , an obstacle sensor 2107 , and a moving mechanism 2108 .

[0281] The microphone 2102 has a function of detecting the user's voice and surrounding sounds, etc. The speaker 2104 has a function of emitting sounds. The robot 2100 can communicate with the user using the microphone 2102 and the speaker 2104.

[0282] Display 2105 has the function of displaying various information. Robot 2100 can display user-desired information on display 2105. Display 2105 may be equipped with a touch panel. Display 2105 may be a detachable information terminal. By placing this information terminal at a predetermined location on robot 2100, it can be charged and transmit and receive data.

[0283] The upper camera 2103 and the lower camera 2106 have the function of capturing images of the surrounding environment of the robot 2100. Furthermore, the obstacle sensor 2107 can detect the presence of obstacles in front of the robot 2100 when the robot 2100 moves using the moving mechanism 2108. The robot 2100 can use the upper camera 2103, the lower camera 2106, and the obstacle sensor 2107 to recognize the surrounding environment and move safely.

[0284] The light-emitting device according to one embodiment of the present invention can be used for the display 2105 .

[0285] Figure 10C 1 is a diagram illustrating an example of a goggle-type display. The goggle-type display includes, for example, a housing 5000, a display portion 5001, a speaker 5003, an LED light 5004, operation keys 5005 (including a power switch or an operation switch), a connection terminal 5006, a sensor 5007 (capable of measuring factors such as force, displacement, position, velocity, acceleration, angular velocity, rotational speed, distance, light, liquid, magnetism, temperature, chemical substances, sound, time, hardness, electric field, current, voltage, power, radiation, flow rate, humidity, inclination, vibration, odor, or infrared light), a microphone 5008, a second display portion 5002, a support portion 5012, and headphones 5013.

[0286] The light-emitting device according to one embodiment of the present invention can be used for the display portion 5001 and the second display portion 5002 .

[0287] Figure 11A and Figure 11B The foldable portable information terminal 5150 is shown. The foldable portable information terminal 5150 includes a housing 5151, a display area 5152, and a bending portion 5153. Figure 11A The portable information terminal 5150 is shown in the unfolded state. Figure 11B The portable information terminal 5150 is shown in a folded state. Although the portable information terminal 5150 has a large display area 5152, by folding the portable information terminal 5150, the portable information terminal 5150 becomes smaller and more portable.

[0288] The display area 5152 can be folded in half by the curved portion 5153. The curved portion 5153 is composed of a retractable member and a plurality of supporting members. When folding, the retractable member is stretched so that the curved portion 5153 has a curvature radius of 2 mm or more, preferably 5 mm or more.

[0289] Alternatively, the display area 5152 may be a touch panel (input / output device) equipped with a touch sensor (input device). The light-emitting device according to one embodiment of the present invention can be used for the display area 5152 .

[0290] This embodiment mode can be appropriately combined with any other embodiment mode.

[0291] (Implementation 5) In this embodiment, referring to Figure 12 Examples of cases where the light-emitting element according to one embodiment of the present invention is applied to various lighting devices will be described. By using the light-emitting element according to one embodiment of the present invention, a lighting device with high luminous efficiency and reliability can be manufactured.

[0292] By forming the light-emitting element according to one embodiment of the present invention on a flexible substrate, it is possible to realize an electronic device or a lighting device having a light-emitting region on a curved surface.

[0293] Furthermore, a light-emitting device to which the light-emitting element according to one embodiment of the present invention is applied can also be applied to automobile lighting provided on a windshield, ceiling, or the like.

[0294] Figure 12 This is an example of using a light-emitting element in an indoor lighting device 8501. In addition, since the light-emitting element can be large-area, a large-area lighting device can also be formed. In addition, a lighting device 8502 having a curved light-emitting area can be formed by using a housing having a curved surface. The light-emitting element shown in this embodiment is in the form of a thin film, so the design freedom of the housing is high. Therefore, a lighting device that can correspond to various designs can be formed. In addition, a large lighting device 8503 can also be provided on the wall of the room. Touch sensors can also be provided in the lighting devices 8501, 8502, and 8503 to start or turn off the power.

[0295] Furthermore, by using light-emitting elements on the surface of a table, a lighting device 8504 having the function of a table can be provided. Furthermore, by using light-emitting elements on a part of other furniture, a lighting device having the function of furniture can be provided.

[0296] As described above, by applying the light-emitting element of one embodiment of the present invention, a lighting device and an electronic device can be obtained. Note that the lighting device and electronic device are not limited to those described in this embodiment, but can be applied to lighting devices and electronic devices in various fields.

[0297] The structure described in this embodiment can be implemented in combination with the structures described in other embodiment modes as appropriate. [Example 1]

[0298] In this embodiment, an example of manufacturing a light emitting element according to one embodiment of the present invention is described. The structure of each light emitting element manufactured in this embodiment is similar to that of the light emitting element. Figure 1A Similarly. Table 1 shows the details of the element structure. The structures and abbreviations of the compounds used are shown below. The structures and abbreviations of other compounds can refer to the above embodiment.

[0299]

[0300] [Table 1]

[0301] <Manufacturing of Light-Emitting Element> A method for manufacturing the light-emitting element manufactured in this embodiment will be described below.

[0302] <Manufacturing of Light-Emitting Element 1> As the electrode 101, a 70 nm thick ITSO film was formed on a glass substrate. The electrode area of ​​the electrode 101 was 4 mm 2 (2mm×2mm).

[0303] As the hole injection layer 111 , DBT3P-II and molybdenum oxide (MoO 3 ) were co-evaporated on the electrode 101 at a weight ratio (DBT3P-II:MoO 3 ) of 1:0.5 to a thickness of 40 nm.

[0304] Next, as the hole transport layer 112 , 9-[3-(9-phenyl-9H-fluoren-9-yl)phenyl]-9H-carbazole (abbreviated as mCzFLP) was deposited on the hole injection layer 111 to a thickness of 20 nm.

[0305] Next, as the light-emitting layer 130, 4PCCzBfpm, tris[2-(1H-pyrazol-1-yl-κN 2Co-evaporation of 10-(2-benzothiazolyl)-2,3,6,7-tetrahydro-1,1,7,7-tetramethyl-1H,5H,11H-[1]benzopyrano[6,7,8-ij]quinolizin-11-one (abbreviated as Coumarin 545T) was performed at a weight ratio of 0.8:0.2:0.005 (4PCCzBfpm:Ir(ppz)3:Coumarin 545T) to a thickness of 30 nm. In the light-emitting layer 130, Coumarin 545T is a fluorescent compound and Ir(ppz)3 is a phosphorescent compound.

[0306] Next, 4,6mCzP2Pm and NBPhen were sequentially deposited to a thickness of 20 nm on the light-emitting layer 130 as the electron transport layer 118. Next, LiF was deposited to a thickness of 1 nm on the electron transport layer 118 as the electron injection layer 119.

[0307] Next, aluminum (Al) was deposited to a thickness of 200 nm on the electron injection layer 119 as the electrode 102 .

[0308] Next, in a glove box with a nitrogen atmosphere, a sealing glass substrate was fixed to the glass substrate on which the organic material was formed using an organic EL sealant, thereby sealing the light-emitting element 1. Specifically, the sealant was applied around the organic material formed on the glass substrate, and the glass substrate and the sealing glass substrate were bonded together. 2 The film was irradiated with ultraviolet light having a wavelength of 365 nm and heated at 80° C. for 1 hour. The light-emitting element 1 was obtained through the above steps.

[0309] Manufacturing of Comparative Light-Emitting Element 2 The only difference between the light-emitting element 2 and the light-emitting element 1 is the process of forming the light-emitting layer 130 , while the other processes are manufactured using the same method as the light-emitting element 1 .

[0310] Comparative Light-Emitting Element 2 uses a co-evaporation method to form light-emitting layer 130 of 4PCCzBfpm and Ir(ppz)3 at a weight ratio of 0.8:0.2 (4PCCzBfpm:Ir(ppz)3) to a thickness of 30 nm. Comparative Light-Emitting Element 2 differs from Light-Emitting Element 1 in the presence or absence of the fluorescent compound; all other components are identical.

[0311] Manufacturing of Light-Emitting Element 3 The light emitting element 3 differs from the light emitting element 1 in the step of forming the light emitting layer 130 , while the other steps are manufactured using the same method as the light emitting element 1 .

[0312] As the light-emitting layer 130 of the light-emitting element 3, 4-[4-(9'-phenyl-3,3'-di-9H-carbazole-9-yl)phenyl]benzofurano[3,2-d]pyrimidine (abbreviated as: 4PCCzPBfpm), Ir(ppz)3, and coumarin 545T are co-evaporated in a weight ratio (4PCCzPBfpm:Ir(ppz)3:coumarin 545T) of 0.8:0.2:0.005 and a thickness of 30 nm.

[0313] Comparative Manufacturing of Light-Emitting Element 4 The only difference between the light emitting element 4 and the light emitting element 3 is the process of forming the light emitting layer 130 , while the other processes are manufactured using the same method as the light emitting element 3 .

[0314] Comparative Light-Emitting Element 4's light-emitting layer 130 was co-evaporated with 4PCCzPBfpm and Ir(ppz)₃ at a weight ratio (4PCCzPBfpm:Ir(ppz)₃) of 0.8:0.2, resulting in a thickness of 30 nm. Comparative Light-Emitting Element 4 differs from Light-Emitting Element 3 in the presence or absence of the fluorescent compound; all other components are identical.

[0315] Manufacturing of Comparative Light-Emitting Element 5 The only difference between the light-emitting element 5 and the light-emitting element 1 is the process of forming the light-emitting layer 130 and the process of forming the electron transport layer 118 . The other processes are manufactured using the same method as the light-emitting element 1 .

[0316] Comparative Light-Emitting Element 5's light-emitting layer 130 was co-evaporated with 4,4'-bis(9-carbazole)biphenyl (CBP), Ir(ppz)₃, and coumarin 545T at a weight ratio of 0.8:0.2:0.005 (CBP:Ir(ppz)₃:coumarin 545T) to a thickness of 30 nm. The difference between Comparative Light-Emitting Element 5 and Light-Emitting Element 1 lies in the host material; Comparative Light-Emitting Element 5 uses CBP, which is not a TADF material, as the host material.

[0317] Next, bathocuproin (BCP) was sequentially deposited to a thickness of 10 nm and NBPhen was subsequently deposited to a thickness of 15 nm on the light-emitting layer 130 as the electron transport layer 118 .

[0318] <Characteristics of Light-Emitting Element> Next, the characteristics of the manufactured Light-Emitting Elements 1 and 3 and Comparative Light-Emitting Elements 2, 4, and 5 were measured. Luminance and CIE chromaticity were measured using a colorimeter (BM-5A, manufactured by TOPCON TECHNOHOUSE). Electroemission spectra were measured using a multi-channel optical spectrum analyzer (PMA-11, manufactured by Hamamatsu Photonics Co., Ltd.).

[0319] Figure 13 The current efficiency-luminance characteristics of Light-Emitting Element 1, Light-Emitting Element 3, Comparative Light-Emitting Element 2, Comparative Light-Emitting Element 4, and Comparative Light-Emitting Element 5 are shown. Figure 14 Showing the current-voltage characteristics, Figure 15 The external quantum efficiency-brightness characteristics are shown. Figure 16 Shown at 2.5 mA / cm 2 Electroemission spectra when a current of a current density of 100 Å was passed through Light-Emitting Element 1, Light-Emitting Element 3, Comparative Light-Emitting Element 2, Comparative Light-Emitting Element 4, and Comparative Light-Emitting Element 5. The measurement of each light-emitting element was performed at room temperature (an atmosphere maintained at 23° C.).

[0320] Table 2 shows 1000 cd / m 2 Element characteristics of nearby light-emitting element 1, light-emitting element 3, comparative light-emitting element 2, comparative light-emitting element 4, and comparative light-emitting element 5.

[0321] [Table 2]

[0322] from Figure 16 It can be seen that the peak wavelength of the electroemission spectra of Light-emitting Element 1, Light-emitting Element 3, and Comparative Light-emitting Element 5 is 509 nm. This indicates that Light-emitting Element 1, Light-emitting Element 3, and Comparative Light-emitting Element 5 exhibit green light emission derived from the fluorescent compound coumarin 545T. Therefore, the peak wavelength of the electroemission spectra of Light-emitting Element 1 and Light-emitting Element 3 according to one embodiment of the present invention is shorter than that of Comparative Light-emitting Element 2 and Comparative Light-emitting Element 4, and the full width at half maximum of Light-emitting Element 1 and Light-emitting Element 3 is smaller than that of Comparative Light-emitting Element 2 and Comparative Light-emitting Element 4. Light-emitting Element 1 and Light-emitting Element 3 can exhibit light with higher color purity than that of Comparative Light-emitting Element 2 and Comparative Light-emitting Element 4. Therefore, the light-emitting element according to one embodiment of the present invention is suitable for use in a display device.

[0323] like Figure 13 、 Figure 15As shown in Table 2, light-emitting element 1 and light-emitting element 3 exhibit high luminous efficiency (current efficiency, power efficiency and external quantum efficiency). Here, the maximum generation probability of singlet excitons generated by the recombination of carriers (holes and electrons) injected from a pair of electrodes is 25%. Therefore, when the light extraction efficiency is assumed to be 25%, the maximum external quantum efficiency is 6.25%. Although light-emitting element 1 and light-emitting element 3 are fluorescent light-emitting elements, the external quantum efficiency is higher than 6.25%. This is because in addition to singlet excitons, in light-emitting element 1 and light-emitting element 3 according to one embodiment of the present invention, triplet excitons can also contribute to fluorescent light emission through the heavy atom effect derived from the phosphorescent compound Ir(ppz)3 and the anti-intersystem crossing generated by the TADF material.

[0324] Light-emitting element 1 and light-emitting element 3 have higher luminous efficiency than comparative light-emitting element 5. As described above, CBP, which is not a TADF material, is used in the light-emitting layer 130 of comparative light-emitting element 5. Therefore, comparative light-emitting element 5 does not have the function of converting triplet excitons into singlet excitons through anti-intersystem crossing generated by the TADF material. On the other hand, light-emitting element 1 and light-emitting element 3 according to one embodiment of the present invention contain a TADF material in the light-emitting layer 130. Therefore, light-emitting element 1 and light-emitting element 3 can convert triplet excitons into singlet excitons through anti-intersystem crossing, thereby achieving high luminous efficiency.

[0325] <Time-resolved luminescence measurement> Next, time-resolved luminescence measurement of Light-Emitting Element 1, Light-Emitting Element 3, Comparative Light-Emitting Element 2, and Comparative Light-Emitting Element 4 was performed.

[0326] In the measurement, a picosecond fluorescence lifetime measurement system (manufactured by Hamamatsu Photonics Co., Ltd., Japan) was used. In order to measure the lifetime of the fluorescence in the light-emitting element, a rectangular pulse voltage was applied to the light-emitting element, and a streak camera was used to perform time-resolved measurement of the luminescence that decayed after the voltage dropped. The pulse voltage was applied at a frequency of 10 Hz, and data with a high S / N ratio was obtained by accumulating the data of repeated measurements. In addition, the measurement was carried out under the following conditions: at room temperature (300 K), the brightness of the light-emitting element was 1000 cd / m 2 A pulse voltage of about 3V to 4V is applied in a near-zero manner, the applied pulse time width is 100μsec, the negative bias voltage is -5V (when the element is not driven), and the measurement time is 20μsec. Figure 17 The measurement results are shown. Figure 17 In the graph, the vertical axis represents the normalized intensity of the emission in a state where carrier injection is continuous (when a pulse voltage is applied), and the horizontal axis represents the time elapsed after the pulse voltage decreases.

[0327] like Figure 17As shown, the decay rate of the light emission of light-emitting element 1 and light-emitting element 3 is faster than that of comparative light-emitting element 2 and comparative light-emitting element 4. This indicates that in light-emitting element 1 and light-emitting element 3, the excitation energy is rapidly converted into light emission. Therefore, in the light-emitting layer, even in a state with a high exciton density (a state where a large amount of current flows), light emission can be efficiently extracted. Thus, as Figure 13 and Figure 15 shown, the attenuation (roll-off) of light-emitting element 1 and light-emitting element 3 is less. In addition, regarding the external quantum efficiency near 15000 cd / m 2 in the high-brightness region, the external quantum efficiency of light-emitting element 1 is 8.0%, that of comparative light-emitting element 2 is 7.3%, that of light-emitting element 3 is 4.8%, and that of comparative light-emitting element 4 is 4.2%. In other words, the efficiency of light-emitting element 1 is higher than that of comparative light-emitting element 2, and the efficiency of light-emitting element 3 is higher than that of comparative light-emitting element 4. Thus, less attenuation is one of the characteristics of the light-emitting element according to an embodiment of the present invention.

[0328] <CV measurement results> Next, the electrochemical properties (oxidation reaction properties and reduction reaction properties) of the materials for the light-emitting layer used in the above light-emitting element were measured using cyclic voltammetry (CV). In the measurement, an electrochemical analyzer (manufactured by BAS Inc., ALS model 600A or 600C) was used, and a solution obtained by dissolving each material in N,N-dimethylformamide (abbreviation: DMF) was measured. In the measurement, the potential of the working electrode relative to the reference electrode was changed within an appropriate range to obtain the oxidation peak potential and the reduction peak potential. In addition, since the redox potential of the reference electrode is estimated to be -4.94 eV, the HOMO energy level and the LUMO energy level of each compound were calculated from this value and the obtained peak potential.

[0329] The HOMO energy level of Ir(ppz)3 calculated by CV measurement is -5.39 eV, and the LUMO energy level is -1.77 eV. The HOMO energy level of 4PCCzBfpm is -5.70 eV, and the LUMO energy level is -2.84 eV. The HOMO energy level of 4PCCzPBfpm is -5.64 eV, and the LUMO energy level is -3.01 eV.

[0330] As described above, the LUMO energy level of 4PCCzBfpm and 4PCCzPBfpm is lower than that of Ir(ppz)3, while the HOMO energy level of Ir(ppz)3 is higher than that of 4PCCzBfpm and 4PCCzPBfpm. Therefore, when these compounds are used in the light-emitting layer, as in Light-Emitting Elements 1 and 3, electrons and holes, carriers injected from a pair of electrodes, are efficiently injected into 4PCCzBfpm or 4PCCzPBfpm and Ir(ppz)3, allowing 4PCCzBfpm and 4PCCzPBfpm to form exciplexes with Ir(ppz)3. Therefore, Light-Emitting Elements 1 and 3 can be said to utilize ExEF.

[0331] The LUMO energy level of the exciplex formed by 4PCCzBfpm and Ir(ppz)3 is located at 4PCCzBfpm, and the HOMO energy level is located at Ir(ppz)3. In addition, the energy difference between the LUMO energy level of 4PCCzBfpm and the HOMO energy level of Ir(ppz)3 is 2.55 eV. This value is consistent with the Figure 16 The luminescence energy (2.42 eV) calculated from the peak wavelength of the emission spectrum of Comparative Light-Emitting Element 2 is substantially consistent. This indicates that the emission spectrum of Comparative Light-Emitting Element 2 corresponds to luminescence from an exciplex formed from 4PCCzBfpm and Ir(ppz)3. Note that the difference between the S1 and T1 levels of the exciplex is small, so the luminescence energy can be interpreted as the energy of the S1 and T1 levels of the exciplex (2.42 eV).

[0332] Similarly, the LUMO energy level of the exciplex formed by 4PCCzPBfpm and Ir(ppz)3 is located at 4PCCzPBfpm, and the HOMO energy level is located at Ir(ppz)3. In addition, the energy difference between the LUMO energy level of 4PCCzPBfpm and the HOMO energy level of Ir(ppz)3 is 2.38 eV. This value is consistent with the Figure 16 The emission energy (2.30 eV) calculated from the peak wavelength of the emission spectrum of Comparative Light-Emitting Element 4 is substantially consistent. This indicates that the emission spectrum of Comparative Light-Emitting Element 4 corresponds to an exciplex formed from 4PCCzPBfpm and Ir(ppz)3. Note that the difference between the S1 and T1 levels of the exciplex is small, so the emission energy can be considered to be the energy of the S1 and T1 levels of the exciplex (2.30 eV).

[0333] <Relationship between the Emission Spectrum of the Exciplex and the Absorption Spectrum of the Guest Material> Figure 18The results of measuring the absorption spectrum of a toluene solution of coumarin 545T and comparing the emission spectra of the exciplexes of light-emitting element 2 and light-emitting element 4 are shown. The absorption spectrum was measured at room temperature (in an atmosphere maintained at 23 °C) using an ultraviolet-visible spectrophotometer (model V550, manufactured by JASCO Corporation).

[0334] As Figure 18 shown, the absorption spectrum of coumarin 545T partially overlaps with the emission spectra of the exciplexes of light-emitting element 2 and light-emitting element 4. Therefore, the excitation energy is efficiently supplied from the exciplex formed by 4PCCzBfpm and Ir(ppz)3 and the exciplex formed by 4PCCzPBfpm and Ir(ppz)3 to the fluorescent compound coumarin 545T. Thus, like light-emitting elements 1 and 3 having the electroluminescence spectrum Figure 16 shown, a light-emitting element that emits light having a peak wavelength shorter than the electroluminescence spectrum of the exciplex can be provided.

[0335] <Measurement of T1 Energy Level> Next, the T1 energy levels of 4PCCzBfpm and 4PCCzPBfpm were determined. The measurement method will be described later. As a result, the T1 energy level of 4PCCzBfpm was 2.58 eV, and the T1 energy level of 4PCCzPBfpm was 2.46 eV.

[0336] To estimate the T1 energy level of Ir(ppz)3, the absorption spectrum and emission spectrum were measured. A dichloromethane solution in which Ir(ppz)3 was dissolved was prepared, and the absorption spectrum was measured using a quartz cell. The absorption spectrum was measured using an ultraviolet-visible spectrophotometer (model V550, manufactured by JASCO Corporation). The absorption spectra of the quartz cell and the solvent were subtracted from the spectrum of the measured sample. The above measurement was carried out at room temperature (in an atmosphere maintained at 23 °C).

[0337] The absorption edge was obtained from the data of the above absorption spectrum, and the transition energy assuming a direct transition was estimated. As a result, the transition energy of Ir(ppz)3 was estimated to be 3.27 eV. Since Ir(ppz)3 is a phosphorescent compound, the absorption band at the lowest energy side is an absorption band based on the transition of the triplet excited state. Thus, the T1 energy level of Ir(ppz)3 calculated from this absorption edge was 3.27 eV.

[0338] From the above measurement results, it can be seen that the T1 energy level of 4PCCzBfpm (2.58eV) and the T1 energy level of 4PCCzPBfpm (2.46eV) are lower than the T1 energy level of Ir(ppz)3 (3.27eV), and the T1 energy level of 4PCCzBfpm (2.58eV) and the T1 energy level of 4PCCzPBfpm (2.46eV) are higher than the T1 energy level of the excited complex formed by 4PCCzBfpm and Ir(ppz)3 (2.42eV) and the T1 energy level of the excited complex formed by 4PCCzPBfpm and Ir(ppz)3 (2.30eV). Therefore, the triplet excitation energy of the exciplex formed by 4PCCzBfpm and Ir(ppz)3 is not inactivated by 4PCCzBfpm or Ir(ppz)3, and the triplet excitation energy of the exciplex formed by 4PCCzPBfpm and Ir(ppz)3 is not inactivated by 4PCCzPBfpm or Ir(ppz)3. As a result, the triplet excitation energy of the exciplex can be converted into luminescence, converted into singlet excitation energy via antisystem crossing, or transferred to a fluorescent compound.

[0339] Although the emission spectrum of Ir(ppz)3 was measured at room temperature, no luminescence was observed. Non-Patent Document 1 discloses that the quantum yield of Ir(ppz)3 at room temperature is less than 1%. This suggests that Ir(ppz)3 is a non-luminescent material at room temperature. This suggests that even using compounds with a quantum yield of less than 1%, it is possible to produce light-emitting devices with high luminescence efficiency.

[0340] <Transition Fluorescence Characteristics of Host Materials> Here, in order to confirm whether 4PCCzBfpm and 4PCCzPBfpm used in Light-Emitting Element 1 and Light-Emitting Element 3, respectively, are TADF materials, the transient fluorescence characteristics are measured by time-resolved luminescence measurement.

[0341] Time-resolved luminescence measurement was performed on a thin film sample co-deposited on a quartz substrate with bis[2-(diphenylphosphinoyl)phenyl]ether (abbreviated as: DPEPO) and 4PCCzPBfpm in a weight ratio (DPEPO:4PCCzPBfpm) of 0.8:0.2 and a thickness of 50 nm, and a thin film sample co-deposited on a quartz substrate with a weight ratio (DPEPO:4PCCzBfpm) of 0.8:0.2 and a thickness of 50 nm.

[0342] In the measurement, a picosecond fluorescence lifetime measurement system (manufactured by Hamamatsu Photonics K.K., Japan) was used. To measure the fluorescence lifetime of the thin film, pulsed laser was irradiated onto the thin film, and the luminescence that decayed after the laser irradiation was measured with a streak camera in a time-resolved manner. As the pulsed laser, a nitrogen gas laser with a wavelength of 337 nm was used, and pulsed laser of 500 ps was irradiated onto the thin film at a frequency of 10 Hz, and data with a high S / N ratio was obtained by accumulating the repeatedly measured data. Note that the measurement was carried out at room temperature (atmosphere maintained at 23 °C).

[0343] Figure 19A and Figure 19B shows the transient fluorescence characteristics of 4PCCzBfpm obtained by the measurement. Figure 19A is the measurement result of the luminescent component with a short luminescence lifetime,[[]] Figure 19B is the measurement result of the luminescent component with a long luminescence lifetime. The transient fluorescence characteristics of 4PCCzPBfpm are not shown in the drawings. 4PCCzPBfpm was measured and calculated in the same manner as 4PCCzBfpm.

[0344] The following formula 4 was used for Figure 19A and Figure 19B the decay curves shown for fitting.

[0345] [Formula 4]

[0346] In formula 4, L represents the normalized luminescence intensity, and t represents the elapsed time. From the fitting results of the decay curves, it can be seen that the light emitted from the thin film samples of 4PCCzBfpm and 4PCCzPBfpm contains multiple luminescent components with different fluorescence lifetimes. It can be seen that the luminescent components of the thin film sample of 4PCCzBfpm at least include an instantaneous fluorescence component with a fluorescence lifetime of 11.7 ns and a delayed fluorescence component with the longest lifetime of 217 μs. The luminescent components of the thin film sample of 4PCCzPBfpm at least include an instantaneous fluorescence component of 11.0 ns and a delayed fluorescence component with the longest lifetime of 301 μs. That is, 4PCCzBfpm and 4PCCzPBfpm are thermally activated delayed fluorescence materials that exhibit delayed fluorescence at room temperature.

[0347] <Measurement of S1 energy level and T1 energy level> In order to efficiently generate reverse intersystem crossing and exhibit thermally activated delayed fluorescence, the energy difference between the S1 energy level and the T1 energy level is preferably greater than 0 eV and 0.3 eV or less, more preferably greater than 0 eV and 0.2 eV or less. Next, calculations for measuring the S1 energy level and the T1 energy level of 4PCCzBfpm and 4PCCzPBfpm were carried out.

[0348] In order to calculate the S1 level and the T1 level, the emission spectra of 4PCCzBfpm and 4PCCzPBfpm were measured. Figure 20 The measurement results of the emission spectrum of 4PCCzBfpm are shown. Figure 21 The measurement results of the emission spectrum of 4PCCzPBfpm are shown.

[0349] The emission spectrum was measured using a LabRAM HR-PL microscope (manufactured by Horiba, Ltd.) at a measurement temperature of 10 K. He-Cd laser light (325 nm) was used as the excitation light, and a CCD detector was used as the detector. A 50 nm thick thin film was formed on a quartz substrate, and another quartz substrate was bonded to the vapor-deposited surface of the quartz substrate in a nitrogen atmosphere for measurement.

[0350] Furthermore, in addition to the general emission spectrum measurement, the emission spectrum measurement was also performed using a time-resolved emission spectrum focusing on luminescence with a long luminescence lifetime. Since both emission spectrum measurements were performed at a low temperature (10K), the general emission spectrum measurement observed phosphorescence in addition to fluorescence, which is the main luminescence component. Furthermore, the time-resolved emission spectrum measurement focusing on luminescence with a long luminescence lifetime primarily observed phosphorescence.

[0351] The emission spectrum measurements above show that the wavelengths of the peaks (including the shoulder peak) on the shortest wavelength side of the fluorescence and phosphorescence components of the emission spectrum of 4PCCzBfpm are 455 nm and 480 nm, respectively. Furthermore, the wavelengths of the peaks (including the shoulder peak) on the shortest wavelength side of the fluorescence and phosphorescence components of the emission spectrum of 4PCCzPBfpm are 480 nm and 505 nm, respectively.

[0352] Therefore, the S1 level of 4PCCzBfpm calculated from the wavelengths of the peaks (including the shoulder) is 2.72 eV, the T1 level is 2.58 eV, and the energy difference between the S1 and T1 levels is 0.14 eV. Furthermore, the S1 level of 4PCCzPBfpm is 2.58 eV, and the T1 level is 2.46 eV, with an energy difference between the S1 and T1 levels of 0.12 eV.

[0353] The emission spectrum measurements above show that the wavelengths of the short-wavelength rise of the fluorescent and phosphorescent components of the 4PCCzBfpm emission spectrum are 435 nm and 464 nm, respectively. The wavelengths of the short-wavelength rise of the fluorescent and phosphorescent components of the 4PCCzPBfpm emission spectrum are 458 nm and 491 nm, respectively. The wavelength of the short-wavelength rise of the emission spectrum is the wavelength of the intersection of the tangent line and the horizontal axis at the wavelength where the inclination of the tangent line of the spectrum reaches a maximum.

[0354] The S1 level of 4PCCzBfpm calculated from the rising wavelength as described above is 2.85 eV, the T1 level is 2.67 eV, and the energy difference between the S1 and T1 levels is 0.18 eV. The S1 level of 4PCCzPBfpm is 2.71 eV, the T1 level is 2.53 eV, and the energy difference between the S1 and T1 levels is 0.18 eV.

[0355] As described above, the energy difference between the S1 and T1 levels of 4PCCzPBfpm and 4PCCzBfpm, calculated from the wavelength of the peak (including the shoulder) on the shortest wavelength side of the emission spectrum or the wavelength of the short-wavelength rise, is extremely small, i.e., greater than 0 eV and less than 0.2 eV. Therefore, 4PCCzPBfpm and 4PCCzBfpm have the function of converting triplet excitation energy into singlet excitation energy through anti-intersystem crossing, thereby exhibiting thermally activated delayed fluorescence.

[0356] <Reliability of Light-Emitting Element> Figure 22 The results of the driving test when the constant current of the light-emitting element 1, the comparative light-emitting element 2, the light-emitting element 3, the comparative light-emitting element 4 and the comparative light-emitting element 5 was 0.5 mA are shown. Figure 22 It can be seen that the reliability of light-emitting element 1 is higher than that of comparative light-emitting element 2, and the reliability of light-emitting element 3 is higher than that of comparative light-emitting element 4. The difference between light-emitting element 1 and comparative light-emitting element 2 and the difference between light-emitting element 3 and comparative light-emitting element 4 is the presence or absence of a fluorescent compound. As described above, light-emitting element 1 and light-emitting element 3 can obtain light-emitting derived from a fluorescent compound, and light-emitting element 2 and comparative light-emitting element 4 can obtain light-emitting derived from an exciplex. Therefore, it can be seen that when light-emitting is obtained from a fluorescent compound as in the light-emitting element of one embodiment of the present invention, reliability is improved. In addition, it can be seen that the reliability of light-emitting element 1 and light-emitting element 3 is higher than that of comparative light-emitting element 5. By using a host material having TADF properties, a highly reliable light-emitting element can be obtained. [Example 2]

[0357] In this embodiment, a light emitting element according to one embodiment of the present invention and a comparative light emitting element are described. The structure of each light emitting element manufactured in this embodiment is similar to that of the light emitting element. Figure 1A Similarly. Table 3 shows the details of the element structure. The structures and abbreviations of the compounds used are shown below. The structures and abbreviations of other compounds can refer to Example 1 and the above-mentioned embodiment.

[0358]

[0359] [Table 3]

[0360] <Manufacturing of Light-Emitting Element> A method for manufacturing the light-emitting element manufactured in this embodiment will be described below.

[0361] Manufacturing of Light-Emitting Element 6 As the electrode 101, a 70 nm thick ITSO film was formed on a glass substrate. The electrode area of ​​the electrode 101 was 4 mm 2 (2mm×2mm).

[0362] Next, as the hole injection layer 111 , DBT3P-II and molybdenum oxide (MoO 3 ) were co-evaporated on the electrode 101 at a weight ratio (DBT3P-II:MoO 3 ) of 1:0.5 to a thickness of 45 nm.

[0363] Next, PCBBi1BP was deposited on the hole injection layer 111 to a thickness of 20 nm as the hole transport layer 112 .

[0364] Next, as the light-emitting layer 130, 4PCCzBfpm, GD270 (manufactured by Jilin Aolaide Optoelectronic Materials Co., Ltd.), and 2,8-di-tert-butyl-5,11-bis(4-tert-butylphenyl)-6,12-diphenyltetracene (TBRb) were co-evaporated on the hole-transporting layer 112 at a weight ratio (4PCCzBfpm:GD270:TBRb) of 0.8:0.2:0.01 to a thickness of 40 nm. In the light-emitting layer 130, GD270 is a phosphorescent compound, and TBRb is a fluorescent compound.

[0365] Next, 4,6mCzP2Pm and NBPhen were sequentially deposited to a thickness of 20 nm on the light-emitting layer 130 as the electron transport layer 118. Next, LiF was deposited to a thickness of 1 nm on the electron transport layer 118 as the electron injection layer 119.

[0366] Next, aluminum (Al) was deposited to a thickness of 200 nm on the electron injection layer 119 as the electrode 102 .

[0367] Next, in a glove box with a nitrogen atmosphere, a sealing glass substrate was fixed to the glass substrate on which the organic material was formed using an organic EL sealant, thereby sealing the light-emitting element 6. Specifically, the sealant was applied around the organic material formed on the glass substrate, and the glass substrate and the sealing glass substrate were bonded together. 2The film was irradiated with ultraviolet light having a wavelength of 365 nm and heated at 80° C. for 1 hour. A light-emitting element 6 was obtained through the above steps.

[0368] Manufacturing of Comparative Light-Emitting Element 7 The only difference between the light-emitting element 7 and the light-emitting element 6 is the process of forming the light-emitting layer 130 , while the other processes are manufactured using the same method as the light-emitting element 6 .

[0369] Comparative Light-Emitting Element 7 used co-evaporation to form light-emitting layer 130 of 4PCCzBfpm and GD270 at a weight ratio (4PCCzBfpm:GD270) of 0.8:0.2 to a thickness of 40 nm. Unlike light-emitting layer 130 of light-emitting element 6, light-emitting layer 130 of comparative light-emitting element 7 did not contain the fluorescent compound TBRb.

[0370] Comparative Manufacturing of Light-Emitting Element 8 As the electrode 101, a 70 nm thick ITSO film was formed on a glass substrate. The electrode area of ​​the electrode 101 was 4 mm 2 (2mm×2mm).

[0371] As the hole injection layer 111 , DBT3P-II and molybdenum oxide (MoO 3 ) were co-evaporated on the electrode 101 at a weight ratio (DBT3P-II:MoO 3 ) of 1:0.5 and a thickness of 45 nm.

[0372] Next, mCzFLP was vapor-deposited on the hole injection layer 111 to a thickness of 20 nm as the hole transport layer 112 .

[0373] Next, CBP, GD270, and TBRb were co-evaporated on the hole-transport layer 112 to form the light-emitting layer 130 at a weight ratio (CBP:GD270:TBRb) of 0.8:0.2:0.01, with a thickness of 30 nm. The difference between the light-emitting layer 130 of Light-Emitting Element 6 and Comparative Light-Emitting Element 8 lies in the host material. Light-Emitting Element 6 was manufactured using a TADF material, while Comparative Light-Emitting Element 8 was manufactured using CBP, which is not a TADF material.

[0374] Next, bathocuproin (BCP) was deposited to a thickness of 10 nm and NBPhen to a thickness of 15 nm on the light-emitting layer 130 as the electron-transporting layer 118. Next, LiF was deposited to a thickness of 1 nm on the electron-transporting layer 118 as the electron-injecting layer 119.

[0375] Next, aluminum (Al) was deposited to a thickness of 200 nm on the electron injection layer 119 as the electrode 102 .

[0376] Next, in a glove box with a nitrogen atmosphere, a sealing glass substrate was fixed to a glass substrate on which an organic material was formed using an organic EL sealant, thereby sealing the comparative light-emitting element 8. Specifically, the sealant was applied around the organic material formed on the glass substrate, and the glass substrate and the sealing glass substrate were bonded together. 2 The film was irradiated with ultraviolet light having a wavelength of 365 nm and heated at 80° C. for 1 hour. A comparative light-emitting element 8 was obtained through the above steps.

[0377] Manufacturing of Comparative Light-Emitting Element 9 The only difference between the comparative light-emitting element 9 and the comparative light-emitting element 8 is the formation process of the light-emitting layer 130 and the electron transport layer 118 , while the other steps are the same as those of the comparative light-emitting element 8 .

[0378] Comparative Light-Emitting Element 9's light-emitting layer 130 was co-evaporated with bis[2-(diphenylphosphinoyl)phenyl]ether (DPEPO), 4PCCzBfpm, and TBRb at a weight ratio of 0.8:0.2:0.01 (DPEPO:4PCCzBfpm:TBRb) to a thickness of 30 nm. Unlike light-emitting layer 130 of light-emitting element 6, light-emitting layer 130 of comparative light-emitting element 9 did not contain a phosphorescent compound.

[0379] Next, as the electron transport layer 118 , DPEPO was evaporated to a thickness of 5 nm on the light emitting layer 130 , and 1,3,5-tris[3-(3-pyridyl)phenyl]benzene (abbreviated as TmPyPB) was evaporated to a thickness of 20 nm.

[0380] <Characteristics of Light-Emitting Element> Next, the characteristics of the light-emitting element 6 and comparative light-emitting elements 7 to 9 manufactured as described above were measured. Note that the measurement method was the same as that of Example 1.

[0381] Figure 23 The current efficiency-luminance characteristics of Light-Emitting Element 6 and Comparative Light-Emitting Element 7 to Comparative Light-Emitting Element 9 are shown. Figure 24 Showing the current-voltage characteristics, Figure 25 The external quantum efficiency-luminance characteristics are shown. Figure 26 Shown at 2.5 mA / cm 2 Electroemission spectra when a current of a current density of 100 Å was passed through Light-Emitting Element 6 and Comparative Light-Emitting Element 7 to Comparative Light-Emitting Element 9. The measurement of each light-emitting element was performed at room temperature (an atmosphere maintained at 23° C.).

[0382] In addition, Table 4 shows that 1000 cd / m 2 Element characteristics of the nearby light-emitting element 6 and comparative light-emitting elements 7 to 9.

[0383] [Table 4]

[0384] like Figure 26 As shown, the peak wavelengths of the emission spectra of light-emitting element 6, comparative light-emitting element 8 and comparative light-emitting element 9 are 565 nm, 562 nm and 561 nm, respectively, and the full width at half maximum is about 72 nm, 67 nm and 69 nm, respectively. This means that light-emitting element 6, comparative light-emitting element 8 and comparative light-emitting element 9 emit yellow light. Therefore, the light emitted by light-emitting element 6, comparative light-emitting element 8 and comparative light-emitting element 9 comes from the fluorescent compound TBRb. In addition, the peak wavelength of the emission spectrum of comparative light-emitting element 7 is 528 nm, and the full width at half maximum is 76 nm. This means that comparative light-emitting element 7 emits green light. Therefore, the light emitted by comparative light-emitting element 7 comes from GD270. Therefore, the full width at half maximum of the peak wavelength of the emission spectrum of light-emitting element 6 of one embodiment of the present invention is smaller than that of comparative light-emitting element 7, and light-emitting element 6 can emit light with higher color purity than that of comparative light-emitting element 7. Therefore, the light-emitting element of one embodiment of the present invention is suitable for use in a display device.

[0385] like Figure 23 and Figure 25 As shown in Table 4, although Light-Emitting Element 6 is a fluorescent light-emitting element, its external quantum efficiency exceeds the maximum external quantum efficiency of 6.25% for a fluorescent light-emitting element. This is because, in Light-Emitting Element 6 according to one embodiment of the present invention, in addition to singlet excitons, triplet excitons can also contribute to fluorescent emission via the phosphorescent compound GD270. Furthermore, as mentioned above, 4PCCzBfpm contained in Light-Emitting Element 6 is a TADF material. Therefore, triplet excitons can contribute to fluorescent emission through anti-intersystem crossing generated by the TADF material, thereby improving the luminous efficiency.

[0386] Light-emitting element 6 has a higher luminous efficiency than comparative light-emitting element 8. As described above, CBP, which is not a TADF material, is used in the light-emitting layer 130 of comparative light-emitting element 8. Therefore, comparative light-emitting element 8 does not have the function of converting triplet excitons into singlet excitons through anti-intersystem crossing caused by the TADF material. On the other hand, light-emitting element 6 according to one embodiment of the present invention includes a TADF material in the light-emitting layer 130. Therefore, in light-emitting element 6, triplet excitons can be converted into singlet excitons through anti-intersystem crossing caused by the TADF material, and a higher luminous efficiency than that of comparative light-emitting element 8 can be achieved.

[0387] The luminous efficiency of light-emitting element 6 is higher than that of comparative light-emitting element 9. As described above, the light-emitting layer 130 of comparative light-emitting element 9 contains a TADF material but does not contain a phosphorescent compound. Therefore, comparative light-emitting element 9 cannot contribute triplet excitons to fluorescent light emission through the phosphorescent compound. On the other hand, light-emitting element 6 according to one embodiment of the present invention contains a phosphorescent compound in addition to the TADF material in the light-emitting layer 130. Therefore, in light-emitting element 6, in addition to the high efficiency effect of anti-intersystem crossing generated by the TADF material, triplet excitons can also be contributed to fluorescent light emission through the phosphorescent compound, thereby achieving a luminous efficiency higher than that of comparative light-emitting element 9.

[0388] <Time-resolved luminescence measurement> Next, time-resolved luminescence measurement of the light-emitting element 6 and the comparative light-emitting element 7 was performed. Figure 27 The measurement method was the same as that described in Example 1.

[0389] like Figure 27 As shown in FIG, the decay rate of the luminescence of the light emitting element 6 is faster than that of the comparative light emitting element 7. This means that in the light emitting element 6, the excitation energy is quickly converted into luminescence, so that even in the state of high exciton density (state where a large amount of current flows) in the light emitting layer, luminescence can be efficiently extracted. Figure 23 and Figure 25 As shown in FIG. 1 , the attenuation of the light emitting element 6 is small. The light emitting efficiency of the light emitting element 6 is higher than that of the comparative light emitting element 7. The light emitting layer 130 of the light emitting element 6 has a structure in which the fluorescent compound TBRb is added to the light emitting layer of the comparative light emitting element 7. Figure 27 It is found that the addition of the fluorescent compound increases the decay rate of luminescence, thereby suppressing the deactivation of excitons and improving the luminous efficiency of Light-Emitting Element 6 compared to Comparative Light-Emitting Element 7.

[0390] <Reliability of Light-Emitting Element> Figure 28 The results of the driving test when the constant current of the light-emitting element 6, the comparative light-emitting element 7, and the comparative light-emitting element 8 was 2.0 mA are shown. Figure 28 It can be seen that the reliability of light-emitting element 6 is higher than that of comparative light-emitting element 7. The difference between light-emitting element 6 and comparative light-emitting element 7 is the presence or absence of a fluorescent compound. As described above, light-emitting element 6 obtains light emission from a fluorescent compound, while comparative light-emitting element 7 obtains light emission from a phosphorescent compound. Therefore, it can be seen that when light emission is obtained from a fluorescent compound as in the light-emitting element of one embodiment of the present invention, reliability is improved. In addition, it can be seen that the reliability of light-emitting element 6 is higher than that of comparative light-emitting element 8. By using a host material having TADF properties, a highly reliable light-emitting element can be obtained. [Example 3]

[0391] In this embodiment, a light emitting element according to one embodiment of the present invention and a comparative light emitting element are described. The structure of each light emitting element manufactured in this embodiment is similar to that of the light emitting element. Figure 1A Similarly. Table 5 shows the details of the element structure. The structures and abbreviations of the compounds used are shown below. The structures and abbreviations of other compounds can refer to the above examples and implementation methods.

[0392]

[0393] [Table 5]

[0394] <Manufacturing of Light-Emitting Element> A method for manufacturing the light-emitting element manufactured in this embodiment will be described below.

[0395] <Manufacturing of Light-Emitting Element 10> As the electrode 101, a 70 nm thick ITSO film was formed on a glass substrate. The electrode area of ​​the electrode 101 was 4 mm 2 (2mm×2mm).

[0396] As the hole injection layer 111 , DBT3P-II and molybdenum oxide (MoO 3 ) were co-evaporated on the electrode 101 at a weight ratio (DBT3P-II:MoO 3 ) of 1:0.5 and a thickness of 45 nm.

[0397] Next, PCBBi1BP was deposited on the hole injection layer 111 to a thickness of 20 nm as the hole transport layer 112 .

[0398] Next, PCCzPTzn, GD270 (manufactured by Jilin Aolaide Optoelectronic Materials Co., Ltd.), and TBRb were co-evaporated onto the hole-transport layer 112 to form the light-emitting layer 130. PCCzPTzn, GD270, and TBRb were deposited at a weight ratio of 0.8:0.2:0.01 (PCCzPTzn:GD270:TBRb) to a thickness of 40 nm. In the light-emitting layer 130, GD270 is a phosphorescent compound, and TBRb is a fluorescent compound.

[0399] Next, PCCzPTzn and NBPhen were sequentially deposited to a thickness of 20 nm and 10 nm on the light-emitting layer 130 as the electron transport layer 118. Next, LiF was deposited to a thickness of 1 nm on the electron transport layer 118 as the electron injection layer 119.

[0400] Next, aluminum (Al) was deposited to a thickness of 200 nm on the electron injection layer 119 as the electrode 102 .

[0401] Next, in a glove box with a nitrogen atmosphere, a sealing glass substrate was fixed to the glass substrate on which the organic material was formed using an organic EL sealant, thereby sealing the light-emitting element 10. Specifically, the sealant was applied around the organic material formed on the glass substrate, and the glass substrate and the sealing glass substrate were bonded together. 2 The device was irradiated with ultraviolet light having a wavelength of 365 nm and heated at 80° C. for 1 hour. The light-emitting element 10 was obtained through the above steps.

[0402] Manufacturing of Comparative Light-Emitting Element 11 The comparison light emitting element 11 differs from the light emitting element 10 only in the process of forming the light emitting layer 130 , while the other processes are manufactured using the same method as the light emitting element 10 .

[0403] As light-emitting layer 130 of comparative light-emitting element 11, PCCzPTzn and GD270 were co-evaporated at a weight ratio (PCCzPTzn:GD270) of 0.8:0.2 to a thickness of 40 nm. Unlike light-emitting layer 130 of light-emitting element 10, light-emitting layer 130 of comparative light-emitting element 11 did not contain the fluorescent compound TBRb.

[0404] Comparative Manufacturing of Light-Emitting Element 12 The only difference between the comparative light-emitting element 12 and the light-emitting element 10 is the process of forming the hole transport layer 112 and the light-emitting layer 130 . The other processes are manufactured using the same method as the light-emitting element 10 .

[0405] As the hole transport layer 112 of the comparative light-emitting element 12 , PCCP was deposited on the hole injection layer 111 to a thickness of 20 nm.

[0406] Next, PCCzPTzn and TBRb were co-evaporated at a weight ratio (PCCzPTzn:TBRb) of 1:0.01 to a thickness of 30 nm as the light-emitting layer 130. Unlike the light-emitting layer 130 of the light-emitting element 10, the light-emitting layer 130 of the comparative light-emitting element 12 did not contain the phosphorescent compound GD270.

[0407] <Characteristics of Light-Emitting Element> Next, the characteristics of the light-emitting element 10, comparative light-emitting element 11, comparative light-emitting element 12, and comparative light-emitting element 8 manufactured as described above were measured. Note that the measurement method was the same as that of Example 1.

[0408] Figure 29 The current efficiency-luminance characteristics of the light-emitting element 10, the comparative light-emitting element 11, the comparative light-emitting element 12, and the comparative light-emitting element 8 are shown. Figure 30Showing the current-voltage characteristics, Figure 31 The external quantum efficiency-brightness characteristics are shown. Figure 32 Shown at 2.5 mA / cm 2 Electroemission spectra when a current of a current density of 100 Å was passed through Light-Emitting Element 10, Comparative Light-Emitting Element 11, Comparative Light-Emitting Element 12, and Comparative Light-Emitting Element 8. The measurement of each light-emitting element was performed at room temperature (an atmosphere maintained at 23° C.).

[0409] Table 6 shows 1000 cd / m 2 Element characteristics of the nearby light-emitting element 10 , the comparative light-emitting element 11 , and the comparative light-emitting element 12 .

[0410] [Table 6]

[0411] like Figure 32 As shown, the peak wavelengths of the emission spectra of light-emitting element 10, comparative light-emitting element 8 and comparative light-emitting element 12 are 566 nm, 562 nm and 560 nm, respectively, and the full width at half maximum is about 74 nm, 67 nm and 69 nm, respectively. This means that light-emitting element 10, comparative light-emitting element 8 and comparative light-emitting element 12 emit yellow light. Therefore, the light emitted by light-emitting element 10, comparative light-emitting element 8 and comparative light-emitting element 12 comes from the fluorescent compound TBRb. In addition, the peak wavelength of the emission spectrum of comparative light-emitting element 11 is 533 nm, and the full width at half maximum is 78 nm. This means that comparative light-emitting element 11 emits green light. Therefore, the light emitted by comparative light-emitting element 11 comes from GD270. Therefore, the full width at half maximum of the peak wavelength of the emission spectrum of light-emitting element 10 of one embodiment of the present invention is smaller than that of comparative light-emitting element 11, and light-emitting element 10 can emit light with higher color purity than that of comparative light-emitting element 11. Therefore, the light-emitting element of one embodiment of the present invention is suitable for use in a display device.

[0412] like Figure 29 、 Figure 31 As shown in Table 6, although light-emitting element 10 is a fluorescent light-emitting element, its external quantum efficiency exceeds 6.25%. This is because, in light-emitting element 10 according to one embodiment of the present invention, in addition to singlet excitons, triplet excitons can also contribute to fluorescent emission via the phosphorescent compound GD270. Furthermore, as described later, PCCzPTzn contained in light-emitting element 10 is a TADF material. Therefore, triplet excitons can contribute to fluorescent emission through anti-intersystem crossing generated by the TADF material, thereby improving luminous efficiency.

[0413] The luminous efficiency of light-emitting element 10 is higher than that of comparative light-emitting element 8. As described above, CBP, which is not a TADF material, is used in the light-emitting layer 130 of comparative light-emitting element 8. Therefore, comparative light-emitting element 8 does not have the function of converting triplet excitons into singlet excitons through anti-intersystem crossing caused by the TADF material. On the other hand, light-emitting element 10 according to one embodiment of the present invention includes a TADF material in the light-emitting layer 130. Therefore, in light-emitting element 10, triplet excitons can be converted into singlet excitons through anti-intersystem crossing caused by the TADF material, and luminous efficiency higher than that of comparative light-emitting element 8 can be achieved.

[0414] The luminous efficiency of the light-emitting element 10 is higher than that of the comparative light-emitting element 12. As described above, the light-emitting layer 130 of the comparative light-emitting element 12 contains a TADF material but does not contain a phosphorescent compound. Therefore, the comparative light-emitting element 12 cannot contribute triplet excitons to fluorescent light emission through the phosphorescent compound. On the other hand, the light-emitting element 10 according to one embodiment of the present invention contains a phosphorescent compound in addition to the TADF material in the light-emitting layer 130. Therefore, in the light-emitting element 10, in addition to the high efficiency effect of anti-intersystem crossing generated by the TADF material, the phosphorescent compound can also contribute triplet excitons to fluorescent light emission, thereby achieving a luminous efficiency higher than that of the comparative light-emitting element 12.

[0415] <Time-resolved luminescence measurement> Next, time-resolved luminescence measurement of the light-emitting element 10 and the comparative light-emitting element 11 was performed. Figure 33 The results are shown in FIG. 4. The measurement method is the same as that shown in the above examples.

[0416] like Figure 33 As shown in FIG. 1 , the luminescence of the light emitting element 10 decays faster than that of the comparative light emitting element 11. This indicates that in the light emitting element 10, the excitation energy is quickly converted into luminescence, and therefore, even in a state where the exciton density is high (a state where a large amount of current flows) in the light emitting layer, luminescence can be efficiently extracted. Figure 29 and Figure 31 As shown in FIG. 1 , the attenuation of the light emitting element 10 is small. The light emitting efficiency of the light emitting element 10 is higher than that of the comparative light emitting element 11. The light emitting layer 130 of the light emitting element 10 has a structure in which the fluorescent compound TBRb is added to the light emitting layer 130 of the comparative light emitting element 11. Figure 33 It is found that the addition of the fluorescent compound increases the decay rate of luminescence, thereby suppressing the deactivation of excitons and improving the luminous efficiency of the light-emitting element 10 compared to the comparative light-emitting element 11.

[0417] <Transition Fluorescence Characteristics of Host Materials> Here, in order to confirm whether the PCCzPTzn used in the light-emitting element 10 is a TADF material, the transition fluorescence characteristics were measured using time-resolved luminescence measurement. The time-resolved luminescence measurement was the same as the method shown in Example 1. In addition, a thin film formed by vapor-depositing PCCzPTzn on a quartz substrate with a thickness of 50 nm was used as the measurement sample.

[0418] Figure 34 Fig. shows the transition fluorescence characteristics of PCCzPTzn obtained by measurement.

[0419] Using Equation 4 to Figure 34 The decay curve shown was fitted. From the fitting results, it can be seen that the light emitted from the thin film sample of PCCzPTzn contains multiple luminescent components with different fluorescence lifetimes. The luminescent components of the thin film sample of PCCzPTzn at least include an instantaneous fluorescence component with a fluorescence lifetime of 15.0 ns and a delayed fluorescence component with the longest lifetime of 1.5 μs. In other words, PCCzPTzn is a thermally activated delayed fluorescence material that exhibits delayed fluorescence at room temperature.

[0420] <Measurement of S1 energy level and T1 energy level> Next, in order to calculate the S1 energy level and T1 energy level of PCCzPTzn, the emission spectrum of PCCzPTzn at low temperature (10 K) was measured. The measurement method was the same as the method shown in Example 1. Figure 35 Fig. shows the measurement results.

[0421] From Figure 35 it can be seen that the wavelengths of the peaks (including shoulders) on the shortest wavelength side of the fluorescence component and phosphorescence component of the emission spectrum of PCCzPTzn are 472 nm and 491 nm, respectively.

[0422] Therefore, the S1 energy level of PCCzPTzn calculated from the wavelengths of the above peaks (including shoulders) is 2.63 eV, the T1 energy level is 2.53 eV, and the energy difference between the S1 energy level and the T1 energy level is 0.10 eV.

[0423] From Figure 35 it can be seen that the wavelengths of the rises on the short wavelength side of the fluorescence component and phosphorescence component of the emission spectrum of PCCzPTzn are 450 nm and 477 nm, respectively. In addition, as the wavelength of the rise on the short wavelength side of the emission spectrum, the wavelength of the intersection of the tangent line of the spectrum at the wavelength where the slope of the tangent line has a maximum value and the horizontal axis is used.

[0424] The S1 energy level of PCCzPTzn calculated from the wavelength of the rise as described above is 2.76 eV, the T1 energy level is 2.60 eV, and the energy difference between the S1 energy level and the T1 energy level is 0.16 eV.

[0425] As described above, the energy difference between the S1 and T1 levels of PCCzPTzn, calculated from the wavelength of the peak (including the shoulder) on the shortest wavelength side of the emission spectrum and the wavelength of the short-wavelength rise, is extremely small, i.e., greater than 0 eV and less than 0.2 eV. This indicates that PCCzPTzn converts triplet excitation energy into singlet excitation energy through anti-intersystem crossing, resulting in thermally activated delayed fluorescence.

[0426] <Reliability of Light-Emitting Element> Figure 36 The results of the driving test when the constant current of the light emitting element 10, the comparative light emitting element 11, the comparative light emitting element 12, and the comparative light emitting element 8 was 2.0 mA are shown. Figure 36 It can be seen that the reliability of the light-emitting element 10 is higher than that of the comparative light-emitting element 11. As described above, the light-emitting element 10 obtains light emission from the fluorescent compound, and the comparative light-emitting element 11 obtains light emission from the phosphorescent compound. Therefore, it can be seen that the reliability is improved when light emission is obtained from the fluorescent compound as in the light-emitting element of one embodiment of the present invention. In addition, it can be seen that the reliability of the light-emitting element 10 is higher than that of the comparative light-emitting element 12. As described above, in the light-emitting element 10, the triplet excitation energy can be transferred to the fluorescent compound through the TADF material and the phosphorescent compound. On the other hand, in the comparative light-emitting element 12, the triplet excitation energy is transferred to the fluorescent compound only through the TADF material. Therefore, as in the light-emitting element of one embodiment of the present invention, when there are multiple paths for transferring the triplet excitation energy to the fluorescent compound, the reliability of the light-emitting element is further improved. In addition, it can be seen that the reliability of the light-emitting element 10 is higher than that of the comparative light-emitting element 8. By using a host material having TADF properties, a highly reliable light-emitting element can be obtained.

[0427] As described above, one embodiment of the present invention can provide a light-emitting element having high luminous efficiency and good reliability. In addition, one embodiment of the present invention can provide a light-emitting element having low driving voltage and low power consumption. [Example 4]

[0428] In this embodiment, a light emitting element according to one embodiment of the present invention and a comparative light emitting element are described. The structure of each light emitting element manufactured in this embodiment is similar to that of the light emitting element. Figure 1A Similarly, the details of the element structure are shown in Table 7. The structures and abbreviations of the compounds used can be referred to the above examples and embodiments.

[0429] [Table 7]

[0430] <Manufacturing of Light-Emitting Element> A method for manufacturing the light-emitting element manufactured in this embodiment will be described below.

[0431] Manufacturing of Light-Emitting Element 13 As the electrode 101, a 70 nm thick ITSO film was formed on a glass substrate. The electrode area of ​​the electrode 101 was 4 mm 2 (2mm×2mm).

[0432] As the hole injection layer 111 , DBT3P-II and molybdenum oxide (MoO 3 ) were co-evaporated on the electrode 101 at a weight ratio (DBT3P-II:MoO 3 ) of 1:0.5 and a thickness of 45 nm.

[0433] Next, mCzFLP was deposited on the hole injection layer 111 to a thickness of 20 nm as the hole transport layer 112 .

[0434] Next, mPCCzPTzn-02, GD270 (manufactured by Jilin Aolaide Optoelectronic Materials Co., Ltd.), and TBRb were co-evaporated onto hole-transport layer 112 to form light-emitting layer 130. A weight ratio of mPCCzPTzn-02:GD270:TBRb was 0.8:0.2:0.01, resulting in a thickness of 40 nm. In light-emitting layer 130, GD270 is a phosphorescent compound, and TBRb is a fluorescent compound.

[0435] Next, mPCCzPTzn-02 and NBPhen were sequentially deposited to a thickness of 20 nm on the light-emitting layer 130 as the electron transport layer 118. Next, LiF was deposited to a thickness of 1 nm on the electron transport layer 118 as the electron injection layer 119.

[0436] Next, aluminum (Al) was deposited to a thickness of 200 nm on the electron injection layer 119 as the electrode 102 .

[0437] Next, in a glove box with a nitrogen atmosphere, a sealing glass substrate was fixed to the glass substrate on which the organic material was formed using an organic EL sealant, thereby sealing the light-emitting element 13. Specifically, the sealant was applied around the organic material formed on the glass substrate, and the glass substrate and the sealing glass substrate were bonded together. 2 The film was irradiated with ultraviolet light having a wavelength of 365 nm and heated at 80° C. for 1 hour. The light-emitting element 13 was obtained through the above steps.

[0438] Comparative Manufacturing of Light-Emitting Element 14 The only difference between the light emitting element 14 and the light emitting element 13 is the process of forming the light emitting layer 130 , while the other processes are manufactured using the same method as the light emitting element 13 .

[0439] Comparative light-emitting element 14's light-emitting layer 130 was formed by co-evaporation of mPCCzPTzn-02 and GD270 at a weight ratio (mPCCzPTzn-02:GD270) of 0.8:0.2 to a thickness of 40 nm. Unlike light-emitting layer 130 of light-emitting element 13, light-emitting layer 130 of comparative light-emitting element 14 did not contain the fluorescent compound TBRb.

[0440] Manufacturing of Comparative Light-Emitting Element 15 The only difference between the light-emitting element 15 and the light-emitting element 13 is the process of forming the hole transport layer 112 and the light-emitting layer 130 . The other processes are manufactured using the same method as the light-emitting element 13 .

[0441] As the hole transport layer 112 of the comparative light-emitting element 15 , PCCP was deposited on the hole injection layer 111 to a thickness of 20 nm.

[0442] Next, mPCCzPTzn-02 and TBRb were co-evaporated at a weight ratio (mPCCzPTzn-02:TBRb) of 1:0.01 to a thickness of 30 nm as light-emitting layer 130. Unlike light-emitting layer 130 of light-emitting element 13, light-emitting layer 130 of comparative light-emitting element 15 did not contain the phosphorescent compound GD270.

[0443] <Characteristics of Light-Emitting Element> Next, the characteristics of the light-emitting element 13, the comparative light-emitting element 14, the comparative light-emitting element 15, and the comparative light-emitting element 8 manufactured as described above were measured. Note that the measurement method was the same as that of Example 1.

[0444] Figure 37 The current efficiency-luminance characteristics of the light-emitting element 13, the comparative light-emitting element 14, the comparative light-emitting element 15, and the comparative light-emitting element 8 are shown. Figure 38 Showing the current-voltage characteristics, Figure 39 The external quantum efficiency-brightness characteristics are shown. Figure 40 Shown at 2.5 mA / cm 2 Electroemission spectra when a current of a current density of 100 Å was passed through Light-Emitting Element 13, Comparative Light-Emitting Element 14, Comparative Light-Emitting Element 15, and Comparative Light-Emitting Element 8. The measurements of each light-emitting element were performed at room temperature (an atmosphere maintained at 23° C.).

[0445] Table 8 shows 1000 cd / m 2 Element characteristics of the nearby light-emitting element 13 , the comparative light-emitting element 14 , and the comparative light-emitting element 15 .

[0446] [Table 8]

[0447] like Figure 40 As shown, the peak wavelengths of the emission spectra of light-emitting element 13, comparative light-emitting element 8 and comparative light-emitting element 15 are 564 nm, 562 nm and 562 nm, respectively, and the full width at half maximum is about 72 nm, 67 nm and 69 nm, respectively. This means that light-emitting element 13, comparative light-emitting element 8 and comparative light-emitting element 15 emit yellow light. Therefore, the light emitted by light-emitting element 13, comparative light-emitting element 8 and comparative light-emitting element 15 comes from the fluorescent compound TBRb. In addition, the peak wavelength of the emission spectrum of comparative light-emitting element 14 is 527 nm, and the full width at half maximum is 73 nm. This means that comparative light-emitting element 14 emits green light. Therefore, the light emitted by comparative light-emitting element 14 comes from GD270. Therefore, the full width at half maximum of the peak wavelength of the emission spectrum of light-emitting element 13 of one embodiment of the present invention is smaller than that of comparative light-emitting element 14, and light-emitting element 13 can emit light with higher color purity than that of comparative light-emitting element 14. Therefore, the light-emitting element of one embodiment of the present invention is suitable for use in a display device.

[0448] like Figure 37 、 Figure 39 As shown in Table 8, although Light-Emitting Element 13 is a fluorescent light-emitting element, its external quantum efficiency exceeds 6.25%. This is because, in Light-Emitting Element 13 according to one embodiment of the present invention, in addition to singlet excitons, triplet excitons can also contribute to fluorescence via the phosphorescent compound GD270. Furthermore, as described later, mPCCzPTzn-02 contained in Light-Emitting Element 13 is a TADF material. Therefore, triplet excitons can contribute to fluorescence through anti-intersystem crossing generated by the TADF material, thereby improving luminous efficiency.

[0449] The luminous efficiency of light-emitting element 13 is higher than that of comparative light-emitting element 8. As described above, CBP, which is not a TADF material, is used in the light-emitting layer 130 of comparative light-emitting element 8. Therefore, comparative light-emitting element 8 does not have the function of converting triplet excitons into singlet excitons through anti-intersystem crossing caused by the TADF material. On the other hand, light-emitting element 13 according to one embodiment of the present invention includes a TADF material in the light-emitting layer 130. Therefore, in light-emitting element 13, triplet excitons can be converted into singlet excitons through anti-intersystem crossing caused by the TADF material, and luminous efficiency higher than that of comparative light-emitting element 8 can be achieved.

[0450] The luminous efficiency of the light-emitting element 13 is higher than that of the comparative light-emitting element 15. As described above, the TADF material is included in the light-emitting layer 130 of the comparative light-emitting element 15, and the phosphorescent compound is not included. Therefore, the comparative light-emitting element 15 cannot contribute triplet excitons to fluorescence emission through the phosphorescent compound. On the other hand, the light-emitting element 13 according to an embodiment of the present invention includes a phosphorescent compound in addition to the TADF material in the light-emitting layer 130. Therefore, triplet excitons can be contributed to fluorescence emission through the phosphorescent compound, and a luminous efficiency higher than that of the comparative light-emitting element 15 can be achieved.

[0451] <Time-resolved luminescence measurement> Next, in order to confirm whether mPCCzPTzn-02 is a TADF material, time-resolved luminescence measurement was performed. Figure 41 The results are shown. The measurement method is the same as the method shown in the above-described embodiment. In addition, the light-emitting element 16 having the element structure shown in Table 9 below was used in the measurement.

[0452] [Table 9] [[ID=

[14]

[0453] As Figure 41 shown, in the light-emitting element 16, multiple luminescent components having different fluorescence lifetimes were observed. Specifically, an instantaneous fluorescence component having a short luminescence lifetime and a delayed fluorescence component having a long luminescence lifetime were observed. Therefore, mPCCzPTzn-02 is a TADF material. On the other hand, from Figure 41 it can be seen that the ratio of the delayed fluorescence component in the overall luminescent components (instantaneous luminescent component and delayed fluorescence component) is about 10%. This means that the ratio of converting singlet excitons into luminescence after converting triplet excitons into singlet excitons is estimated to be about 4%. Therefore, mPCCzPTzn-02 has TADF properties, but its luminous efficiency is not high. However, as described above, a very high external quantum efficiency, that is, more than 27%, can be obtained from the light-emitting element 13. Therefore, the TADF material for the light-emitting element according to an embodiment of the present invention may have a low luminous efficiency as long as it has TADF properties

[0454] <Measurement of S1 energy level and T1 energy level> Next, in order to calculate the S1 energy level and T1 energy level of mPCCzPTzn-02, the emission spectrum of mPCCzPTzn-02 at a low temperature (10K) was measured. The measurement method is the same as the method shown in Example 1. Figure 42 The measurement results are shown.

[0455] From Figure 42It was found that the wavelengths of the peaks (including the shoulder peaks) on the shortest wavelength side of the fluorescence component and the phosphorescence component of the emission spectrum of mPCCzPTzn-02 were 471 nm and 496 nm, respectively.

[0456] Therefore, the S1 level of mPCCzPTzn-02 calculated from the wavelength of the above peak (including the shoulder peak) is 2.63 eV, the T1 level is 2.50 eV, and the energy difference between the S1 level and the T1 level is 0.13 eV.

[0457] As described above, the energy difference between the S1 and T1 levels of mPCCzPTzn-02, calculated from the wavelength of the peak (including the shoulder) on the shortest wavelength side of the emission spectrum, is extremely small, exceeding 0 eV and falling below 0.2 eV. This suggests that mPCCzPTzn-02 converts triplet excitation energy into singlet excitation energy via anti-intersystem crossing, resulting in thermally activated delayed fluorescence.

[0458] <Reliability of Light-Emitting Element> Figure 43 The results of the driving test when the constant current of the light emitting element 13, the comparative light emitting element 14, the comparative light emitting element 15, and the comparative light emitting element 8 was 2.0 mA are shown. Figure 43 It can be seen that the reliability of light-emitting element 13 is higher than that of comparative light-emitting element 14. As described above, light emission from the fluorescent compound is obtained in light-emitting element 13, and light emission from the phosphorescent compound is obtained in comparative light-emitting element 14. Therefore, it can be seen that the reliability is improved when light emission is obtained from the fluorescent compound as in the light-emitting element of one embodiment of the present invention. In addition, it can be seen that the reliability of light-emitting element 13 is higher than that of comparative light-emitting element 15. As described above, in light-emitting element 13, triplet excitation energy can be transferred to the fluorescent compound through the TADF material and the phosphorescent compound. On the other hand, in comparative light-emitting element 15, triplet excitation energy is transferred to the fluorescent compound only through the TADF material. Therefore, as in the light-emitting element of one embodiment of the present invention, the reliability of the light-emitting element is further improved when there are multiple paths for transferring triplet excitation energy to the fluorescent compound. In addition, it can be seen that the reliability of light-emitting element 13 is higher than that of comparative light-emitting element 8. By using a host material having TADF properties, a highly reliable light-emitting element can be obtained.

[0459] As described above, one embodiment of the present invention can provide a light-emitting element having high luminous efficiency and good reliability. In addition, one embodiment of the present invention can provide a light-emitting element having low driving voltage and low power consumption. [Example 5]

[0460] In this embodiment, a light emitting element according to one embodiment of the present invention and a comparative light emitting element are described. The structure of each light emitting element manufactured in this embodiment is similar to that of the light emitting element. Figure 1A Similarly, the details of the element structure are shown in Table 10. The structures and abbreviations of the compounds used can be referred to the above examples and embodiments.

[0461] [Table 10]

[0462] <Manufacturing of Light-Emitting Element> A method for manufacturing the light-emitting element manufactured in this embodiment will be described below.

[0463] <Manufacturing of Light-Emitting Element 17> As the electrode 101, a 70 nm thick ITSO film was formed on a glass substrate. The electrode area of ​​the electrode 101 was 4 mm 2 (2mm×2mm).

[0464] As the hole injection layer 111 , DBT3P-II and molybdenum oxide (MoO 3 ) were co-evaporated on the electrode 101 at a weight ratio (DBT3P-II:MoO 3 ) of 1:0.5 and a thickness of 45 nm.

[0465] Next, mCzFLP was deposited on the hole injection layer 111 to a thickness of 20 nm as the hole transport layer 112 .

[0466] Next, mPCCzPTzn-02, PCCP, GD270, and TBRb were co-evaporated onto the hole-transporting layer 112 at a weight ratio (mPCCzPTzn-02:PCCP:GD270:TBRb) of 0.5:0.5:0.1:0.01 to a thickness of 40 nm to form the light-emitting layer 130. In the light-emitting layer 130, TBRb is a fluorescent compound.

[0467] Next, mPCCzPTzn-02 and NBPhen were sequentially deposited to a thickness of 20 nm on the light-emitting layer 130 as the electron transport layer 118. Next, LiF was deposited to a thickness of 1 nm on the electron transport layer 118 as the electron injection layer 119.

[0468] Next, aluminum (Al) was deposited to a thickness of 200 nm on the electron injection layer 119 as the electrode 102 .

[0469] Next, in a glove box with a nitrogen atmosphere, a sealing glass substrate was fixed to the glass substrate on which the organic material was formed using an organic EL sealant, thereby sealing the light-emitting element 17. Specifically, the sealant was applied around the organic material formed on the glass substrate, and the glass substrate and the sealing glass substrate were bonded together. 2The film was irradiated with ultraviolet light having a wavelength of 365 nm and heated at 80° C. for 1 hour. The light-emitting element 17 was obtained through the above steps.

[0470] Comparative Manufacturing of Light-Emitting Element 18 The only difference between the light emitting element 18 and the light emitting element 17 is the process of forming the light emitting layer 130 , while the other processes are manufactured using the same method as the light emitting element 17 .

[0471] Comparative light-emitting element 18 formed light-emitting layer 130 by co-evaporation of mPCCzPTzn-02, PCCP, and GD270 at a weight ratio (mPCCzPTzn-02:PCCP:GD270) of 0.5:0.5:0.1 to a thickness of 40 nm. Compared to light-emitting layer 130 of light-emitting element 17, light-emitting layer 130 of comparative light-emitting element 18 did not contain the fluorescent compound TBRb.

[0472] <Characteristics of Light-Emitting Element> Next, the characteristics of the light-emitting element 17, the comparative light-emitting element 18, and the light-emitting element 13 manufactured as described above were measured. Note that the measurement method was the same as that of Example 1.

[0473] Figure 44 The current efficiency-luminance characteristics of the light-emitting element 17, the comparative light-emitting element 18, and the light-emitting element 13 are shown. Figure 45 Showing the current-voltage characteristics, Figure 46 The external quantum efficiency-brightness characteristics are shown. Figure 47 Shown at 2.5 mA / cm 2 Electroemission spectra when a current of a current density of 100 Å was passed through Light-Emitting Element 17, Comparative Light-Emitting Element 18, and Light-Emitting Element 13. The measurement of each light-emitting element was performed at room temperature (an atmosphere maintained at 23° C.).

[0474] Table 11 shows 1000 cd / m 2 Element characteristics of the nearby light-emitting element 17 and the comparative light-emitting element 18.

[0475] [Table 11]

[0476] like Figure 47As shown, the peak wavelengths of the electroluminescence spectra of the light-emitting element 17 and the light-emitting element 13 are 559 nm and 564 nm, respectively, and the full widths at half maximum are about 71 nm and 72 nm, respectively. This means that the light-emitting element 17 and the light-emitting element 13 emit yellow light. Therefore, the light emitted by the light-emitting element 17 and the light-emitting element 13 is derived from the fluorescent compound TBRb. In addition, the peak wavelength of the electroluminescence spectrum of the comparative light-emitting element 18 is 524 nm, and the full width at half maximum is 72 nm. This means that the comparative light-emitting element 18 emits green light. Therefore, the light emitted by the comparative light-emitting element 18 is derived from the phosphorescent compound GD270.

[0477] As Figure 44 , Figure 46 and Table 11 show, the light-emitting element 17, the comparative light-emitting element 18, and the light-emitting element 13 have very high luminous efficiencies (current efficiency, power efficiency, and external quantum efficiency). Although the light-emitting element 17 is a fluorescent light-emitting element, the external quantum efficiency is very high, that is, it greatly exceeds 6.25%. This is because in addition to the light emission from singlet excitons generated by the recombination of carriers (holes and electrons), light emission from triplet excitons is also obtained, which means that the excitation energy moves to the fluorescent compound TBRb through the phosphorescent compound GD270. In addition, as described above, mPCCzPTzn-02 contained in the light-emitting element 17 is a TADF material. Therefore, triplet excitons can contribute to fluorescent light emission due to the reverse intersystem crossing generated by the TADF material, so the luminous efficiency can be improved.

[0478] <CV measurement results> Next, cyclic voltammetry (CV) measurements were performed on the electrochemical properties (oxidation reaction properties and reduction reaction properties) of the above compounds to calculate the HOMO energy level and LUMO energy level of the above compounds. The measurement method is the same as that in Example 1 above.

[0479] According to the CV measurement, the HOMO energy level of mPCCzPTzn-02 is -5.69 eV, the LUMO energy level is -3.00 eV, the HOMO energy level of PCCP is -5.63 eV, and the LUMO energy level is -1.96 eV.

[0480] Therefore, the HOMO energy level of mPCCzPTzn-02 is higher than that of PCCP, and the LUMO energy level is lower than that of PCCP. Thus, mPCCzPTzn-02 and PCCP are a combination that forms an exciplex in the light-emitting layer.

[0481] The S1 and T1 levels calculated from the peak wavelengths of the emission spectrum of the exciplex formed by mPCCzPTzn-02 and PCCP are both 2.45 eV. The T1 level of GD270 is 2.44 eV (calculated from the absorption edge of the chloroform solution), indicating that the exciplex's excitation energy can be transferred to GD270.

[0482] <Investigation of Exciplex Formation> To investigate whether mPCCzPTzn-02 and PCCP form an exciplex, Light-Emitting Element 19 and the aforementioned Light-Emitting Element 16 shown in Table 12 were produced. Furthermore, the presence or absence of exciplex formation was investigated by comparing the emission spectrum of mPCCzPTzn-02 with the emission spectrum of a mixed film of mPCCzPTzn-02 and PCCP.

[0483] [Table 12]

[0484] EL Spectrum Figure 48 Shown to make 2.5mA / cm 2 EL spectrum obtained when a current of 100 Ω flows through the light emitting element 16 and the light emitting element 19. Figure 48 It can be seen that light originating from mPCCzPTzn-02 is obtained in Light-Emitting Element 16. Here, the light from Light-Emitting Element 19 has a peak at a longer wavelength than the light from Light-Emitting Element 16. The luminescence energy (2.45 eV) calculated from the peak wavelength of the emission spectrum of Light-Emitting Element 19 roughly matches the difference (2.63 eV) between the LUMO level of mPCCzPTzn-02 and the HOMO level of PCCP. Therefore, an exciplex is formed between mPCCzPTzn-02 and PCCP.

[0485] Time-resolved fluorescence Time-resolved fluorescence measurement was performed on the light-emitting element 16 and the light-emitting element 19 . Figure 49 The results are shown. Figure 49 It can be seen that the ratio of the delayed fluorescence component in Light-emitting Element 19 is greater than that in Light-emitting Element 16. In addition, Light-emitting Element 19 contains a light-emitting component with a longer lifetime than that of Light-emitting Element 16. In other words, the transient response characteristics of Light-emitting Element 16 and Light-emitting Element 19 differ. Therefore, an exciplex is formed by mPCCzPTzn-02 and PCCP.

[0486] <Relationship between the Emission Spectrum of the Exciplex and the Absorption Spectrum of the Guest Material> Figure 50 Shown are the results of measuring the absorption spectrum of a toluene solution of TBRb and the emission spectrum of the comparative light-emitting element 18. The measurement was performed in the same manner as in the above-described embodiment.

[0487] like Figure 50 As shown, the absorption spectrum of TBRb and the emission spectrum of the comparative light-emitting element 18 partially overlap. Therefore, the excitation energy can be efficiently supplied from the exciplex formed by mPCCzPTzn-02 and PCCP to the fluorescent compound TBRb through GD270. By moving the energy to TBRb through the phosphorescent compound GD270, the triplet excitation energy can contribute to the fluorescent light emission. When mPCCzPTzn-02 that has not formed an exciplex is excited, since mPCCzPTzn-02 has TADF properties, singlet excitons are generated from triplet excitons through anti-intersystem crossing. In the light-emitting layer 130, due to the generation of singlet excitons of the above-mentioned TADF material and the transfer of triplet excitation energy to the fluorescent compound TBRb through the phosphorescent compound GD270, the light-emitting element 17 can obtain extremely high luminous efficiency.

[0488] <Reliability of Light-Emitting Element> The driving test was performed on the light emitting element 17, the comparative light emitting element 18 and the light emitting element 13 at a constant current of 2.0 mA. Table 13 shows the LT of the driving test. 60 (Time when brightness is reduced by 40%).

[0489] [Table 13] <![CDATA[LT 60 (h)]]> Light emitting element 17 690 Comparative Light Emitting Element 18 430 Light-emitting element 13 580

[0490] As can be seen from Table 13, the light emitting element 17, the comparative light emitting element 18, and the light emitting element 13 have good reliability. In addition, it can be seen that the reliability of the light emitting element 17 is higher than that of the comparative light emitting element 18. 60 It is longer than the light-emitting element 13. Therefore, by using a TADF material as a host material and utilizing an exciplex, a light-emitting element with good reliability can be obtained. Explanation of symbols

[0491] 100: EL layer, 101: Electrode, 102: Electrode, 106: Light-emitting unit, 108: Light-emitting unit, 111: Hole injection layer, 112: Hole transport layer, 113: Electron transport layer, 114: Electron injection layer, 115: Charge generation layer, 116: Hole injection layer, 117: Hole transport layer, 118: Electron transport layer, 119: Electron injection layer, 120: Light-emitting layer, 130: Light-emitting layer, 131: Compound, 132: Compound, 133: Compound, 134: Compound, 150: Light-emitting element, 170: Light-emitting layer, 250: Light-emitting element, 601: Source-side driver circuit, 602: Pixel portion, 603: Gate-side driver circuit, 604: Sealing substrate, 6 05: Sealant, 607: Space, 608: Wiring, 609: FPC, 610: Element Substrate, 611: Switching TFT, 612: Current Control TFT, 613: Electrode, 614: Insulator, 616: EL Layer, 617: Electrode, 618: Light-Emitting Element, 623: N-Channel TFT, 624: P-Channel TFT, 625: Desiccant, 900: Portable Information Terminal, 901: Housing, 902: Housing, 903: Display, 905: Hinge, 910: Portable Information Terminal, 911: Housing, 912: Display, 913: Operation Button, 914: External Connection Port, 915: Speaker, 916: Microphone, 917: Camera, 920 : Camera, 921: Housing, 922: Display portion, 923: Operation button, 924: Shutter button, 926: Lens, 1001: Substrate, 1002: Base insulating film, 1003: Gate insulating film, 1006: Gate electrode, 1007: Gate electrode, 1008: Gate electrode, 1020: Interlayer insulating film, 1021: Interlayer insulating film, 1022: Electrode, 1024B: Electrode, 1024G: Electrode, 1024R: Electrode, 1024W: Electrode, 1025B: Lower electrode, 1025G: Lower electrode, 1025R: Lower electrode, 1025W: Lower electrode, 1026: Partition wall, 1028: EL layer, 1029: Electrode, 1031: Sealing substrate, 1 032: Sealant, 1033: Base material, 1034B: Colored layer, 1034G: Colored layer, 1034R: Colored layer, 1035: Black layer, 1036: Protective layer, 1037: Interlayer insulating film, 1040: Pixel portion, 1041: Driver circuit portion, 1042: Peripheral portion, 1044B: Blue pixel, 1044G: Green pixel, 1044R: Red pixel, 1044W: White pixel, 2100: Robot, 2101: Illumination sensor, 2102: Microphone, 2103: Upper camera, 2104: Speaker, 2105: Display, 2106: Lower camera, 2107: Obstacle sensor, 2108: Moving mechanism, 2110: Computing device,5000: Housing, 5001: Display unit, 5002: Display unit, 5003: Speaker, 5004: LED light, 5005: Operation key, 5006: Connection terminal, 5007: Sensor, 5008: Microphone, 5012: Support unit, 5013: Earphone, 5100: Cleaning robot, 5101: Display, 5102: Camera, 5103: Brush, 5104: Operation button, 5120: Trash, 5140: Portable electronic device, 5150: Portable information terminal, 5151: Housing, 5152: Display area, 5153: Bending unit, 8501: Lighting device, 8502: Lighting device, 8503: Lighting device, 8504: Lighting device. This application is based on Japanese Patent Application No. 2017-213080 filed with the Japan Patent Office on November 2, 2017, the entire contents of which are incorporated herein by reference.

Claims

1. A light emitting device, comprising: a first electrode; The light-emitting layer on the first electrode comprises: a first organic compound configured to convert triplet excitation energy into luminescence; a second organic compound; and a third organic compound configured to convert singlet excitation energy into luminescence; and a second electrode on the luminescent layer, wherein a difference between the lowest singlet excitation energy level of the second organic compound and the lowest triplet excitation energy level of the second organic compound is greater than or equal to 0 eV and less than or equal to 0.2 eV, And, the light emitted from the light emitting layer includes the light emitted from the third organic compound.

Citation Information

Patent Citations

  • Light-emitting element

    JP2014045179A

  • Game machine

    JP2017213080A